Glacier elevation changes (2012–2016) of the Puruogangri Ice Field on the Tibetan Plateau derived from bi-temporal TanDEM-X InSAR data - Lin Liu; Liming Jiang; Yafei Sun; Chaolu Yi; Hansheng Wang; Houtse Hsu (International Journal of Remote Sensing, 2016)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

Three new triterpenoid saponins from the roots of Ardisia crenata and their cytotoxic activities - Dai-Lin Liu; Xue Zhang; Yanmin Zhao; Nai-Li Wang; Xin-Sheng Yao (Natural Product Research, 2016)

Synthesis and biological evaluation of n-butylphthalide derivatives as anti-platelet aggregation agents - Meihui Chen; Qi Liu; Min Tan; Shijun Wen; Rongbiao Pi; Dingkun Lin (Natural Product Research, 2016)

Essential oil composition and antibacterial activity of Lindera nacusua (D. Don) Merr. - Guoqing Wei; Lin Kong; Jiasui Zhang; Chaoying Ma; Xiaoqing Wu; Xueru Li; Hezhong Jiang (Natural Product Research, 2016)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

Weight and prognosis for influenza A(H1N1)pdm09 infection during the pandemic period between 2009 and 2011: a systematic review of observational studies with meta-analysis - Ying Sun; Quanyi Wang; Guoyan Yang; Changying Lin; Yi Zhang; Peng Yang (Infectious Diseases, 2016)

NH3-SCR Performance of Mn-Fe/TiO2 Catalysts at Low Temperature in the Absence and Presence of Water Vapor - Lin Zhu; Zhaoping Zhong; Han Yang; Chunhua Wang (Water, Air, & Soil Pollution, 2016)

Hydrology Drives Vegetation Succession in a Tidal Freshwater Wetland of Subtropical Taiwan - Hsing-Juh Lin; Chun-Han Huang; Gwo-Wen Hwang; Chorng-Bin Hsu; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2016)

Ectopic expression of a SOC1 homolog from Phyllostachys violascens alters flowering time and identity of floral organs in Arabidopsis thaliana - Shinan Liu; TianTian Qi; JingJing Ma; Tengfei Ma; Luyi Ma; Xinchun Lin (Trees, 2016)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

The Diagnosis and Natural History of Multiple System Atrophy, Cerebellar Type - David J. Lin; Katherine L. Hermann; Jeremy D. Schmahmann (The Cerebellum, 2016)

The spatio-temporal characteristics of potential dengue risk assessed by Aedes aegypti and Aedes albopictus in high-epidemic areas - Chia-Hsien Lin; Tzai-Hung Wen; Hwa-Jen Teng; Niann-Tai Chang (Stochastic Environmental Research and Risk Assessment, 2016)

Interleukin-17 inhibits development of malignant pleural effusion via interleukin-9-dependent mechanism - Yong Lu; Hua Lin; Kan Zhai; Xiaojuan Wang; Qiong Zhou; Huanzhong Shi (Science China Life Sciences, 2016)

Features and origin time of Mesozoic strike-slip structures in the Yilan-Yitong Fault Zone - ChengChuan Gu; Guang Zhu; MingJian Zhai; ShaoZe Lin; LiHong Song; Bei Liu (Science China Earth Sciences, 2016)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Local background climate determining the dynamics of plateau lakes in China - Lin Huang; Xinliang Xu; Jun Zhai; Chaoyang Sun (Regional Environmental Change, 2016)

Generating Random Earthquake Events for Probabilistic Tsunami Hazard Assessment - Randall J. LeVeque; Knut Waagan; Frank I. González; Donsub Rim; Guang Lin (Pure and Applied Geophysics, 2016)

Genome-Wide Discovery of Tissue-Specific Genes in Maize - Feng Lin; Huabin Bao; Jun Yang; Yuhe Liu; Huixue Dai; Han Zhao (Plant Molecular Biology Reporter, 2016)

Traits of dominant tree species predict local scale variation in forest aboveground and topsoil carbon stocks - Dunmei Lin; Kristina J. Anderson-Teixeira; Jiangshan Lai; Xiangcheng Mi; Haibao Ren; Keping Ma (Plant and Soil, 2016)

Development of an In Planta system to monitor phosphorus status by agroinfiltration and agroinjection - Jia-Ying Lin; Tzyy-Jen Chiou; Hsiao-Feng Lo; Shu-I Lin (Plant and Soil, 2016)

ER-localized adenine nucleotide transporter ER-ANT1: an integrator of energy and stress signaling in rice - Xiangqian Zhang; Xu Zheng; Shanwen Ke; Haitao Zhu; Fang Liu; Zemin Zhang; Xinxiang Peng; Lin Guo; Ruizhen Zeng; Pei Hou; Ziqiang Liu; Suowei Wu; et al. (Plant Molecular Biology, 2016)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

Multiple metrics of diversity have different effects on temperate forest functioning over succession - Zuoqiang Yuan; Shaopeng Wang; Antonio Gazol; Jarad Mellard; Fei Lin; Ji Ye; Zhanqing Hao; Xugao Wang; Michel Loreau (Oecologia, 2016)

Hydroregulation in a tropical dry-skinned ectotherm - Anna F. V. Pintor; Lin Schwarzkopf; Andrew K. Krockenberger (Oecologia, 2016)

Risks Associated with Misuse of Ketamine as a Rapid-Acting Antidepressant - Weili Zhu; Zengbo Ding; Yinan Zhang; Jie Shi; Kenji Hashimoto; Lin Lu (Neuroscience Bulletin, 2016)

Special Topic on Mental Health and Addiction - Lin Lu; Wenhua Zhou (Neuroscience Bulletin, 2016)

On the Eve of Upgrading Antidepressants: (R)-Ketamine and Its Metabolites - Kai Yuan; Ying Han; Kenji Hashimoto; Lin Lu (Neuroscience Bulletin, 2016)

Extracellular Signal-Regulated Kinase in Nucleus Accumbens Mediates Propofol Self-Administration in Rats - Benfu Wang; Xiaowei Yang; Anna Sun; Lanman Xu; Sicong Wang; Wenxuan Lin; Miaojun Lai; Huaqiang Zhu; Wenhua Zhou; Qingquan Lian (Neuroscience Bulletin, 2016)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

The Other Face of the Nucleus Accumbens: Aversion - Ying Han; Lin Lu (Neuroscience Bulletin, 2016)

Identifying N 6-methyladenosine sites in the Arabidopsis thaliana transcriptome - Wei Chen; Pengmian Feng; Hui Ding; Hao Lin (Molecular Genetics and Genomics, 2016)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

NMR-Based Metabolomics Reveal a Recovery from Metabolic Changes in the Striatum of 6-OHDA-Induced Rats Treated with Basic Fibroblast Growth Factor - Hong Zheng; Liangcai Zhao; Huanhuan Xia; Cuicui Xu; Dan Wang; Kun Liu; Li Lin; Xiaokun Li; Zhihan Yan; Hongchang Gao (Molecular Neurobiology, 2016)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

The genus Fusariella - Chuan-Gen Lin; Yun Chen; Eric H. C. McKenzie; Darbhe J. Bhat; Hiran A. Ariyawansa; Kevin D. Hyde; Yong Wang (Mycological Progress, 2016)

An unusual Lophodermium species on needles of Pinus taiwanensis from China - Zhi-Jie Li; J. E. Taylor; Cheng-Lin Hou (Mycological Progress, 2016)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

A GWA study reveals genetic loci for body conformation traits in Chinese Laiwu pigs and its implications for human BMI - Lisheng Zhou; Jiuxiu Ji; Song Peng; Zhen Zhang; Shaoming Fang; Lin Li; Yaling Zhu; Lusheng Huang; Congying Chen; Junwu Ma (Mammalian Genome, 2016)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Genome Duplication and Evolution of Heat Shock Transcription Factor (HSF) Gene Family in Four Model Angiosperms - Yuxin Zhu; Hanwei Yan; Yiyi Wang; Lin Feng; Zhu Chen; Yan Xiang (Journal of Plant Growth Regulation, 2016)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

Low-Cost High-Accuracy QRS Detection for Body Area Network Applications - Kuang-Hao Lin; Jen-Hao Wu (Journal of Medical and Biological Engineering, 2016)

2-Methylisoborneol production characteristics of Pseudanabaena sp. FACHB 1277 isolated from Xionghe Reservoir, China - Ting Zhang; Lingling Zheng; Lin Li; Lirong Song (Journal of Applied Phycology, 2016)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Regulation of peroxisome proliferator-activated receptor gamma on milk fat synthesis in dairy cow mammary epithelial cells - Lili Liu; Ye Lin; Lixin Liu; Lina Wang; Yanjie Bian; Xuejun Gao; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)

Effect of sustained training on glycolysis and fatty acids oxidation in swimming muscles and liver in juvenile tinfoil barb Barbonymus schwanenfeldii (Bleeker, 1854) - Zhiming Zhu; Bolan Song; Xiaotao Lin; Zhongneng Xu (Fish Physiology and Biochemistry, 2016)

Molecular characterization and expression analysis of AMPK α subunit isoform genes from Scophthalmus maximus responding to salinity stress - Lin Zeng; Bin Liu; Chang-Wen Wu; Ji-Lin Lei; Mei-Ying Xu; Ai-Yi Zhu; Jian-She Zhang; Wan-Shu Hong (Fish Physiology and Biochemistry, 2016)

High-intensity Interval training enhances mobilization/functionality of endothelial progenitor cells and depressed shedding of vascular endothelial cells undergoing hypoxia - Hsing-Hua Tsai; Chin-Pu Lin; Yi-Hui Lin; Chih-Chin Hsu; Jong-Shyan Wang (European Journal of Applied Physiology, 2016)

Accumulation behavior and risk assessment of heavy metals and arsenic in tissues of white bream (Parabramis pekinensis) from the Xiang River, southern China - Yuyu Jia; Qian Kong; Zhaoguang Yang; Lin Wang (Environmental Science and Pollution Research, 2016)

Effect of di-n-butyl phthalate (DBP) on the fruit quality of cucumber and the health risk - Lei Wang; Xin Sun; Qin Chang; Yue Tao; Lihua Wang; Junwei Dong; Yulong Lin; Ying Zhang (Environmental Science and Pollution Research, 2016)

Removal of polybrominated diphenyl ethers by biomass carbon-supported nanoscale zerovalent iron particles: influencing factors, kinetics, and mechanism - Rongbing Fu; Zhen Xu; Lin Peng; Dongsu Bi (Environmental Science and Pollution Research, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Population genetic diversity and geographical differentiation of MHC class II DAB genes in the vulnerable Chinese egret (Egretta eulophotes) - Wei Lei; Wenzhen Fang; Xiaoping Zhou; Qingxian Lin; Xiaolin Chen (Conservation Genetics, 2016)

Monitoring early-flood season intraseasonal oscillations and persistent heavy rainfall in South China - Jianyun Gao; Hai Lin; Lijun You; Si Chen (Climate Dynamics, 2016)

Characterization of nanocellulose recovery from Elaeis guineensis frond for sustainable development - Muhammad Safwan Mohaiyiddin; Ong Hui Lin; Wei Tieng Owi; Chi Hoong Chan; Chin Hua Chia; Sarani Zakaria; Al Rey Villagracia; Hazizan Md Akil (Clean Technologies and Environmental Policy, 2016)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Pik Fang Kho; Jonathan Fawcett; Lin Fritschi; Harvey Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2016)

High-Dose Fluoride Induces Apoptosis and Inhibits Ameloblastin Secretion in Primary Rat Ameloblast - Lin Wang; Yong Zhu; Danyang Wang (Biological Trace Element Research, 2016)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Ten polymorphic microsatellite markers characterized for Schizothorax pseudaksaiensis and applied for population genetic analysis - MING MING BAO; QIONG ZHOU; CONG XIN XIE; LIN GANG CAI; JIAN GONG NIU; HONG LI (Journal of Genetics, 2016)

HSR mechanisms and effects on the spatial structure of regional tourism in China - Degen Wang; Li Wang; Tian Chen; Lin Lu; Yu Niu; August Lew Alan (Journal of Geographical Sciences, 2016)

Analysis of chemical characteristics of PM2.5 in Beijing over a 1-year period - Zhanshan Wang; Dawei Zhang; Baoxian Liu; Yunting Li; Tian Chen; Feng Sun; Dongyan Yang; Yunping Liang; Miao Chang; Liu Yang; Anguo Lin (Journal of Atmospheric Chemistry, 2016)

Identification of a nuclear-recessive gene locus for male sterility on A2 chromosome using the Brassica 60 K SNP array in non-heading Chinese cabbage - Xia Li; Aihua Wang; Feng Zu; Zhenhua Hu; Jiazao Lin; Guolin Zhou; Jinxing Tu (Genes & Genomics, 2016)

Deformation geometry and timing of theWupoer thrust belt in the NE Pamir and its tectonic implications - Xiaogan Cheng; Hanlin Chen; Xiubin Lin; Shufeng Yang; Shenqiang Chen; Fenfen Zhang; Kang Li; Zelin Liu (Frontiers of Earth Science, 2016)

Dynamic soil-tunnel interaction in layered half-space for incident plane SH waves - Jia Fu; Jianwen Liang; Lin Qin (Earthquake Engineering and Engineering Vibration, 2016)

Development of chloroplast genomic resources for Akebia quinata (Lardizabalaceae) - Bin Li; Yanda Li; Qifei Cai; Furong Lin; Ping Huang; Yongqi Zheng (Conservation Genetics Resources, 2016)

Complete chloroplast genome sequences of Rehmannia chingii, an endemic and endangered herb - Shuyun Zeng; Jianhua Zhao; Kai Han; Zhan-Lin Liu (Conservation Genetics Resources, 2016)

The complete chloroplast genome sequence of Pinus dabeshanensis - Ren-Yan Duan; Li-Min Yang; Tong Lv; Gan-Lin Wu; Min-Yi Huang (Conservation Genetics Resources, 2016)

Short Peptides Regulate Gene Expression - V. Kh. Khavinson; N. S. Lin’kova; S. I. Tarnovskaya (Bulletin of Experimental Biology and Medicine, 2016)

Long noncoding RNAs in cell differentiation and pluripotency - Lin Chen; Sheng Zhang (Cell and Tissue Research, 2016)

Urban metabolic efficiencies and elasticities of Chinese cities - Tao Song; Jianming Cai; Zhenshan Yang; Mingxing Chen; Jing Lin (Chinese Geographical Science, 2016)

Repeated damage by specialist insects suppresses the growth of a high tolerance invasive tree - Yi Wang; Lin Zhu; Evan Siemann; Jianqing Ding (BioControl, 2016)

A Validation Study of Adiponectin rs266729 Gene Variant with Type 2 Diabetes, Obesity, and Metabolic Phenotypes in a Taiwanese Population - Tun-Jen Hsiao; Eugene Lin (Biochemical Genetics, 2016)

Halorussus salinus sp. nov., isolated from a marine solar saltern - Jia-Qi Xu; Wen-Mei Xu; Yang Li; Yao Zhou; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Archives of Microbiology, 2016)

Equisetum cf. oppositum (Equisetaceae) from the Paleocene-Eocene of Tibet in southwestern China and its paleoenvironmental implications - Guo-Lin Yang; Zi-Xi Wang; Jing-Wei Chen; De-Fei Yan; Bai-Nian Sun (Arabian Journal of Geosciences, 2016)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

Multiple-factor classification of a human-modified forest landscape in the Hsuehshan Mountain Range, Taiwan - Kevan J. Berg; Lahuy Icyeh; Yih-Ren Lin; Arnold Janz; Steven G. Newmaster (Ambio, 2016)

Genome-wide transcriptional response of the Arctic bacterium Pseudoalteromonas sp. A2 to oxidative stress induced by hydrogen peroxide - Xuezheng Lin; Zhen Wang; Yang Li; Jiang Li (Acta Oceanologica Sinica, 2016)

Object-based image analysis for mapping geomorphic zones of coral reefs in the Xisha Islands, China - Jingping Xu; Jianhua Zhao; Fang Li; Lin Wang; Derui Song; Shiyong Wen; Fei Wang; Ning Gao (Acta Oceanologica Sinica, 2016)

The genetic relationship between Habo alkaline intrusion and its surrounding deposits, Yunnan Province, China: geological and S–Pb isotopic evidences - Zhongneng Meng; Qian Zhang; Lin Ye; Yupin Liu; Jiangbo Lan; Dapeng Wang (Acta Geochimica, 2016)

Distribution, fractionation, and contamination assessment of heavy metals in offshore surface sediments from western Xiamen Bay, China - Qiuli Yang; Gongren Hu; Ruilian Yu; Haixing He; Chengqi Lin (Acta Geochimica, 2016)

Dual‐compartmental transcriptomic + proteomic analysis of a marine endosymbiosis exposed to environmental change - Anderson B. Mayfield; Yu‐Bin Wang; Chii‐Shiarng Chen; Shu‐Hwa Chen; Chung‐Yen Lin (Molecular Ecology, 2016)
As significant anthropogenic pressures are putting undue stress on the world's oceans, there has been a concerted effort to understand how marine organisms respond to environmental change. Transcriptomic approaches, in particular, have been readily employed to document the m RNA ‐level response of a plethora of marine invertebrates exposed to an array of simulated stress scenarios, with the tacit and untested assumption being that the respective proteins show a corresponding trend. To better understand the degree of congruency between m RNA and protein expression in an endosymbiotic marine invertebrate, m RNA s and proteins were sequenced from the same samples of the common, Indo‐Pacific coral Seriatopora hystrix exposed to stable or upwelling‐simulating conditions for 1 week. Of the 167 proteins downregulated at variable temperature, only two were associated with m RNA s that were also differentially expressed between treatments. Of the 378 differentially expressed genes, none were associated with a differentially expressed protein. Collectively, these results highlight the inherent risk of inferring cellular behaviour based on m RNA expression data alone and challenge the current, m RNA ‐focused approach taken by most marine and many molecular biologists.

Identification of Vibrio parahaemolyticus in Seafood by Multiplex PCR - Chung-Saint Lin; Tser-Sheng Lin; Din-Yuan Yu; Yi-Cheng Su; Yung-Hsiang Tsai (Journal of Aquatic Food Product Technology, 2016)

Moisture Adsorption Isotherms and Thermodynamic Properties of Penaeus vannamei Meat with and without Maltodextrin Addition - Qilong Shi; Wenwen Lin; Ya Zhao; Pingping Zhang; Ruiying Wang (Journal of Aquatic Food Product Technology, 2016)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Secondary metabolites of Xylaria sp., an endophytic fungus from Taxus mairei - Xiao Lin; Miao Yu; Ting Lin; Lianru Zhang (Natural Product Research, 2016)

Dependency of the Sentinel-1 azimuth wavelength cut-off on significant wave height and wind speed - G. Grieco; W. Lin; M. Migliaccio; F. Nirchio; M. Portabella (International Journal of Remote Sensing, 2016)

Identification of a new sildenafil analogue adulterant, desethylcarbodenafil, in a herbal supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Ya-Tze Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Influence of Florfenicol on the Treatment Effect of Intermittent Aeration Dynamic Membrane Bioreactors, and its Enhanced Removal Process Investigation - Xiang Wu; Hao Wu; Lin Mao; Lan Yu; Rongfei Zhang; Jinyun Ye (Water, Air, & Soil Pollution, 2016)

Comparison of Kinetics of Arsenic(V) Adsorption on Two Types of Red Soil Weathered from Granite and Sandstone - Hongwei Chen; Lin Liu; Rouyan Gong; Runchu Wei; Qiaohui Yi; Anni Qiu (Water, Air, & Soil Pollution, 2016)

Considering the Order and Symmetry to Improve the Traditional RVA for Evaluation of Hydrologic Alteration of River Systems - Kairong Lin; Youqin Lin; Pan Liu; Yanhu He; Xinjun Tu (Water Resources Management, 2016)

Modeling daily reference ET in the karst area of northwest Guangxi (China) using gene expression programming (GEP) and artificial neural network (ANN) - Sheng Wang; Zhi-yong Fu; Hong-song Chen; Yun-peng Nie; Ke-lin Wang (Theoretical and Applied Climatology, 2016)

Differential surface uplift: Cenozoic paleoelevation history of the Tibetan Plateau - XiaoHui Liu; Qiang Xu; Lin Ding (Science China Earth Sciences, 2016)

NanoSIMS imaging method of zircon U-Pb dating - Sen Hu; YangTing Lin; Wei Yang; Wei-RZ Wang; JianChao Zhang; JiaLong Hao; WeiFan Xing (Science China Earth Sciences, 2016)

Strength, Deformability and X-ray Micro-CT Observations of Deeply Buried Marble Under Different Confining Pressures - Sheng-Qi Yang; Yang Ju; Feng Gao; Yi-Lin Gui (Rock Mechanics and Rock Engineering, 2016)

Microseismic Precursory Characteristics of Rock Burst Hazard in Mining Areas Near a Large Residual Coal Pillar: A Case Study from Xuzhuang Coal Mine, Xuzhou, China - An-ye Cao; Lin-ming Dou; Chang-bin Wang; Xiao-xiao Yao; Jing-yuan Dong; Yu Gu (Rock Mechanics and Rock Engineering, 2016)

An Experimental and Numerical Study on Mechanical Behavior of Ubiquitous-Joint Brittle Rock-Like Specimens Under Uniaxial Compression - Ri-hong Cao; Ping Cao; Xiang Fan; Xinguang Xiong; Hang Lin (Rock Mechanics and Rock Engineering, 2016)

Erratum to: Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Local-scale determinants of elemental stoichiometry of soil in an old-growth temperate forest - Yanyan Suo; Zuoqiang Yuan; Fei Lin; Xugao Wang; Ji Ye; Edith Bai; Zhanqing Hao (Plant and Soil, 2016)

Responses of rice to chronic and acute iron toxicity: genotypic differences and biofortification aspects - Michael Frei; Richmond Narh Tetteh; Ando Lalaina Razafindrazaka; Michael Apolonius Fuh; Lin-Bo Wu; Mathias Becker (Plant and Soil, 2016)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Wheat bHLH-type transcription factor gene TabHLH1 is crucial in mediating osmotic stresses tolerance through modulating largely the ABA-associated pathway - Tongren Yang; Sufei Yao; Lin Hao; Yuanyuan Zhao; Wenjing Lu; Kai Xiao (Plant Cell Reports, 2016)

Tetrasomic inheritance pattern of the pentaploid Solanum chacoense (+) S. tuberosum somatic hybrid (resistant to bacterial wilt) revealed by SSR detected alleles - Lin Chen; Xianpu Guo; Haibo Wang; Conghua Xie; Xingkui Cai; Li He; Jun Zhou; Jun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Functional composition drives ecosystem function through multiple mechanisms in a broadleaved subtropical forest - Jyh-Min Chiang; Marko J. Spasojevic; Helene C. Muller-Landau; I-Fang Sun; Yiching Lin; Sheng-Hsin Su; Zueng-Sang Chen; Chien-Teh Chen; Nathan G. Swenson; Ryan W. McEwan (Oecologia, 2016)

Types of water hazards in China coalmines and regional characteristics - Herong Gui; Manli Lin (Natural Hazards, 2016)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Chromogenic media for MRSA diagnostics - Zhenbo Xu; Yuchao Hou; Brian M. Peters; Dingqiang Chen; Bing Li; Lin Li; Mark E. Shirtliff (Molecular Biology Reports, 2016)

Erratum to: Evaluation of Anti-Inflammatory Effects of Helminthostachys zeylanica Extracts via Inhibiting Bradykinin-Induced MMP-9 Expression in Brain Astrocytes - Chuen-Mao Yang; Sien-Hung Yang; Tsong-Hai Lee; Jia-You Fang; Chwan-Fwu Lin; Mei-Jie Jou; Hsi-Lung Hsieh (Molecular Neurobiology, 2016)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Tripchlorolide Attenuates β-amyloid Generation via Suppressing PPARγ-Regulated BACE1 Activity in N2a/APP695 Cells - Nan Lin; Li-min Chen; Xiao-dong Pan; Yuan-gui Zhu; Jing Zhang; Yan-qing Shi; Xiao-chun Chen (Molecular Neurobiology, 2016)

MicroRNA124 Regulated Neurite Elongation by Targeting OSBP - Xi Gu; Aili Li; Shuhu Liu; Lifang Lin; Shuang Xu; Peidong Zhang; Shuji Li; Xiaowen Li; Bo Tian; Xinhong Zhu; Xuemin Wang (Molecular Neurobiology, 2016)

Interlukin-18 Is a Pivot Regulatory Factor on Matrix Metalloproteinase-13 Expression and Brain Astrocytic Migration - Jia-Hong Chen; Chon-Haw Tsai; Hsiao-Yun Lin; Chien-Fang Huang; Yuk-Man Leung; Sheng-Wei Lai; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2016)

Evaluation of Anti-Inflammatory Effects of Helminthostachys zeylanica Extracts via Inhibiting Bradykinin-Induced MMP-9 Expression in Brain Astrocytes - Hsi-Lung Hsieh; Sien-Hung Yang; Tsong-Hai Lee; Jia-You Fang; Chwan-Fwu Lin (Molecular Neurobiology, 2016)

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade - Chien-Chung Yang; Chih-Chung Lin; Peter Tzu-Yu Chien; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2016)

Synthesis and antifungal activity of dehydroabietic acid-based 1,3,4-thiadiazole-thiazolidinone compounds - Naiyuan Chen; Wengui Duan; Guishan Lin; Luzhi Liu; Rui Zhang; Dianpeng Li (Molecular Diversity, 2016)

Ubiquitin-specific protease 39 is overexpressed in human lung cancer and promotes tumor cell proliferation in vitro - Zhifeng Lin; Liwen Xiong; Qiang Lin (Molecular and Cellular Biochemistry, 2016)

Prey selection and foraging behavior of the whelk Rapana venosa - Nan Hu; Fang Wang; Tao Zhang; Hao Song; Zheng-Lin Yu; Da-Peng Liu (Marine Biology, 2016)

Low humic acids promote in vitro lily bulblet enlargement by enhancing roots growth and carbohydrate metabolism - Yun Wu; Yi-ping Xia; Jia-ping Zhang; Fang Du; Lin Zhang; Yi-di Ma; Hong Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

In vitro remineralization of hybrid layers using biomimetic analogs - Hui-ping Lin; Jun Lin; Juan Li; Jing-hong Xu; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2016)

Fungal spondylodiscitis in a patient recovered from H7N9 virus infection: a case study and a literature review of the differences between Candida and Aspergillus spondylodiscitis - Lie-dao Yu; Zhi-yun Feng; Xuan-wei Wang; Zhi-heng Ling; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

FUS-linked essential tremor associated with motor dysfunction in Drosophila - Murni Tio; Rujing Wen; Yih Lin Lim; Huashan Wang; Shuo-Chien Ling; Yi Zhao; Eng-King Tan (Human Genetics, 2016)

Population structure and association analysis of yield and grain quality traits in hybrid rice primal parental lines - Yingheng Wang; Yanmei Zheng; Qiuhua Cai; Changjian Liao; Xiaohui Mao; Hongguang Xie; Yongsheng Zhu; Lin Lian; Xi Luo; Huaan Xie; Jianfu Zhang (Euphytica, 2016)
To make advances in rice molecular design breeding, it is important to understand the genetic background and phenotypes of the parental lines, to known superior allele of the breeding material. In this study, 34 pairs of insertion-deletion (InDel) markers were used to analyze the differentiation of indica – japonica properties in 277 primal parental lines of hybrid rice that are used in China and abroad. The genetic diversity and population structure were assessed with simple sequence repeat (SSR) markers. We also evaluated the association between SSR markers and seven yield traits and four grain-quality traits of 256 indica rice lines. The main results are as follows. (1) Within the 277 lines there were two subgroups: indica and japonica . The 256 lines of the indica -subgroup were further divided into four sub–sub-groups: landrace, maintainer, restorer, and rice lines from the International Rice Research Institute. (2) We identified 29 loci associated with 11 agronomic traits, including one for plant height, two for tiller number, one for panicle length, three for grain length, eight for grain width, eight for grain length/width ratio, one for thousand grain weight, one for amylose content, two for gel consistency, one for gelatinization temperature and one for total protein content. (3) Among those loci, 16 markers were closely linked to previously identified genes. Superior allele carrier lines and allele effects were also analyzed. Our results provided the population structure and indica – japonica properties for parent matching, and the marker–trait association will also be useful for molecular design breeding.

Co-exposure to amorphous silica nanoparticles and benzo[a]pyrene at low level in human bronchial epithelial BEAS-2B cells - Jing Wu; Yanfeng Shi; Collins Otieno Asweto; Lin Feng; Xiaozhe Yang; Yannan Zhang; Hejing Hu; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2016)

Effects of doping amounts of potassium ferricyanide with titanium dioxide and calcination durations on visible-light degradation of pharmaceuticals - Justin Chun-Te Lin; Mark Daniel G. de Luna; Mary Jane N. Gotostos; Ming-Chun Lu (Environmental Science and Pollution Research, 2016)

Catalytic reduction of hexavalent chromium by a novel nitrogen-functionalized magnetic ordered mesoporous carbon doped with Pd nanoparticles - Sisi Li; Lin Tang; Guangming Zeng; Jiajia Wang; Yaocheng Deng; Jingjing Wang; Zhihong Xie; Yaoyu Zhou (Environmental Science and Pollution Research, 2016)

Characterization of the spatial variability of soil available zinc at various sampling densities using grouped soil type information - Xiao-Dong Song; Gan-Lin Zhang; Feng Liu; De-Cheng Li; Yu-Guo Zhao (Environmental Monitoring and Assessment, 2016)

Green and sustainable remediation (GSR) evaluation: framework, standards, and tool. A case study in Taiwan - Wen-Yen Huang; Weiteng Hung; Chi Thanh Vu; Wei-Ting Chen; Jhih-Wei Lai; Chitsan Lin (Environmental Science and Pollution Research, 2016)

Highway increases concentrations of toxic metals in giant panda habitat - Ying-juan Zheng; Yi-ping Chen; Lorraine Maltby; Xue-lin Jin (Environmental Science and Pollution Research, 2016)

Optimal Subdivision for Treatment and Management of Catastrophic Landslides in a Watershed Using Topographic Factors - Chao-Yuan Lin; Kuei-Lin Fu; Cheng-Yu Lin (Environmental Management, 2016)

Diagnosing the possible dynamics controlling Sahel precipitation in the short-range ensemble community atmospheric model hindcasts - Yu-heng Tseng; Yen-heng Lin; Min-hui Lo; Shu-chih Yang (Climate Dynamics, 2016)

The effect of future reduction in aerosol emissions on climate extremes in China - Zhili Wang; Lei Lin; Meilin Yang; Yangyang Xu (Climate Dynamics, 2016)

Influence of Three Citrus Herbicides on Potential Production of Sorghum bicolor ‘Topper 76-6’ as a Bioenergy Crop - Patrick C. Wilson; Barrett Gruber; Youjian Lin; Prem Kumar; David Niebch; Sandra Wilson (Bulletin of Environmental Contamination and Toxicology, 2016)

A three-dimensional rigorous method for stability analysis and its application - Kun Lin Lu; Da Yong Zhu (Bulletin of Engineering Geology and the Environment, 2016)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)

Alleviation of Lead-Induced Apoptosis by Puerarin via Inhibiting Mitochondrial Permeability Transition Pore Opening in Primary Cultures of Rat Proximal Tubular Cells - Zhong-Kun Wang; Xue-Lei Zhou; Xiang-Bin Song; Dong-Ming Zhuang; Zhen-Yong Wang; Du-Bao Yang; Lin Wang (Biological Trace Element Research, 2016)

Increasing phosphorus concentration in the extraradical hyphae of Rhizophagus irregularis DAOM 197198 leads to a concomitant increase in metal minerals - Lin Zhang; Caiyun Jiang; Jiachao Zhou; Stéphane Declerck; Changyan Tian; Gu Feng (Mycorrhiza, 2016)

A WD40 protein, AtGHS40, negatively modulates abscisic acid degrading and signaling genes during seedling growth under high glucose conditions - Yu-Chun Hsiao; Yi-Feng Hsu; Yun-Chu Chen; Yi-Lin Chang; Co-Shine Wang (Journal of Plant Research, 2016)

Mineral constituents of a prized edible mushroom (Tricholoma matsutake) and soils beneath the fruiting bodies from the production areas across China - Qiang Li; Shu-hong Li; Wen-li Huang; Cheng-yi Liu; Chuan Xiong; Xiao-lin Li; Lin-yong Zheng (Journal of Mountain Science, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Spatiotemporal evolution of urban air quality and socioeconomic driving forces in China - Xueqin Lin; Dai Wang (Journal of Geographical Sciences, 2016)

One-step reverse transcription loop-mediated isothermal amplification for the detection of Capsicum chlorosis virus in Phalaenopsis orchids - Cheng-Ping Kuan; Yu-Fei Lin; Yu-Chun Lin; Chin-Chih Chen (Journal of General Plant Pathology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Regulation of fibronectin gene expression in cardiac fibroblasts by scleraxis - Rushita A. Bagchi; Justin Lin; Ryan Wang; Michael P. Czubryt (Cell and Tissue Research, 2016)

Complex mammal species responses to fire in a native tropical savannah invaded by non-native grader grass (Themeda quadrivalvis) - Rickard Abom; Scott A. Parsons; Lin Schwarzkopf (Biological Invasions, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Efficacy and safety of interferon-α2b spray in the treatment of hand, foot, and mouth disease: a multicenter, randomized, double-blind trial - Hailong Lin; Leting Huang; Jian Zhou; Kaichun Lin; Hongjiao Wang; Xia Xue; Chan Xia (Archives of Virology, 2016)

Dynamic patterns of circulating influenza virus from 2005 to 2012 in Shandong Province, China - Ti Liu; Zhong Li; Yi Lin; Shaoxia Song; Shengyang Zhang; Lin Sun; Yulu Wang; Aiqiang Xu; Zhenqiang Bi; Xianjun Wang (Archives of Virology, 2016)

Molecular epidemiology of J-subgroup avian leukosis virus isolated from meat-type chickens in southern China between 2013 and 2014 - Wencheng Lin; Xinjian Li; Zhenkai Dai; Xinheng Zhang; Shuang Chang; Peng Zhao; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

The Rab1 in host cells modulates Brucella intracellular survival and binds to Brucella DnaK protein - Ning Liu; Changjiang Sun; Guimei Cui; Pan Wei; Li Yang; Wanchun Sun; Shuangxi Wang; Lin Wang; Qisheng Peng (Archives of Microbiology, 2016)

Proteomic analysis of Mortierella isabellina M6-22 during cold stress - Binbin Hu; Minzhou Luo; Xiuling Ji; Lianbing Lin; Yunlin Wei; Qi Zhang (Archives of Microbiology, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Ground-based radar reflectivity mosaic of mei-yu precipitation systems over the Yangtze River–Huaihe River basins - Yali Luo; Weimiao Qian; Yu Gong; Hongyan Wang; Da-Lin Zhang (Advances in Atmospheric Sciences, 2016)

The distribution and inter-annual variation of water masses on the Bering Sea shelf in summer - Na Liu; Lina Lin; Yingjie Wang; Hongxia Chen; Yan He (Acta Oceanologica Sinica, 2016)

Plant adaptation or acclimation to rising CO 2 ? Insight from first multigenerational RNA‐Seq transcriptome - Alexander Watson‐Lazowski; Yunan Lin; Franco Miglietta; Richard J. Edwards; Mark A. Chapman; Gail Taylor (Global Change Biology, 2016)
Atmospheric carbon dioxide ( CO 2 ) directly determines the rate of plant photosynthesis and indirectly effects plant productivity and fitness and may therefore act as a selective pressure driving evolution, but evidence to support this contention is sparse. Using Plantago lanceolata L. seed collected from a naturally high CO 2 spring and adjacent ambient CO 2 control site, we investigated multigenerational response to future, elevated atmospheric CO 2 . Plants were grown in either ambient or elevated CO 2 (700 μmol mol −1 ), enabling for the first time, characterization of the functional and population genomics of plant acclimation and adaptation to elevated CO 2 . This revealed that spring and control plants differed significantly in phenotypic plasticity for traits underpinning fitness including above‐ground biomass, leaf size, epidermal cell size and number and stomatal density and index. Gene expression responses to elevated CO 2 (acclimation) were modest [33–131 genes differentially expressed ( DE )], whilst those between control and spring plants (adaptation) were considerably larger (689–853 DE genes). In contrast, population genomic analysis showed that genetic differentiation between spring and control plants was close to zero, with no fixed differences, suggesting that plants are adapted to their native CO 2 environment at the level of gene expression. An unusual phenotype of increased stomatal index in spring but not control plants in elevated CO 2 correlated with altered expression of stomatal patterning genes between spring and control plants for three loci ( YODA , CDKB 1;1 and SCRM 2 ) and between ambient and elevated CO 2 for four loci ( ER , YODA , MYB 88 and BCA 1 ). We propose that the two positive regulators of stomatal number ( SCRM 2 ) and CDKB 1;1 when upregulated act as key controllers of stomatal adaptation to elevated CO 2 . Combined with significant transcriptome reprogramming of photosynthetic and dark respiration and enhanced growth in spring plants, we have identified the potential basis of plant adaptation to high CO 2 likely to occur over coming decades.

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Differential foraging preferences on seed size by rodents result in higher dispersal success of medium‐sized seeds - Lin Cao; Zhenyu Wang; Chuan Yan; Jin Chen; Cong Guo; Zhibin Zhang (Ecology, 2016)
Rodent preference for scatter‐hoarding large seeds has been widely considered to favor the evolution of large seeds. Previous studies supporting this conclusion were primarily based on observations at earlier stages of seed dispersal, or on a limited sample of successfully established seedlings. Because seed dispersal comprises multiple dispersal stages, we hypothesized that differential foraging preference on seed size by animal dispersers at different dispersal stages would ultimately result in medium‐sized seeds having the highest dispersal success rates. In this study, by tracking a large number of seeds for 5 yr, we investigated the effects of seed size on seed fates from seed removal to seedling establishment of a dominant plant Pittosporopsis kerrii (Icacinaceae) dispersed by scatter‐hoarding rodents in tropical forest in southwest China. We found that small seeds had a lower survival rate at the early dispersal stage where more small seeds were predated at seed stations and after removal; large seeds had a lower survival rate at the late dispersal stage, more large seeds were recovered, predated after being cached, or larder‐hoarded. Medium‐sized seeds experienced the highest dispersal success. Our study suggests that differential foraging preferences by scatter‐hoarding rodents at different stages of seed dispersal could result in conflicting selective pressures on seed size and higher dispersal success of medium‐sized seeds.

Catastrophic outburst and tsunami flooding of Lake Baikal: U–Pb detrital zircon provenance study of the Palaeo-Manzurka megaflood sediments - Alexei V. Ivanov; Elena I. Demonterova; Leonid Z. Reznitskii; Igor G. Barash; Sergey G. Arzhannikov; Anastasia V. Arzhannikova; Chan-Hui Hung; Sun-Lin Chung; Yoshiyuki Iizuka (International Geology Review, 2016)

Exploring the Mechanism of Surface and Ground Water through Data-Driven Techniques with Sensitivity Analysis for Water Resources Management - Wen-Ping Tsai; Yen-Ming Chiang; Jun-Lin Huang; Fi-John Chang (Water Resources Management, 2016)

Characteristics of soil CO2 efflux under an invasive species, Moso bamboo, in forests of central Taiwan - I-Fang Hsieh; Tomonori Kume; Meng-Ying Lin; Chih-Hsin Cheng; Takeshi Miki (Trees, 2016)

Transcriptome analysis of the male-to-hermaphrodite sex reversal induced by low temperature in papaya - Hai Lin; Zhenyang Liao; Lingmao Zhang; Qingyi Yu (Tree Genetics & Genomes, 2016)

Variation in nesting behavior of eight species of spider mites, Stigmaeopsis having sociality - Yutaka Saito; Yan-Xuan Zhang; Kotaro Mori; Katsura Ito; Yukie Sato; Anthony R. Chittenden; Jian-Zhen Lin; Younghae Chae; Takane Sakagami; Ken Sahara (The Science of Nature, 2016)

Surgical treatment of hepato-pancreato-biliary disease in China: the Tongji experience - Binhao Zhang; Wei Dong; Hongping Luo; Xuanru Zhu; Lin Chen; Changhai Li; Peng Zhu; Wei Zhang; Shuai Xiang; Wanguang Zhang; Zhiyong Huang; Xiao-Ping Chen (Science China Life Sciences, 2016)

Dynamic Fracture Properties of Rocks Subjected to Static Pre-load Using Notched Semi-circular Bend Method - Rong Chen; Kang Li; Kaiwen Xia; Yuliang Lin; Wei Yao; Fangyun Lu (Rock Mechanics and Rock Engineering, 2016)

Unilateral hippocampal inactivation or lesion selectively impairs remote contextual fear memory - Heng Zhou; Qixin Zhou; Lin Xu (Psychopharmacology, 2016)

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; James P. Keener; Robert Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2016)

Modulation of Nav1.8 by Lysophosphatidic Acid in the Induction of Bone Cancer Pain - Hai-Li Pan; Ben-Long Liu; Wei Lin; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Synthesis and evaluation as potential antitumor agents of novel ursolic acid derivatives - Ming-Chuan Liu; Sheng-Jie Yang; Lin-Hong Jin; De-Yu Hu; Wei Xue; Song Yang (Medicinal Chemistry Research, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Dissipation of fomesafen in biochar-amended soil and its availability to corn (Zea mays L.) and earthworm (Eisenia fetida) - Mahdi Safaei Khorram; Yuan Zheng; Dunli Lin; Qian Zhang; Hua Fang; Yunlong Yu (Journal of Soils and Sediments, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

First report of the melon stem rot disease in protected cultivation caused by Pseudomonas fluorescens - Chenghua Zhang; Tao Lin; Jufen Li; Guobin Ma; Yiwen Wang; Pinkuan Zhu; Ling Xu (Journal of Plant Diseases and Protection, 2016)

Paleohydrological processes revealed by n-alkane δD in lacustrine sediments of Lake Pumoyum Co, southern Tibetan Plateau, and their response to climate changes during the past 18.5 cal ka - Yong Wang; Liping Zhu; Junbo Wang; Jianting Ju; Ping Peng; Xiao Lin; Jianfang Hu; Mitsugu Nishimura (Journal of Paleolimnology, 2016)

An n-alkane and carbon isotope record during the last deglaciation from annually laminated sediment in Lake Xiaolongwan, northeastern China - Qing Sun; Manman Xie; Yuan Lin; Yabing Shan; Qingzeng Zhu; Deke Xu; Youliang Su; Patrick Rioual; Guoqiang Chu (Journal of Paleolimnology, 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

The potential of the brown seaweed Sargassum polycystum against acne vulgaris - Jamie Mei-Lin Kok; Jap-Meng Jee; Lye-Yee Chew; Ching-Lee Wong (Journal of Applied Phycology, 2016)

Utilization of gaseous emissions from a methanol plant for cultivation of Acutodesmus obliquus - Lin Chen; Xiaomei Li; Mingzi Wang; Jian Huang; Bilian Chen; Xinglong Li; Xing Zheng (Journal of Applied Phycology, 2016)

A longitudinal study on urinary cadmium and renal tubular protein excretion of nickel–cadmium battery workers after cessation of cadmium exposure - Yanhua Gao; Yanfang Zhang; Juan Yi; Jinpeng Zhou; Xianqing Huang; Xinshan Shi; Shunhua Xiao; Dafeng Lin (International Archives of Occupational and Environmental Health, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

Biological characterization of bovine mammary epithelial cell lines immortalized by HPV16 E6/E7 and SV40T - Kang Zhan; Miao Lin; Qian-Ming Zhao; Jin-Shun Zhan; Guo-Qi Zhao (In Vitro Cellular & Developmental Biology - Animal, 2016)

Aneuploid progenies of triploid hybrids between diploid and tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Zhong-Qiao Lin; Tian-Yu Ma; Yi Sui; Katsutoshi Arai (Genetica, 2016)

Effects of β-glucan on ROS production and energy metabolism in yellow croaker (Pseudosciaena crocea) under acute hypoxic stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Jia-Lang Zheng; Chang-Wen Wu; Rong Cai (Fish Physiology and Biochemistry, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Simultaneous determination of estrogenic odorant alkylphenols, chlorophenols, and their derivatives in water using online headspace solid phase microextraction coupled with gas chromatography-mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-Xian Lian; Chuangtao Yang; Qing Lin; Hua Yin; Zhi Dang (Environmental Science and Pollution Research, 2016)

Crystal Violet and XTT Assays on Staphylococcus aureus Biofilm Quantification - Zhenbo Xu; Yanrui Liang; Shiqi Lin; Dingqiang Chen; Bing Li; Lin Li; Yang Deng (Current Microbiology, 2016)

Limited diversity associated with duplicated class II MHC-DRB genes in the red squirrel population in the United Kingdom compared with continental Europe - Keith T. Ballingall; Angeline McIntyre; Zhenzhen Lin; Naomi Timmerman; Erik Matthysen; Peter W.W. Lurz; Lynsey Melville; Amy Wallace; Anna L. Meredith; Claudia Romeo; Lucas A. Wauters; Anthony W. Sainsbury; et al. (Conservation Genetics, 2016)

Improved ENSO simulation from climate system model FGOALS-g1.0 to FGOALS-g2 - Lin Chen; Yongqiang Yu; Weipeng Zheng (Climate Dynamics, 2016)

The interdecadal change of the leading mode of the winter precipitation over China - Jingwen Ge; Xiaojing Jia; Hai Lin (Climate Dynamics, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

A prognostic model for advanced colorectal neoplasia recurrence - Lin Liu; Karen Messer; John A. Baron; David A. Lieberman; Elizabeth T. Jacobs; Amanda J. Cross; Gwen Murphy; Maria Elena Martinez; Samir Gupta (Cancer Causes & Control, 2016)

RETRACTED ARTICLE: TP53INP1 3′-UTR functions as a ceRNA in repressing the metastasis of glioma cells by regulating miRNA activity - Yi Wang; Guihua Lin (Biotechnology Letters, 2016)

Bis(maltolato)oxovanadium(IV) (BMOV) Attenuates Apoptosis in High Glucose-Treated Cardiac Cells and Diabetic Rat Hearts by Regulating the Unfolded Protein Responses (UPRs) - Xiao-Qiang Cong; Mei-Hua Piao; Ying Li; Lin Xie; Ya Liu (Biological Trace Element Research, 2016)

Effects of Replacing of Inorganic Trace Minerals by Organically Bound Trace Minerals on Growth Performance, Tissue Mineral Status, and Fecal Mineral Excretion in Commercial Grower-Finisher Pigs - Bing Liu; Pingwen Xiong; Nana Chen; Junna He; Gang Lin; Yan Xue; Weifen Li; Dongyou Yu (Biological Trace Element Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Proteasomes regulate hepatitis B virus replication by degradation of viral core-related proteins in a two-step manner - Zi-Hua Zheng; Hui-Ying Yang; Lin Gu; Xiao-Mou Peng (Virus Genes, 2016)

Kin-biased conspecific brood parasitism in a native Mandarin duck population - Ye Gong; Rebecca T. Kimball; Colette St. Mary; Xiang Cui; Lin Wang; Yunlei Jiang; Haitao Wang (Journal of Ornithology, 2016)

Chemical mechanism of flocculation and deposition of clay colloids in coastal aquifers - Jun Zhou; Lixia Qiu; Guoqing Lin; Xiaoyun Yan; Xiaolan Chen; Honglu Pang (Journal of Ocean University of China, 2016)

Distribution of soil carbon in different grassland types of the Qinghai-Tibetan Plateau - Shu-li Liu; Yan-gong Du; Fa-wei Zhang; Li Lin; Yi-kang Li; Xiao-wei Guo; Qian Li; Guang-min Cao (Journal of Mountain Science, 2016)

Analyzing land use characteristics of rural settlements on the urban fringe of Liangjiang New Area, Chongqing, China - Yi Wang; Guo-hua Bi; Qing-yuan Yang; Zhao-lin Wang (Journal of Mountain Science, 2016)

Sialylation and desialylation dynamics of monocytes upon differentiation and polarization to macrophages - Dan Wang; Evgeny Ozhegov; Lin Wang; Aimin Zhou; Huan Nie; Yu Li; Xue-Long Sun (Glycoconjugate Journal, 2016)

Modeling and verifying the impact of time delay on INS-aided GNSS PLLs - Tisheng Zhang; Hongping Zhang; Tao Lin; Kunlun Yan; Xiaoji Niu (GPS Solutions, 2016)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

Behavioural response of the greater horseshoe bat to geographical variation in echolocation calls - Aiqing Lin; Heng Liu; Yang Chang; Guanjun Lu; Jiang Feng (Behavioral Ecology and Sociobiology, 2016)

Isolation, identification and evolution analysis of a novel subgroup of avian leukosis virus isolated from a local Chinese yellow broiler in South China - Xinjian Li; Wencheng Lin; Shuang Chang; Peng Zhao; Xinheng Zhang; Yang Liu; Weiguo Chen; Baohong Li; Dingming Shu; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

The Vibrio parahaemolyticus-infecting bacteriophage qdvp001: genome sequence and endolysin with a modular structure - Weiyu Wang; Mengzhe Li; Hong Lin; Jingxue Wang; Xiangzhao Mao (Archives of Virology, 2016)

Assessment of the seasonal variation of simulated Wyrtki jet over the tropical Indian Ocean in CMIP5 models - Lin Liu; Baochao Liu; Guoqing Han; Lin Feng; Xinfang Li; Weidong Yu (Arabian Journal of Geosciences, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Effects of probiotics on soil microbial activity, biomass and enzymatic activity under cover crops in field and greenhouse studies - Ahsan M. Rajper; Ranjith P. Udawatta; Robert J. Kremer; Chung-ho Lin; Shibu Jose (Agroforestry Systems, 2016)

Removal of Random Noise in Seismic Data by Time-varying Window-length Time-frequency Peak Filtering - Pengjun Yu; Yue Li; Hongbo Lin; Ning Wu (Acta Geophysica, 2016)

Litter quality mediated nitrogen effect on plant litter decomposition regardless of soil fauna presence - Weidong Zhang; Lin Chao; Qingpeng Yang; Qingkui Wang; Yunting Fang; Silong Wang (Ecology, 2016)
Nitrogen addition has been shown to affect plant litter decomposition in terrestrial ecosystems. The way that nitrogen deposition impacts the relationship between plant litter decomposition and altered soil nitrogen availability is unclear, however. This study examined 18 co‐occurring litter types in a subtropical forest in China in terms of their decomposition (1 yr of exposure in the field) with nitrogen addition treatment (0, 0.4, 1.6, and 4.0 mol·N·m −2 ·yr −1 ) and soil fauna exclusion (litter bags with 0.1 and 2 cm mesh size). Results showed that the plant litter decomposition rate is significantly reduced because of nitrogen addition; the strength of the nitrogen addition effect is closely related to the nitrogen addition levels. Plant litters with diverse quality responded to nitrogen addition differently. When soil fauna was present, the nitrogen addition effect on medium‐quality or high‐quality plant litter decomposition rate was −26% ± 5% and −29% ± 4%, respectively; these values are significantly higher than that of low‐quality plant litter decomposition. The pattern is similar when soil fauna is absent. In general, the plant litter decomposition rate is decreased by soil fauna exclusion; an average inhibition of −17% ± 1.5% was exhibited across nitrogen addition treatment and litter quality groups. However, this effect is weakly related to nitrogen addition treatment and plant litter quality. We conclude that the variations in plant litter quality, nitrogen deposition, and soil fauna are important factors of decomposition and nutrient cycling in a subtropical forest ecosystem.

Tree species classification based on stem-related feature parameters derived from static terrestrial laser scanning data - Tian Wei; Yi Lin; Lei Yan; Lifu Zhang (International Journal of Remote Sensing, 2016)

Three-dimensional rock slope stability analysis considering the surface load distribution - Hang Lin; Wenwen Zhong; Ping Cao (European Journal of Environmental and Civil Engineering, 2016)

Zircon U–Pb and molybdenite Re–Os geochronology of copper–molybdenum deposits in southeast Liaoning Province, China - Peng Zhang; Yan Zhao; Lin-Lin Kou; Hong-Zhi Yang; Feng-Chao Yang (International Geology Review, 2016)

A graph-based approach for the co-registration refinement of very-high-resolution imagery and digital line graphic data - Zhou Guo; Shihong Du; Wenzhi Zhao; Fangning He; Yun-Jou Lin (International Journal of Remote Sensing, 2016)

In Situ Field-Scale Remediation of Low Cd-Contaminated Paddy Soil Using Soil Amendments - Lin-feng Li; Shao-ying Ai; Yan-hong Wang; Ming-deng Tang; Yi-Chun Li (Water, Air, & Soil Pollution, 2016)

Biosurfactant Production by Marine-Originated Bacteria Bacillus Subtilis and Its Application for Crude Oil Removal - Zhiwen Zhu; Baiyu Zhang; Bing Chen; Qinghong Cai; Weiyun Lin (Water, Air, & Soil Pollution, 2016)

Improving the Long Lead-Time Inundation Forecasts Using Effective Typhoon Characteristics - Bing-Chen Jhong; Jhih-Huang Wang; Gwo-Fong Lin (Water Resources Management, 2016)

Urban high-resolution fossil fuel CO2 emissions quantification and exploration of emission drivers for potential policy applications - Risa Patarasuk; Kevin Robert Gurney; Darragh O’Keeffe; Yang Song; Jianhua Huang; Preeti Rao; Martin Buchert; John C. Lin; Daniel Mendoza; James R. Ehleringer (Urban Ecosystems, 2016)

Present-Day Crustal Vertical Motion Around the Ordos Block Constrained by Precise Leveling and GPS Data - Ming Hao; Qingliang Wang; Duxin Cui; Liwei Liu; Lin Zhou (Surveys in Geophysics, 2016)

Diversified variants of the mcr-1-carrying plasmid reservoir in the swine lung microbiota - Zhencui Li; Chen Tan; Jingxia Lin; Youjun Feng (Science China Life Sciences, 2016)

The agranular and granular insula differentially contribute to gambling-like behavior on a rat slot machine task: effects of inactivation and local infusion of a dopamine D4 agonist on reward expectancy - P. J. Cocker; M. Y. Lin; M. M. Barrus; B. Le Foll; C. A. Winstanley (Psychopharmacology, 2016)

Betaine enhances antidepressant-like, but blocks psychotomimetic effects of ketamine in mice - Jen-Cheng Lin; Mei-Yi Lee; Ming-Huan Chan; Yi-Chyan Chen; Hwei-Hsien Chen (Psychopharmacology, 2016)

The catalytic subunit of magnesium-protoporphyrin IX monomethyl ester cyclase forms a chloroplast complex to regulate chlorophyll biosynthesis in rice - Weiyi Kong; Xiaowen Yu; Haiyuan Chen; Linglong Liu; Yanjia Xiao; Yunlong Wang; Chaolong Wang; Yun Lin; Yang Yu; Chunming Wang; Ling Jiang; Huqu Zhai; et al. (Plant Molecular Biology, 2016)

Phosphate starvation promoted the accumulation of phenolic acids by inducing the key enzyme genes in Salvia miltiorrhiza hairy roots - Lin Liu; DongFeng Yang; TongYao Liang; HaiHua Zhang; ZhiGui He; ZongSuo Liang (Plant Cell Reports, 2016)

Methylation and Esterification of Magnolol for Ameliorating Cutaneous Targeting and Therapeutic Index by Topical Application - Chwan-Fwu Lin; Chi-Feng Hung; Ibrahim A. Aljuffali; Yu-Ling Huang; Wei-Chun Liao; Jia-You Fang (Pharmaceutical Research, 2016)

Nutraceuticals in Neurodegeneration and Aging - Wei-Yi Ong; Grace Y. Sun; W. Gibson Wood; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Interleukin-35 (IL-35) inhibits proliferation and promotes apoptosis of fibroblast-like synoviocytes isolated from mice with collagen-induced arthritis - Yunxia Li; Suqin Wu; Yuxuan Li; Shenyi Jiang; Tiantian Lin; Liping Xia; Hui Shen; Jing Lu (Molecular Biology Reports, 2016)

Inhibition of Peripheral TNF-α and Downregulation of Microglial Activation by Alpha-Lipoic Acid and Etanercept Protect Rat Brain Against Ischemic Stroke - Ming-Hsiu Wu; Chao-Ching Huang; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

Examining the Neural and Astroglial Protective Effects of Cellular Prion Protein Expression and Cell Death Protease Inhibition in Mouse Cerebrocortical Mixed Cultures - Kevin K. W. Wang; Zhihui Yang; Allen Chiu; Fan Lin; Richard Rubenstein (Molecular Neurobiology, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

Cobalt Protoporphyrin Upregulates Cyclooxygenase-2 Expression Through a Heme Oxygenase-Independent Mechanism - Hsiao-Yun Lin; Chon-Haw Tsai; Chingju Lin; Wei-Lan Yeh; Cheng-Fang Tsai; Pei-Chun Chang; Ling-Hsuan Wu; Dah-Yuu Lu (Molecular Neurobiology, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

A Pooling Genome-Wide Association Study Combining a Pathway Analysis for Typical Sporadic Parkinson’s Disease in the Han Population of Chinese Mainland - Yakun Hu; Libing Deng; Jie Zhang; Xin Fang; Puming Mei; Xuebing Cao; Jiari Lin; Yi Wei; Xiong Zhang; Renshi Xu (Molecular Neurobiology, 2016)

Early detection of white mold caused by Sclerotinia sclerotiorum in potato fields using real-time PCR - Mohammad Reza Ojaghian; Jing-Ze Zhang; Fan Zhang; Wen Qiu; Xiao-Lin Li; Guan-Lin Xie; Shui-Jin Zhu (Mycological Progress, 2016)

A20 reduces lipid storage and inflammation in hypertrophic adipocytes via p38 and Akt signaling - Luoyan Ai; Xiaohan Wang; Zhiwei Chen; Qing Lin; Dazhi Su; Qingqing Xu; Changwei Wu; Xiaoke Jiang; Antao Xu; Zhuping Fan (Molecular and Cellular Biochemistry, 2016)

FGF21 ameliorates nonalcoholic fatty liver disease by inducing autophagy - Shenglong Zhu; Yunzhou Wu; Xianlong Ye; Lei Ma; Jianying Qi; Dan Yu; Yuquan Wei; Guangxiao Lin; Guiping Ren; Deshan Li (Molecular and Cellular Biochemistry, 2016)

A novel technology: microfluidic devices for microbubble ultrasound contrast agent generation - Hangyu Lin; Junfang Chen; Chuanpin Chen (Medical & Biological Engineering & Computing, 2016)

Arbuscular mycorrhizal fungi optimize the acquisition and translocation of Cd and P by cucumber (Cucumis sativus L.) plant cultivated on a Cd-contaminated soil - Junli Hu; Wing Tsang; Fuyong Wu; Shengchun Wu; Junhua Wang; Xiangui Lin; Ming Hung Wong (Journal of Soils and Sediments, 2016)

Promising Role of Moderate Soil Drying and Subsequent Recovery Through Moderate Wetting at Grain-Filling Stage for Rice Yield Enhancement - Zhong Li; Saadia Azeem; Zhixing Zhang; Zhou Li; Hong Zhao; Wenxiong Lin (Journal of Plant Growth Regulation, 2016)

Tomato Jasmonic Acid-Deficient Mutant spr2 Seedling Response to Cadmium Stress - Shiyang Zhao; Qunfei Ma; Xin Xu; Guangzhe Li; Lin Hao (Journal of Plant Growth Regulation, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

Impact of heat waves on nonaccidental deaths in Jinan, China, and associated risk factors - Jun Zhang; Shouqin Liu; Jing Han; Lin Zhou; Yueling Liu; Liu Yang; Ji Zhang; Ying Zhang (International Journal of Biometeorology, 2016)

Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Deep-sequencing transcriptome analysis of field-grown Medicago sativa L. crown buds acclimated to freezing stress - Lili Song; Lin Jiang; Yue Chen; Yongjun Shu; Yan Bai; Changhong Guo (Functional & Integrative Genomics, 2016)

Cadmium accumulation characteristics of F1 hybrids by reciprocal hybridizing of Solanum nigrum in two climate–ecology regions - Lijin Lin; Jing He; Xun Wang; Jin Wang; Xiulan Lv; Ming’an Liao; Zhihui Wang; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai (Environmental Science and Pollution Research, 2016)

Low temperature destruction of PCDD/Fs over V2O5-CeO2/TiO2 catalyst with ozone - Ming-feng Yu; Xiao-qing Lin; Mi Yan; Xiao-dong Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

The fractionation and geochemical characteristics of rare earth elements measured in ambient size-resolved PM in an integrated iron and steelmaking industry zone - Qili Dai; Liwei Li; Jiamei Yang; Baoshuang Liu; Xiaohui Bi; Jianhui Wu; YuFen Zhang; Lin Yao; Yinchang Feng (Environmental Science and Pollution Research, 2016)

Source identification and risk assessment of heavy metal contaminations in urban soils of Changsha, a mine-impacted city in Southern China - Li Ma; Zhaoguang Yang; Lei Li; Lin Wang (Environmental Science and Pollution Research, 2016)

Health risk assessment of heavy metals in soil-plant system amended with biogas slurry in Taihu basin, China - Bo Bian; Cheng Lin; Lin Lv (Environmental Science and Pollution Research, 2016)

Protective Effects of Extracellular and Intracellular Polysaccharides on Hepatotoxicity by Hericium erinaceus SG-02 - Fangyuan Cui; Xia Gao; Jianjun Zhang; Min Liu; Chen Zhang; Nuo Xu; Huajie Zhao; Lin Lin; Meng Zhou; Le Jia (Current Microbiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Characterization of an ene-reductase from Meyerozyma guilliermondii for asymmetric bioreduction of α,β-unsaturated compounds - Baoqi Zhang; Liandan Zheng; Jinping Lin; Dongzhi Wei (Biotechnology Letters, 2016)

Mapping anhedonia-specific dysfunction in a transdiagnostic approach: an ALE meta-analysis - Bei Zhang; Pan Lin; Huqing Shi; Dost Öngür; Randy P. Auerbach; Xiaosheng Wang; Shuqiao Yao; Xiang Wang (Brain Imaging and Behavior, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Iodine Status of Vulnerable Populations in Henan Province of China 2013–2014 After the Implementation of the New Iodized Salt Standard - Jin Yang; Lin Zhu; Xiaofeng Li; Heming Zheng; Zhe Wang; Yang Liu; Zongyu Hao (Biological Trace Element Research, 2016)

Optimization of Water Pumping and Injection for Underground Coal Gasification in the Meiguiying Mine, China - Donglin Dong; Mingdong Zhao; Gang Lin; Weijun Zhao; Kai Zhang; Neng Li (Mine Water and the Environment, 2016)

Ecological species groups and interspecific association of vegetation in natural recovery process at Xiejiadian landslide after 2008 Wenchuan earthquake - Qing-wei Yang; Shou-jiang Liu; Cui-hua Hu; Ye-bin Lin; Bin Zhang; Ming-liang Luo; Hui-ling Peng (Journal of Mountain Science, 2016)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

Genomewide association analysis for awn length linked to the seed shattering gene qSH1 in rice - RISPER AUMA MAGWA; HU ZHAO; WEN YAO; WEIBO XIE; LIN YANG; YONGZHONG XING; XUFENG BAI (Journal of Genetics, 2016)

Lack of association between rs10491334 in the CAMK4 gene and longevity in a Chinese population - RONG LIN; YUNXIA ZHANG; DONGJING YAN; XIAOPING LIAO; YUNXIN FU; WANGWEI CAI (Journal of Genetics, 2016)

Association of a common rs9939609 variant in the fat mass and obesity-associated (FTO) gene with obesity and metabolic phenotypes in a Taiwanese population: a replication study - TUN-JEN HSIAO; EUGENE LIN (Journal of Genetics, 2016)

Infanticide in the Indo-Pacific humpback dolphin (Sousa chinensis) - Ruiqiang Zheng; Leszek Karczmarski; Wenzhi Lin; Stephen C. Y. Chan; Wei-Lun Chang; Yuping Wu (Journal of Ethology, 2016)

Estimating the effect of shallow groundwater on diurnal heat transport in a vadose zone - Jianmei Jiang; Lin Zhao; Zhe Zhai (Frontiers of Earth Science, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The complete chloroplast genome of a Tertiary relict species Liriodendron chinense (Magnoliaceae) - Bin Li; Yanda Li; Qifei Cai; Furong Lin; Qinyang Meng; Yongqi Zheng (Conservation Genetics Resources, 2016)

Bioethanol production by heterologous expression of two individual 1-FEH genes from Helianthus tuberosus in Saccharomyces cerevisiae 6525 - Xi Zhang; Huanhuan Xu; Ruixin Fu; Lijin Jin; Haiyan Zhao; Lin Wang; Mingxiang Liang (BioEnergy Research, 2016)

Isolation and characterization of a distinct duck-origin goose parvovirus causing an outbreak of duckling short beak and dwarfism syndrome in China - Shilong Chen; Shao Wang; Xiaoxia Cheng; Shifeng Xiao; Xiaoli Zhu; Fengqiang Lin; Nanyang Wu; Jinxiang Wang; Meiqing Huang; Min Zheng; Shaoying Chen; Fusong Yu (Archives of Virology, 2016)

Paleokarst system based on FMI facies analysis: a case study in the Yingshan Formation at the Tazhong uplift in the Tarim Basin, Northwest China - Xiaojie Geng; Changsong Lin; Bin Wu; Hao Li (Arabian Journal of Geosciences, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Greater nitrogen dioxide concentrations at child versus adult breathing heights close to urban main road kerbside - Hannah S. Kenagy; Chun Lin; Hao Wu; Mathew R. Heal (Air Quality, Atmosphere & Health, 2016)

The characteristics of warm water inflowing and its temporal and spatial variation on the Prydz Bay continental shelf, Antarctic - Lina Lin; Hongxia Chen; Na Liu (Acta Oceanologica Sinica, 2016)

Satellite SAR observation of the sea surface wind field caused by rain cells - Xiaomin Ye; Mingsen Lin; Xinzhe Yuan; Jing Ding; Xuetong Xie; Yi Zhang; Ying Xu (Acta Oceanologica Sinica, 2016)

A study of sea level variability and its long-term trend in the South China Sea - Ying Xu; Mingsen Lin; Quan’an Zheng; Qingtao Song; Xiaomin Ye (Acta Oceanologica Sinica, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Plant diversity accurately predicts insect diversity in two tropical landscapes - Kai Zhang; Siliang Lin; Yinqiu Ji; Chenxue Yang; Xiaoyang Wang; Chunyan Yang; Hesheng Wang; Haisheng Jiang; Rhett D. Harrison; Douglas W. Yu (Molecular Ecology, 2016)
Plant diversity surely determines arthropod diversity, but only moderate correlations between arthropod and plant species richness had been observed until Basset et al . (Science, 338, 2012 and 1481) finally undertook an unprecedentedly comprehensive sampling of a tropical forest and demonstrated that plant species richness could indeed accurately predict arthropod species richness. We now require a high‐throughput pipeline to operationalize this result so that we can (i) test competing explanations for tropical arthropod megadiversity, (ii) improve estimates of global eukaryotic species diversity, and (iii) use plant and arthropod communities as efficient proxies for each other, thus improving the efficiency of conservation planning and of detecting forest degradation and recovery. We therefore applied metabarcoding to Malaise‐trap samples across two tropical landscapes in China. We demonstrate that plant species richness can accurately predict arthropod (mostly insect) species richness and that plant and insect community compositions are highly correlated, even in landscapes that are large, heterogeneous and anthropogenically modified. Finally, we review how metabarcoding makes feasible highly replicated tests of the major competing explanations for tropical megadiversity.

Mixed population genomics support for the central marginal hypothesis across the invasive range of the cane toad ( Rhinella marina ) in Australia - Daryl R. Trumbo; Brendan Epstein; Paul A. Hohenlohe; Ross A. Alford; Lin Schwarzkopf; Andrew Storfer (Molecular Ecology, 2016)
Understanding factors that cause species' geographic range limits is a major focus in ecology and evolution. The central marginal hypothesis ( CMH ) predicts that species cannot adapt to conditions beyond current geographic range edges because genetic diversity decreases from core to edge due to smaller, more isolated edge populations. We employed a population genomics framework using 24 235–33 112 SNP loci to test major predictions of the CMH in the ongoing invasion of the cane toad ( Rhinella marina ) in Australia. Cane toad tissue samples were collected along broad‐scale, core‐to‐edge transects across their invasive range. Geographic and ecological core areas were identified using GIS and habitat suitability indices from ecological niche modelling. Bayesian clustering analyses revealed three genetic clusters, in the northwest invasion‐front region, northeast precipitation‐limited region and southeast cold temperature‐limited region. Core‐to‐edge patterns of genetic diversity and differentiation were consistent with the CMH in the southeast, but were not supported in the northeast and showed mixed support in the northwest. Results suggest cold temperatures are a likely contributor to southeastern range limits, consistent with CMH predictions. In the northeast and northwest, ecological processes consisting of a steep physiological barrier and ongoing invasion dynamics, respectively, are more likely explanations for population genomic patterns than the CMH .

Historical biogeography of the short‐faced scorpionflies (Insecta: Mecoptera: Panorpodidae) - Gui‐Lin Hu; Bao‐Zhen Hua (Journal of Biogeography, 2016)
Aim Panorpodidae is a species‐poor family of Mecoptera, containing only 13 species in its two genera, Panorpodes and Brachypanorpa . They are found disjunctly in eastern Asia and North America, and this distribution has been deeply affected by the region's complex geological and climatic history. We calculate a time‐calibrated molecular phylogeny and use it to reconstruct the historical biogeography of the Panorpodidae, in order to explore the family's phylogenetic origin and the biogeographical process that resulted in the present disjunct distribution. Location Eastern Asia and North America. Methods Sequence data from mitochondrial ( COI and COII ) and nuclear DNA ( 28S and EF ‐1 α) were assembled from eight ingroup species. A phylogeny was reconstructed using maximum‐likelihood analysis and Bayesian inference, and divergence times were estimated using fossil‐calibrated Bayesian analysis. Ancestral areas were reconstructed with rasp 3.02, implementing dispersal–vicariance analysis, dispersal–extinction–cladogenesis and Bayesian binary MCMC . Results The initial diversification of Panorpodidae occurred during the Ypresian ( c. 53.9 Ma). A wide ancestral distribution in eastern Asia and western North America was inferred from the biogeographical analyses. The original range of Panorpodes across eastern Asia and western North America was fragmented by intercontinental vicariance. The genus Brachypanorpa was initially restricted to western North America and subsequently dispersed into eastern regions of North America. Main conclusions Two alternative biogeographical patterns were recovered. Either Panorpodidae was restricted to western North America in the Eocene and subsequently dispersed into eastern Asia or – more reasonably – it was widely distributed in western North America, eastern Asia and Europe during the Eocene. Our biogeographical reconstructions corroborate the significant role of vicariance in shaping the current eastern Asian and North American disjunction in Panorpodes . The geographical separation of western and eastern North American Brachypanorpa species is likely to have resulted from the uplift of the Rocky Mountains and the emergence of grassland biomes in central North America.

The deep‐sea glass sponge L ophophysema eversa harbours potential symbionts responsible for the nutrient conversions of carbon, nitrogen and sulfur - Ren‐Mao Tian; Jin Sun; Lin Cai; Wei‐Peng Zhang; Guo‐Wei Zhou; Jian‐Wen Qiu; Pei‐Yuan Qian (Environmental Microbiology, 2016)
Summary Glass sponge ( H exactinellida , P orifera ) is a special lineage because of its unique tissue organization and skeleton material. Structure and physiology of glass sponge have been extensively studied. However, our knowledge of the glass sponge‐associated microbial community and of the interaction with the host is rather limited. Here, we performed genomic studies on the microbial community in the glass sponge L ophophysema eversa in seamount. The microbial community was dominated by an ammonia‐oxidizing archaeum ( AOA ), a nitrite‐oxidizing bacterium ( NOB ) and a sulfur‐oxidizing bacterium ( SOB ), all of which were autotrophs. Genomic analysis on the AOA , NOB and SOB in the sponge revealed specific functional features of sponge‐associated microorganisms in comparison with the closely related free‐living relatives, including chemotaxis, phage defence, vitamin biosynthesis and nutrient uptake among others, which are related to ecological functions. The three autotrophs play essential roles in the cycles of carbon, nitrogen and sulfur in the microenvironment inside the sponge body, and they are considered to play symbiotic roles in the host as scavengers of toxic ammonia, nitrite and sulfide. Our study extends knowledge regarding the metabolism and the evolution of chemolithotrophs inside the invertebrate body.

Convergence and divergence in a long‐term old‐field succession: the importance of spatial scale and species abundance - Shao‐peng Li; Marc W. Cadotte; Scott J. Meiners; Zhichao Pu; Tadashi Fukami; Lin Jiang (Ecology Letters, 2016)
Whether plant communities in a given region converge towards a particular stable state during succession has long been debated, but rarely tested at a sufficiently long time scale. By analysing a 50‐year continuous study of post‐agricultural secondary succession in New Jersey, USA , we show that the extent of community convergence varies with the spatial scale and species abundance classes. At the larger field scale, abundance‐based dissimilarities among communities decreased over time, indicating convergence of dominant species, whereas incidence‐based dissimilarities showed little temporal tend, indicating no sign of convergence. In contrast, plots within each field diverged in both species composition and abundance. Abundance‐based successional rates decreased over time, whereas rare species and herbaceous plants showed little change in temporal turnover rates. Initial abandonment conditions only influenced community structure early in succession. Overall, our findings provide strong evidence for scale and abundance dependence of stochastic and deterministic processes over old‐field succession.

Linking individual‐level functional traits to tree growth in a subtropical forest - Xiaojuan Liu; Nathan G. Swenson; Dunmei Lin; Xiangcheng Mi; María Natalia Umaña; Bernhard Schmid; Keping Ma (Ecology, 2016)
Forging strong links between traits and performance is essential for understanding and predicting community assembly and dynamics. Functional trait analyses of trees that have correlated single‐trait values with measures of performance such as growth and mortality have generally found weak relationships. A reason for these weak relationships is the failure to use individual‐level trait data while simultaneously putting that data into the context of the abiotic setting, neighborhood composition, and the remaining axes constituting the overall phenotype. Here, utilizing detailed growth and trait data for 59 species of trees in a subtropical forest, we demonstrate that the individual‐level functional trait values are strongly related to individual growth rates, and that the strength of these relationships critically depends on the context of that individual. We argue that our understanding of trait–performance relationships can be greatly improved with individual‐level data so long as that data is put into the proper context.

In vitro anti-tumor activity of the tanshinone IIA against SKOV3 cells - Ju Huang; Hao Lin; YingKai Hong (Natural Product Research, 2016)

Assessing the conservation effectiveness of wetland protected areas in Northeast China - Chunyan Lu; Zongming Wang; Lin Li; Puzhou Wu; Dehua Mao; Mingming Jia; Zhangyu Dong (Wetlands Ecology and Management, 2016)

Simulation of Water Quality under Different Reservoir Regulation Scenarios in the Tidal River - Tao Jiang; Ming Zhong; Ying-jie Cao; Long-jian Zou; Bo Lin; Ai-ping Zhu (Water Resources Management, 2016)

Proteomic profile of Citrus grandis roots under long-term boron-deficiency revealed by iTRAQ - Lin-Tong Yang; Yi-Bin Lu; Yuan Zhang; Peng Guo; Li-Song Chen (Trees, 2016)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Prevalence and phylogenetic characterization of canine coronavirus from diseased pet dogs in Beijing, China - Shuai Lu; Di Zhang; Jianfang Zhou; Zhaofei Xia; Degui Lin; Yongliang Lou; Wenjie Tan; Kun Qin (Science China Life Sciences, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Plant food sources and stone tools’ function at the site of Shunshanji based on starch grain analysis - YuZhang Yang; WeiYa Li; Ling Yao; ZhiJie Cheng; WuHong Luo; JuZhong Zhang; LiuGen Lin; HuiYuan Gan; Long Yan (Science China Earth Sciences, 2016)

Characteristic of In Situ Stress and Its Control on the Coalbed Methane Reservoir Permeability in the Eastern Margin of the Ordos Basin, China - Junlong Zhao; Dazhen Tang; Hao Xu; Yong Li; Song Li; Shu Tao; Wenji Lin; Zhenxing Liu (Rock Mechanics and Rock Engineering, 2016)

Cracking Process and Stress Field Evolution in Specimen Containing Combined Flaw Under Uniaxial Compression - Ting Liu; Baiquan Lin; Wei Yang; Quanle Zou; Jia Kong; Fazhi Yan (Rock Mechanics and Rock Engineering, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

Ecophysiology of picophytoplankton in different water masses of the northern Bering Sea - Fang Zhang; Ling Lin; Yuan Gao; Shunan Cao; Jianfeng He (Polar Biology, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Two AMT2-Type Ammonium Transporters from Pyrus betulaefolia Demonstrate Distinct Expression Characteristics - Hui Li; Yu Cong; You-hong Chang; Jing Lin (Plant Molecular Biology Reporter, 2016)

Wax crystal-sparse leaf 3 encoding a β-ketoacyl-CoA reductase is involved in cuticular wax biosynthesis in rice - Lu Gan; Xiaole Wang; Zhijun Cheng; Linglong Liu; Jiulin Wang; Zhe Zhang; Yulong Ren; Cailin Lei; Zhichao Zhao; Shanshan Zhu; Qibing Lin; Fuqing Wu; et al. (Plant Cell Reports, 2016)

Scale-dependent effect of biotic interactions and environmental conditions in community assembly: insight from a large temperate forest plot - Zuoqiang Yuan; Antonio Gazol; Fei Lin; Xugao Wang; Ji Ye; Yanyan Suo; Shuai Fang; Jarad Mellard; Zhanqing Hao (Plant Ecology, 2016)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

Extracellular Cl− regulates human SO4 2−/anion exchanger SLC26A1 by altering pH sensitivity of anion transport - Meng Wu; John F. Heneghan; David H. Vandorpe; Laura I. Escobar; Bai-Lin Wu; Seth L. Alper (Pflügers Archiv - European Journal of Physiology, 2016)

Baicalin Attenuates Ketamine-Induced Neurotoxicity in the Developing Rats: Involvement of PI3K/Akt and CREB/BDNF/Bcl-2 Pathways - Daiying Zuo; Li Lin; Yumiao Liu; Chengna Wang; Jingwen Xu; Feng Sun; Lin Li; Zengqiang Li; Yingliang Wu (Neurotoxicity Research, 2016)

Erratum to: Progressive changes of orexin system in a rat model of 6-hydroxydopamine-induced Parkinson’s disease - Long-Biao Cui; Bo-Wei Li; Xiao-Hang Jin; Lin Zhao; Juan Shi (Neuroscience Bulletin, 2016)

Serine 707 of APPL1 is Critical for the Synaptic NMDA Receptor-Mediated Akt Phosphorylation Signaling Pathway - Jiejie Wang; Wen Lu; Lin Chen; Ping Zhang; Tingting Qian; Wei Cao; Jianhong Luo (Neuroscience Bulletin, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Nuclear Factor-kappaB-Dependent Sestrin2 Induction Mediates the Antioxidant Effects of BDNF Against Mitochondrial Inhibition in Rat Cortical Neurons - Chia-Lin Wu; Shang-Der Chen; Jiu-Haw Yin; Chi-Shin Hwang; Ding-I Yang (Molecular Neurobiology, 2016)

Interleukin-17A Acts to Maintain Neuropathic Pain Through Activation of CaMKII/CREB Signaling in Spinal Neurons - Cheng-ye Yao; Ze-lin Weng; Jian-cheng Zhang; Tao Feng; Yun Lin; Shanglong Yao (Molecular Neurobiology, 2016)

Obesity Exacerbates Rat Cerebral Ischemic Injury through Enhancing Ischemic Adiponectin-Containing Neuronal Apoptosis - Ming-Hsiu Wu; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Chao-Ching Huang; Mao-Tsun Lin (Molecular Neurobiology, 2016)

PPAR-γ Ameliorates Neuronal Apoptosis and Ischemic Brain Injury via Suppressing NF-κB-Driven p22phox Transcription - Jui-Sheng Wu; Hsin-Da Tsai; Wai-Mui Cheung; Chung Y. Hsu; Teng-Nan Lin (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Spatiotemporal properties of growing season indices during 1961–2010 and possible association with agroclimatological regionalization of dominant crops in Xinjiang, China - Hui Ci; Qiang Zhang; Vijay P. Singh; Mingzhong Xiao; Lin Liu (Meteorology and Atmospheric Physics, 2016)

Probiotic properties of lactic acid bacteria isolated from traditionally fermented Xinjiang cheese - Ramila Azat; Yan Liu; Wei Li; Abdurihim Kayir; Ding-bo Lin; Wen-wen Zhou; Xiao-dong Zheng (Journal of Zhejiang University-SCIENCE B, 2016)

Reliability back analysis of shear strength parameters of landslide with three-dimensional upper bound limit analysis theory - Lian-Heng Zhao; Shi Zuo; Yu-Liang Lin; Liang Li; Yingbin Zhang (Landslides, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Automatic Wheezing Detection Using Speech Recognition Technique - Bor-Shing Lin; Bor-Shyh Lin (Journal of Medical and Biological Engineering, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

Cannibalistic viruses in the aquatic environment: role of virophages in manipulating microbial communities - V. Marie; J. Lin (International Journal of Environmental Science and Technology, 2016)

BM-MSCs and Bio-Oss complexes enhanced new bone formation during maxillary sinus floor augmentation by promoting differentiation of BM-MSCs - Qian Zhou; Bo-Han Yu; Wei-Cai Liu; Zuo-Lin Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Catalytic destruction of PCDD/Fs over vanadium oxide-based catalysts - Ming-feng Yu; Xiao-qing Lin; Xiao-dong Li; Mi Yan; Bayu Prabowo; Wen-wei Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Atmospheric polycyclic aromatic hydrocarbons (PAHs) of southern Taiwan in relation to monsoons - Jing-O Cheng; Fung-Chi Ko; Chon-Lin Lee; Meng-Der Fang (Environmental Science and Pollution Research, 2016)

The relationships of meteorological factors and nutrient levels with phytoplankton biomass in a shallow eutrophic lake dominated by cyanobacteria, Lake Dianchi from 1991 to 2013 - Qichao Zhou; Yunlin Zhang; Dunmei Lin; Kun Shan; Yu Luo; Lei Zhao; Zhiwei Tan; Lirong Song (Environmental Science and Pollution Research, 2016)

Adaptability comparison of E. fetida in vermicomposting against sludge from livestock wastewater treatment plant based on their several growth stages - Xiaoxia Hao; Hongwen Hu; Xuewei Li; Dongmei Jiang; Li Zhu; Lin Bai (Environmental Science and Pollution Research, 2016)

Co and Fe-catalysts supported on sepiolite: effects of preparation conditions on their catalytic behaviors in high temperature gas flow treatment of dye - Xiangfeng Lin; Jian Fang; Menglin Chen; Zhi Huang; Chengyuan Su (Environmental Science and Pollution Research, 2016)

Brominated flame retardants in the hair and serum samples from an e-waste recycling area in southeastern China: the possibility of using hair for biomonitoring - Si Liang; Feng Xu; Weibiao Tang; Zheng Zhang; Wei Zhang; Lili Liu; Junxia Wang; Kuangfei Lin (Environmental Science and Pollution Research, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Bone microenvironment-mediated resistance of cancer cells to bisphosphonates and impact on bone osteocytes/stem cells - Abeer Alasmari; Shih-Chun Lin; Serge Dibart; Erdjan Salih (Clinical & Experimental Metastasis, 2016)

Soft tissue invasion of papillary thyroid carcinoma - Jen-Der Lin; Chuen Hsueh; Tzu-Chieh Chao (Clinical & Experimental Metastasis, 2016)

The relationship between action anticipation and emotion recognition in athletes of open skill sports - Yu-Ling Shih; Chia-Yen Lin (Cognitive Processing, 2016)

Genomic analysis of a xylose operon and characterization of novel xylose isomerase and xylulokinase from Bacillus coagulans NL01 - Zhaojuan Zheng; Xi Lin; Ting Jiang; Weihua Ye; Jia Ouyang (Biotechnology Letters, 2016)

The use of chlorogenic acid and its analogues as inhibitors: an investigation of the inhibition of sortase A of Staphylococcus aureus using molecular docking and dynamic simulation - Chongwei Bi; Lin Wang; Xiaodi Niu; Hongjun Cai; Xiaobo Zhong; Xuming Deng; Tiedong Wang; Dacheng Wang (Biotechnology Letters, 2016)

Pranlukast, a novel binding ligand of human Raf1 kinase inhibitory protein - Tao Sun; Zhihua Wu; Mengyao Luo; Donghai Lin; Chenyun Guo (Biotechnology Letters, 2016)

MeHg Suppressed Neuronal Potency of Hippocampal NSCs Contributing to the Puberal Spatial Memory Deficits - Jianying Tian; Yougen Luo; Weiwei Chen; Shengsen Yang; Hao Wang; Jing Cui; Zhiyan Lu; Yuanye Lin; Yongyi Bi (Biological Trace Element Research, 2016)

Conversion of a natural evergreen broadleaved forest into coniferous plantations in a subtropical area: effects on composition of soil microbial communities and soil respiration - Jianfen Guo; Zhijie Yang; Chengfang Lin; Xiaofei Liu; Guangshui Chen; Yusheng Yang (Biology and Fertility of Soils, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

An approach to determination of phenolic compounds in seawater using SPME-GC-MS based on SWCNTs coating - Jia Zhu; Ying Wang; Lin Zeng (Journal of Ocean University of China, 2016)

Study on biogenic amines in various dry salted fish consumed in China - Yanyan Wu; Yufeng Chen; Laihao Li; Xianqing Yang; Shaoling Yang; Wanling Lin; Yongqiang Zhao; Jianchao Deng (Journal of Ocean University of China, 2016)

Advanced glycation endproducts in 35 types of seafood products consumed in eastern China - Jing Wang; Zhenxing Li; Ramesh Tushar Pavase; Hong Lin; Long Zou; Jie Wen; Liangtao Lv (Journal of Ocean University of China, 2016)

Interannual variability of summer rainfall over the northern part of China and the related circulation features - Cholaw Bueh; Yan Li; Dawei Lin; Yi Lian (Journal of Meteorological Research, 2016)

Population geography in China since the 1980s: Forging the links between population studies and human geography - Yu Zhu; Jinhong Ding; Guixin Wang; Jianfa Shen; Liyue Lin; Wenqian Ke (Journal of Geographical Sciences, 2016)

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

The Aggregation Pheromone of Phyllotreta striolata (Coleoptera: Chrysomelidae) Revisited - Franziska Beran; Guillermo H. Jiménez-Alemán; Mei-ying Lin; Yun-Che Hsu; Inga Mewis; Ramasamy Srinivasan; Christian Ulrichs; Wilhelm Boland; Bill S. Hansson; Andreas Reinecke (Journal of Chemical Ecology, 2016)

Changes in Sympathetic Innervation of Rat Caudal Artery in Experimental Myocardial Infarction. Effect of Semax Peptide - A. M. Gorbacheva; A. B. Berdalin; A. N. Stulova; A. D. Nikogosova; M. D. Lin; S. V. Buravkov; S. A. Gavrilova; V. B. Koshelev (Bulletin of Experimental Biology and Medicine, 2016)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

Dynamics and responses of vegetation to climatic variations in Ziya-Daqing basins, China - Farong Huang; Xingguo Mo; Zhonghui Lin; Shi Hu (Chinese Geographical Science, 2016)

Soil nutrient variance by slope position in a Mollisol farmland area of Northeast China - Shaoliang Zhang; Lili Jiang; Xiaobing Liu; Xingyi Zhang; Shicong Fu; Lin Dai (Chinese Geographical Science, 2016)

Complete sequence of a double-stranded RNA from the phytopathogenic fungus Erysiphe cichoracearum that might represent a novel endornavirus - Zhenguo Du; Wenzhong Lin; Ping Qiu; Xiaojuan Liu; Lingfang Guo; Kangcheng Wu; Songbai Zhang; Zujian Wu (Archives of Virology, 2016)

Complete genome sequence of a coxsackievirus B3 recombinant isolated from an aseptic meningitis outbreak in eastern China - Wenqiang Zhang; Xiaojuan Lin; Ping Jiang; Zexin Tao; Xiaolin Liu; Feng Ji; Tongzhan Wang; Suting Wang; Hui Lv; Aiqiang Xu; Haiyan Wang (Archives of Virology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Microbial community in a multi-trophic aquaculture system of Apostichopus japonicus, Styela clava and microalgae - Jian Lin; Bao Ju; Yanan Yao; Xiaoming Lin; Ronglian Xing; Li Teng; Aili Jiang (Aquaculture International, 2016)

Greenhouse gas emissions and comprehensive greenhouse effect potential of Megalobrama amblycephala culture pond ecosystems in a 3-month growing season - Lin Zhu; Xuan Che; Huang Liu; Xingguo Liu; Chong Liu; Xiaolong Chen; Xu Shi (Aquaculture International, 2016)

Fungal and bacterial endosymbionts of eared leafhoppers of the subfamily Ledrinae (Hemiptera: Cicadellidae) - Takanori Nishino; Masahiko Tanahashi; Chung-Ping Lin; Ryuichi Koga; Takema Fukatsu (Applied Entomology and Zoology, 2016)

Halomarina salina sp. nov., isolated from a marine solar saltern - Wen-Mei Xu; Jia-Qi Xu; Yao Zhou; Yang Li; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Antonie van Leeuwenhoek, 2016)

Direct Methods for Predicting Movement Biomechanics Based Upon Optimal Control Theory with Implementation in OpenSim - Sina Porsa; Yi-Chung Lin; Marcus G. Pandy (Annals of Biomedical Engineering, 2016)

Distinctive precursory air–sea signals between regular and super El Niños - Lin Chen; Tim Li; Swadhin K. Behera; Takeshi Doi (Advances in Atmospheric Sciences, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

The Sediment Source and Transport Trends around the Abandoned Yellow River Delta, China - Lin Zhang; Shenliang Chen; Liang Yi (Marine Georesources & Geotechnology, 2016)

Estimating crop chlorophyll content with hyperspectral vegetation indices and the hybrid inversion method - Liang Liang; Zhihao Qin; Shuhe Zhao; Liping Di; Chao Zhang; Meixia Deng; Hui Lin; Lianpeng Zhang; Lijuan Wang; Zhixiao Liu (International Journal of Remote Sensing, 2016)

Clinical characteristics and outcomes of veterans hospitalised with purulent soft tissue infections with and without systemic signs of infection - Craig G. Gunderson; Jurgen Holleck; John J. Chang; Shin Lin; Naseema Merchant; Shaili Gupta (Infectious Diseases, 2016)

Repair process and enzymatic activity associated with induction of shell regeneration in the invasive species Pomacea canaliculata - Song Yang; Lin-kang Ni; Liu-lan Zhao; Jin-wei Yang; Qiao Liu; Jia-en Zhang; Zhi He; Shuang Peng (Molluscan Research, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

New evidence for Neolithic rice cultivation and Holocene environmental change in the Fuzhou Basin, southeast China - Ting Ma; Zhuo Zheng; Barry V. Rolett; Gongwu Lin; Guifang Zhang; Yuanfu Yue (Vegetation History and Archaeobotany, 2016)

Investigation of peat sediments from Daiyun Mountain in southeast China: late Holocene vegetation, climate and human impact - Lin Zhao; Chunmei Ma; Lingyu Tang; Kam-biu Liu; Limi Mao; Yu Zhang; Huayu Lu; Shuangye Wu; Qingyun Tu (Vegetation History and Archaeobotany, 2016)

Unexpected complexity of multidrug resistance in the mcr-1-harbouring Escherichia coli - Rongsui Gao; Yue Li; Jingxia Lin; Chen Tan; Youjun Feng (Science China Life Sciences, 2016)

Radial propagation of magnetospheric substorm-injected energetic electrons observed using a BD-IES instrument and Van Allen Probes - QiuGang Zong; YiXin Hao; Hong Zou; SuiYan Fu; XuZhi Zhou; Jie Ren; LingHua Wang; ChongJing Yuan; ZhiYang Liu; XiangHong Jia; Lin Quan; Ying Liu; et al. (Science China Earth Sciences, 2016)

Three-dimensional crustal velocity structure model of the middle-eastern north China Craton (HBCrust1.0) - YongHong Duan; FuYun Wang; XianKang Zhang; JiYan Lin; Zhi Liu; BaoFeng Liu; ZhuoXin Yang; WenBin Guo; YunHao Wei (Science China Earth Sciences, 2016)

A Study on the Vibration Frequency of Blasting Excavation in Highly Stressed Rock Masses - Jianhua Yang; Wenbo Lu; Qinghui Jiang; Chi Yao; Shuihua Jiang; Lin Tian (Rock Mechanics and Rock Engineering, 2016)

Overexpression of a synthetic insect–plant geranyl pyrophosphate synthase gene in Camelina sativa alters plant growth and terpene biosynthesis - Jing Xi; Lorenzo Rossi; Xiuli Lin; De-Yu Xie (Planta, 2016)

Dimeric artificial microRNAs mediate high resistance to RSV and RBSDV in transgenic rice plants - Lin Sun; Chao Lin; Jinwen Du; Yunzhi Song; Mingsong Jiang; Hongmei Liu; Shumei Zhou; Fujiang Wen; Changxiang Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

PSI photoinhibition is more related to electron transfer from PSII to PSI rather than PSI redox state in Psychotria rubra - Wei Huang; Ying-Jie Yang; Jiao-Lin Zhang; Hong Hu; Shi-Bao Zhang (Photosynthesis Research, 2016)

Chidamide alleviates TGF-β-induced epithelial–mesenchymal transition in lung cancer cell lines - Sheng-Hao Lin; Bing-Yen Wang; Ching-Hsiung Lin; Peng-Ju Chien; Yueh-Feng Wu; Jiunn-Liang Ko; Jeremy J. W. Chen (Molecular Biology Reports, 2016)

Roles of Neuroglobin Binding to Mitochondrial Complex III Subunit Cytochrome c1 in Oxygen-Glucose Deprivation-Induced Neurotoxicity in Primary Neurons - Zhanyang Yu; Yu Zhang; Ning Liu; Jing Yuan; Li Lin; Qichuan Zhuge; Jian Xiao; Xiaoying Wang (Molecular Neurobiology, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke - Xiao-Lin Gu; Lin Liu; Xiang-Dong Lu; Zhen-Rui Liu (Molecular Neurobiology, 2016)

Leifiporia rhizomorpha gen. et sp. nov. and L. eucalypti comb. nov. in Polyporaceae (Basidiomycota) - Chang-Lin Zhao; Fang Wu; Yu-Cheng Dai (Mycological Progress, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

Design of wireless multi-parameter monitoring system for oral feeding of premature infants - Yu-Lin Wang; Hsing-Chien Kuo; Lin-Yu Wang; Mei-Ju Ko; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Effects of pH and polycyclic aromatic hydrocarbon pollution on thaumarchaeotal community in agricultural soils - Yucheng Wu; Qinghe Zhu; Jun Zeng; Qingmin Ding; Yi Gong; Peng Xing; Xiangui Lin (Journal of Soils and Sediments, 2016)

The application of rapidly composted manure decreases paddy CH4 emission by adversely influencing methanogenic archaeal community: a greenhouse study - Beibei Zhou; Yiming Wang; Youzhi Feng; Xiangui Lin (Journal of Soils and Sediments, 2016)

Precursor times of abnormal b-values prior to mainshocks - Jeen-Hwa Wang; Kou-Cheng Chen; Peih-Lin Leu; Chien-Hsin Chang (Journal of Seismology, 2016)

Identification and characterization of a β-1, 3-glucanase gene, TcLr19Glu, involved in wheat resistance against Puccinia triticina - Lin Gao; Shen Wang; Yanjun Zhang; Xiaoying Li; Haiyan Wang; Daqun Liu (Journal of Plant Biochemistry and Biotechnology, 2016)

Gene structure and expression characteristics of the auxin receptor TIR1 ortholog in Momordica charantia and developmental analysis of its promoter in transgenic plants - Cheng-Ku Lin; Nien-Ying Lee; Pung-Ling Huang; Yi-Yin Do (Journal of Plant Biochemistry and Biotechnology, 2016)

Adult reproductive diapause in Drosophila suzukii females - Yifan Zhai; Qingcai Lin; Jinping Zhang; Feng Zhang; Li Zheng; Yi Yu (Journal of Pest Science, 2016)

Male-Biased Capture in Light Traps in Spodoptera exigua (Lepidoptera: Noctuidae): Results from the Studies of Reproductive Activities - Wen-Jie Cheng; Xia-Lin Zheng; Pan Wang; Li-Lin Zhou; Sheng-Yun Si; Xiao-Ping Wang (Journal of Insect Behavior, 2016)

A large stokes-shifted fluorescent dye synthesized as a new probe for the determination of protein - Dayong Lin; Xuening Fei; Ran Li; Yingchun Gu; Yalin Tang; Jianguo Zhou; Baolian Zhang (Journal of Fluorescence, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Lack of association between polymorphisms in interleukin (IL)-12, IL-12R, IL-23, IL-23R genes and Takayasu arteritis in a Chinese population - Kun-Qi Yang; Yan-Kun Yang; Xu Meng; Ying Zhang; Xiong-Jing Jiang; Hai-Ying Wu; Hui-Min Zhang; Lei Song; Jin Bian; Dan Wen; Lin-Ping Wang; Xian-Liang Zhou (Inflammation Research, 2016)

PPARGC1B gene is associated with Kashin-Beck disease in Han Chinese - Yan Wen; Jingcan Hao; Xiao Xiao; Wenyu Wang; Xiong Guo; Weimin Lin; Tielin Yang; Xiaogang Liu; Hui Shen; Lijun Tan; Xiangding Chen; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Type 3 iodothyronine deiodinase in neonatal goats: molecular cloning, expression, localization, and methylation signature - Tao Zhong; Peng-Fei Jin; Wei Zhao; Lin-Jie Wang; Li Li; Hong-Ping Zhang (Functional & Integrative Genomics, 2016)

Fine mapping of qKW7, a major QTL for kernel weight and kernel width in maize, confirmed by the combined analytic approaches of linkage and association analysis - Xin Li; Yong-xiang Li; Lin Chen; Xun Wu; Weiwei Qin; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Yunsu Shi (Euphytica, 2016)

Genome-wide association study of the husk number and weight in maize (Zea mays L.) - Guangfei Zhou; Derong Hao; Guoqing Chen; Huhua Lu; Mingliang Shi; Yuxiang Mao; Zhengliang Zhang; Xiaolan Huang; Lin Xue (Euphytica, 2016)

Examination of Winter Circulation in a Northern Gulf of Mexico Estuary - Jun Lin; Chunyan Li; Kevin M. Boswell; Matthew Kimball; Lawrence Rozas (Estuaries and Coasts, 2016)

Surface water pH variations and trends in China from 2004 to 2014 - Yinhuan Qiao; Jianfeng Feng; Xia Liu; Wei Wang; Pei Zhang; Lin Zhu (Environmental Monitoring and Assessment, 2016)

Similarities and differences in combined toxicity of sulfonamides and other antibiotics towards bacteria for environmental risk assessment - Shuxia Fang; Dali Wang; Xiaoxian Zhang; Xi Long; Mengnan Qin; Zhifen Lin; Ying Liu (Environmental Monitoring and Assessment, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

Efficient photocatalytic degradation of tetracycline hydrochloride by Ag3PO4 under visible-light irradiation - QiShe Yan; MengMeng Xu; CuiPing Lin; JiFei Hu; YongGang Liu; RuiQin Zhang (Environmental Science and Pollution Research, 2016)

Contamination and human health risk of lead in soils around lead/zinc smelting areas in China - Kai Lei; Elisa Giubilato; Andrea Critto; Huiyun Pan; Chunye Lin (Environmental Science and Pollution Research, 2016)

Two-year stability of immobilization effect of sepiolite on Cd contaminants in paddy soil - Xuefeng Liang; Yi Xu; Yingming Xu; Pengchao Wang; Lin Wang; Yuebing Sun; Qingqing Huang; Rong Huang (Environmental Science and Pollution Research, 2016)

How much of the interannual variability of East Asian summer rainfall is forced by SST? - Chao He; Bo Wu; Chunhui Li; Ailan Lin; Dejun Gu; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Mechanism-based QSAR Models for the Toxicity of Quorum Sensing Inhibitors to Gram-negative and Gram-positive Bacteria - Dali Wang; Zhifen Lin; Zhengyang Huo; Ting Wang; Zhifeng Yao; Yongping Cong (Bulletin of Environmental Contamination and Toxicology, 2016)

Endoglucanase enzymatic modification of kraft pulp during recycling - Tao Deng; Liuliu Lu; Shipeng Gao; Ying Lin; Shuangyan Han (Biotechnology Letters, 2016)

Biotransformation of gypenoside XVII to compound K by a recombinant β-glucosidase - Fei-Liang Zhong; Wei-Wei Dong; Songquan Wu; Jun Jiang; Deok-Chun Yang; Donghao Li; Lin-Hu Quan (Biotechnology Letters, 2016)

Identification and characterization of a novel bifunctional Δ12/Δ15-fatty acid desaturase gene from Rhodosporidium kratochvilovae - Jinjin Cui; Shiwu He; Xiuling Ji; Lianbing Lin; Yunlin Wei; Qi Zhang (Biotechnology Letters, 2016)

Effective improvement of the activity of membrane-bound alcohol dehydrogenase by overexpression of adhS in Gluconobacter oxydans - Huan Zhang; Lulu Shi; Jinping Lin; Ming Sun; Dongzhi Wei (Biotechnology Letters, 2016)

The Effect on Sodium/Iodide Symporter and Pendrin in Thyroid Colloid Retention Developed by Excess Iodide Intake - Xiao-yi Chen; Chu-hui Lin; Li-hua Yang; Wang-gen Li; Jin-wei Zhang; Wen-wei Zheng; Xiang Wang; Jiang Qian; Jia-luan Huang; Yi-xiong Lei (Biological Trace Element Research, 2016)

Effect of Zinc on Appetite Regulatory Peptides in the Hypothalamus of Salmonella-Challenged Broiler Chickens - Xiyi Hu; Ardashir Sheikhahmadi; Xianlei Li; Yufeng Wang; Hongchao Jiao; Hai Lin; Bingkun Zhang; Zhigang Song (Biological Trace Element Research, 2016)

The Association Between Serum Selenium Levels with Rheumatoid Arthritis - Na Yu; Fang Han; Xiaojun Lin; Chun Tang; Jinghua Ye; Xiaoyan Cai (Biological Trace Element Research, 2016)

Bacteria play a more important role than nutrients in the accumulation of tetracycline resistance in manure-treated soil - Shuang Peng; Beibei Zhou; Yiming Wang; Xiangui Lin; Hongmei Wang; Cunpu Qiu (Biology and Fertility of Soils, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

The climatic impacts of land use and land cover change compared among countries - Jiyuan Liu; Quanqin Shao; Xiaodong Yan; Jiangwen Fan; Jinyan Zhan; Xiangzheng Deng; Wenhui Kuang; Lin Huang (Journal of Geographical Sciences, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Emergence of reticuloendotheliosis virus in pigeons in Guangdong Province, Southern China - Shao-Lun Zhai; Sheng-Nan Chen; Tao Lin; Xiao-Hui Wen; Wen-Kang Wei; Dian-Hong Lv; Rui-Ai Chen (Archives of Virology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Deep sequencing of banana bract mosaic virus from flowering ginger (Alpinia purpurata) and development of an immunocapture RT-LAMP detection assay - Jingxin Zhang; Wayne B. Borth; Birun Lin; Kishore K. Dey; Michael J. Melzer; Huifang Shen; Xiaoming Pu; Dayuan Sun; John S. Hu (Archives of Virology, 2016)

Aeromicrobium halotolerans sp. nov., isolated from desert soil sample - Zheng-Fei Yan; Pei Lin; Xiao Chu; MooChang Kook; Chang-Tian Li; Tae-Hoo Yi (Archives of Microbiology, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Multiplexed Fluid Flow Device to Study Cellular Response to Tunable Shear Stress Gradients - Maggie A. Ostrowski; Eva Y. Huang; Vinay N. Surya; Charlotte Poplawski; Joseph M. Barakat; Gigi L. Lin; Gerald G. Fuller; Alexander R. Dunn (Annals of Biomedical Engineering, 2016)

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

Evaluation of ocean data assimilation in CAS-ESM-C: Constraining the SST field - Xiao Dong; Renping Lin; Jiang Zhu; Zeting Lu (Advances in Atmospheric Sciences, 2016)

Effect of silicon on grain yield of rice under cadmium-stress - Hongmei Lin; Changxun Fang; Yingzhe Li; Weiwei Lin; Jianyu He; Ruiyu Lin; Wenxiong Lin (Acta Physiologiae Plantarum, 2016)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

Ectopic expression of PvSOC1, a homolog of SOC1 from Phyllostachys violascens, promotes flowering in Arabidopsis and rice - Shinan Liu; Tengfei Ma; Luyi Ma; Xinchun Lin (Acta Physiologiae Plantarum, 2016)

Arctic autumn sea ice decline and Asian winter temperature anomaly - Na Liu; Lina Lin; Yingjie Wang; Bin Kong; Zhanhai Zhang; Hongxia Chen (Acta Oceanologica Sinica, 2016)

Multiscale partitioning of small mammal β‐diversity provides novel insights into the Quaternary faunal history of Qinghai–Tibetan Plateau and Hengduan Mountains - Zhixin Wen; Qisen Yang; Qing Quan; Lin Xia; Deyan Ge; Xue Lv (Journal of Biogeography, 2016)
Aim To assess the validity of four hypothesized drivers (Quaternary climate, niche conservatism, contemporary climate, spatial configuration) of small mammal beta diversity in the Qinghai–Tibetan Plateau ( QTP ) and the Hengduan Mountains ( HDM ). Location QTP and HDM of China. Methods We partitioned the beta diversity of small mammals in QTP and HDM into the spatial turnover and nestedness components at the regional (longitudinal/latitudinal zones) and grid (1° × 1°) scales. Regional beta diversity was evaluated by calculating the multiple‐site dissimilarities and the distance‐dissimilarity relationships. We examined the relative effects of geographical distance, environmental difference, habitat diversity, geographical isolation and Quaternary climate stability on the beta diversity patterns. Results The overall beta diversity in all longitudinal/latitudinal zones of both regions was primarily driven by spatial turnover, longitudinal nestedness patterns were almost non‐existent in QTP . Turnover was stronger in the latitudinal direction of QTP and in the longitudinal direction of HDM , which corresponded to the general topography of each region. At the grid scale, higher turnover was primarily concentrated in mountainous areas. Turnover was highly correlated with geographical distance and environmental difference in both regions, and geographical isolation was another strong predictor of turnover in HDM . Habitat diversity independently explained most of the variation in nestedness of HDM . Main conclusions Spatial turnover is the primary cause of the small mammal beta diversity in QTP and HDM . Three non‐exclusive mechanisms including the historic effect of past glaciation, contemporary climate and spatial configuration of the landscape might act in combination to shape the beta diversity patterns in QTP and HDM , particularly the directional patterns. Our results challenge the prevailing view that the current distribution of QTP fauna is primarily explained by westward post‐glacial recolonization, and support the alternative idea that QTP retained considerable refugia and even centres of origin during the Quaternary glaciations.

Observed changes in precipitation extremes across 11 basins in China during 1961–2013 - Xushu Wu; Zhaoli Wang; Xiaowen Zhou; Chengguang Lai; Wenxin Lin; Xiaohong Chen (International Journal of Climatology, 2016)
Extremes of weather and climate can cause disasters such as floods and droughts. Further studies of precipitation extremes are crucial for enabling reliable projections of future changes. In this study, we used a high‐resolution (0.5° × 0.5°) gridded precipitation data set to analyse these events across the 11 basins in China between 1961 and 2013 mainly by the Mann–Kendall and generalized extreme value methods. Our results indicated a wetter trend in the Tarim River Basin ( TRB ) but drier conditions in the central Yangtze River Basin ( YRB ), western Pearl River Basin and eastern Yarlung Tsangpo River Basin. There was an increasing risk of flooding in the mid‐lower YRB and Minjiang River Basin ( MRB ), and an increasing risk of drought in the central Lantsang River Basin. The results revealed strengthened maximum 1‐day precipitation ( RX1DAY ) in the Liaohe River Basin ( LB ), YRB , MRB and TRB , together with strengthened maximum 5‐day precipitation ( RX5DAY ) in the Songhua River Basin, MRB and TRB during 1987–2013. RX1DAY and RX5DAY for return periods of 20 and 50 years gradually decreased from southeast to northwest. Along the south‐eastern coastline of the Mainland and on Hainan Island, the RX1DAY for the 20‐ and 50‐year return periods would exceed 165 and 195 mm, respectively, whereas the RX5DAY would exceed 270 and 320 mm for the same return periods. Furthermore, summer Southern Oscillation Index ( SOI ) positively impacted precipitation extremes in the Yellow River Basin and YRB , and autumn SOI negatively impacted the extremes of the next year in LB and YRB , while winter SOI negatively impacted the extremes of the next year in YRB . Additionally, the East Asia summer monsoon ( EASM ) and the South Asia summer monsoon ( SASM ) were both associated with precipitation extremes across China; however, EASM contributed more to these events than did the SASM .

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Soil Carbon Dioxide Fluxes from Three Forest Types of the Tropical Montane Rainforest on Hainan Island, China - Xinhua Jiang; Huai Chen; Changhui Peng; Yide Li; Yixin He; Dexiang Chen; Mingxian Lin; Ji Hu; Tianli Ma; Liangfeng Liu; Xinwei Liu; Miao Xia; et al. (Water, Air, & Soil Pollution, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Developing Single Nucleotide Polymorphism (SNP) Markers for the Identification of Coffee Germplasm - Lin Zhou; Fernando E. Vega; Huawei Tan; Aixa E. Ramírez Lluch; Lyndel W. Meinhardt; Wanping Fang; Sue Mischke; Brian Irish; Dapeng Zhang (Tropical Plant Biology, 2016)

Characterization and utilization of microsatellites in the Coffea canephora genome to assess genetic association between wild species in Kenya and cultivated coffee - Collins Ogutu; Ting Fang; Lin Yan; Lu Wang; Lifang Huang; Xiaoyang Wang; Baiquan Ma; Xianbao Deng; Albert Owiti; Aggrey Nyende; Yuepeng Han (Tree Genetics & Genomes, 2016)

Disentangling the effects of isolation-by-distance and isolation-by-environment on genetic differentiation among Rhododendron lineages in the subgenus Tsutsusi - Chun-Lin Huang; Jui-Hung Chen; Chung-Te Chang; Jeng-Der Chung; Pei-Chun Liao; Jenn-Che Wang; Shih-Ying Hwang (Tree Genetics & Genomes, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Large Deformation Analysis of a High Steep Slope Relating to the Laxiwa Reservoir, China - Peng Lin; Xiaoli Liu; Senying Hu; Pujian Li (Rock Mechanics and Rock Engineering, 2016)

Probabilistic Analysis of Earthquake-Led Water Contamination: A Case of Sichuan, China - Yan Yang; Lin Li; F. Benjamin Zhan; Yanhua Zhuang (Pure and Applied Geophysics, 2016)

Using high spatial resolution satellite imagery for mapping powdery mildew at a regional scale - Lin Yuan; Ruiliang Pu; Jingcheng Zhang; Jihua Wang; Hao Yang (Precision Agriculture, 2016)

Overexpression of SsDGAT2 from Sapium sebiferum (L.) Roxb Increases Seed Oleic Acid Level in Arabidopsis - YiQiang Wang; Dan Peng; Lin Zhang; XiaoFeng Tan; DeYi Yuan; XuanMing Liu; Bo Zhou (Plant Molecular Biology Reporter, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

A Multi-Functional Tumor Theranostic Nanoplatform for MRI Guided Photothermal-Chemotherapy - Jinjin Shi; Binghua Wang; Zhaoyang Chen; Wei Liu; Jingjing Pan; Lin Hou; Zhenzhong Zhang (Pharmaceutical Research, 2016)

Hybrid Electrospun Polycaprolactone Mats Consisting of Nanofibers and Microbeads for Extended Release of Dexamethasone - Kuan-Hui Hsu; Sheng-Po Fang; Chang-Lin Lin; Yan-Shin Liao; Yong-Kyu Yoon; Anuj Chauhan (Pharmaceutical Research, 2016)

Phosphofructokinase-1 Negatively Regulates Neurogenesis from Neural Stem Cells - Fengyun Zhang; Xiaodan Qian; Cheng Qin; Yuhui Lin; Haiyin Wu; Lei Chang; Chunxia Luo; Dongya Zhu (Neuroscience Bulletin, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Telomere length change plateaus at 4 years of age in Latino children: associations with baseline length and maternal change - Janet M. Wojcicki; Stephen Shiboski; Melvin B. Heyman; Deena Elwan; Jue Lin; Elizabeth Blackburn; Elissa Epel (Molecular Genetics and Genomics, 2016)

Different evolutionary patterns of SNPs between domains and unassigned regions in human protein-coding sequences - Erli Pang; Xiaomei Wu; Kui Lin (Molecular Genetics and Genomics, 2016)

Features of reversible P2Y12 receptor antagonists based on piperazinyl-glutamate-pyridines - Zhen Zhang; Guanzhong Wu; Chengqian Wang; Xiao Jin; Dong Li; Kejiang Lin (Medicinal Chemistry Research, 2016)

Tropical Storm Kyle (2002) and cold-air damming: their interactions and impacts on heavy rainfall in the Carolinas - Jose M. Garcia-Rivera; Yuh-Lang Lin; Yevgenii Rastigejev (Meteorology and Atmospheric Physics, 2016)

Functional Genomic Analysis of the Impact of Camelina (Camelina sativa) Meal on Atlantic Salmon (Salmo salar) Distal Intestine Gene Expression and Physiology - Tyler D. Brown; Tiago S. Hori; Xi Xue; Chang Lin Ye; Derek M. Anderson; Matthew L. Rise (Marine Biotechnology, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Manifold-Preserving Common Subspace Factorization for Feature Matching - Weidong Yan; ShaoJun Shi; Wei Lin; Lulu Pan; Jinhuan Wen (Journal of the Indian Society of Remote Sensing, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Expression Profiling of Several Gene Families Involved in Anthocyanin Biosynthesis in Apple (Malus domestica Borkh.) Skin During Fruit Development - Rui Meng; Juan Zhang; Lin An; Bohu Zhang; Xiaobing Jiang; Yazhou Yang; Zhengyang Zhao (Journal of Plant Growth Regulation, 2016)

Silicon Alleviates Cadmium Toxicity in Two Cypress Varieties by Strengthening the Exodermis Tissues and Stimulating Phenolic Exudation of Roots - Bin Guo; Chen Liu; Nengfei Ding; Qinglin Fu; Yicheng Lin; Hua Li; Ningyu Li (Journal of Plant Growth Regulation, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Using Free Navigation Reference Points and Prefabricated Bone Plates for Zygoma Fracture Model Surgeries - Tien-Hsiang Wang; Hsu Ma; Ching-Shiow Tseng; Yi-Hong Chou; Kun-Lin Cai (Journal of Medical and Biological Engineering, 2016)

Production of crocetin in transgenic Chlorella vulgaris expressing genes crtRB and ZCD1 - Sulin Lou; Liuying Wang; Lijuan He; Zhaokai Wang; Guangce Wang; Xiangzhi Lin (Journal of Applied Phycology, 2016)

De novo transcriptome analysis of carotenoid and polyunsaturated fatty acid metabolism in Rhodomonas sp. - Huanqin Li; Wenlei Wang; Zhaokai Wang; Xiangzhi Lin; Fang Zhang; Longhe Yang (Journal of Applied Phycology, 2016)

Copper(II) binding properties of hepcidin - Kanokwan Kulprachakarn; Yu-Lin Chen; Xiaole Kong; Maria C. Arno; Robert C. Hider; Somdet Srichairatanakool; Sukhvinder S. Bansal (JBIC Journal of Biological Inorganic Chemistry, 2016)

Identifying Antioxidant Proteins by Using Optimal Dipeptide Compositions - Pengmian Feng; Wei Chen; Hao Lin (Interdisciplinary Sciences: Computational Life Sciences, 2016)

The phytotoxic effects of selenium–mercury interactions on root growth in Brassica rapa (LvLing) - Zhi-Wei Bian; Jian Chen; Hui Li; Dan-Dan Liu; Li-Fei Yang; Yue-Lin Zhu; Wen-Li Zhu; Wei Liu; Zheng-Zheng Ying (Horticulture, Environment, and Biotechnology, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

Modelling the presence and identifying the determinant factors of dominant macroinvertebrate taxa in a karst river - Yuqing Lin; Qiuwen Chen; Kai Chen; Qingrui Yang (Environmental Monitoring and Assessment, 2016)

Emission and distribution of PCDD/Fs and CBzs from two co-processing RDF cement plants in China - Tong Chen; Ming-Xiu Zhan; Xiao-qing Lin; Ye-qing Li; Jiang Zhang; Xiao-Dong Li; Jian-hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Speciation of dissolved copper in human impacted freshwater and saltwater lakes - Deli Wang; Yaqin Gao; Katarina Larsson; Wenfang Lin (Environmental Science and Pollution Research, 2016)

Occurrence, spatial distribution, sources, and risks of polychlorinated biphenyls and heavy metals in surface sediments from a large eutrophic Chinese lake (Lake Chaohu) - Wei He; Ze-Lin Bai; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Sven Erik Jørgensen; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Pacificimonas aurantium sp. nov., Isolated from the Seawater of the Pacific Ocean - Shuhui Li; Wenchu Zhou; Dan Lin; Kai Tang; Nianzhi Jiao (Current Microbiology, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

Study on effects of endophytes on growth and production of Z-Ligustilide and ferulic acid in Angelica sinensis - Xin-Guo Zhang; Xiao-Ru Li; Qiang-Lin Wang; Wen-Na Wang; Xiao-Qian Chen (Brazilian Journal of Botany, 2016)

Reduced cortical thickness, surface area in patients with chronic obstructive pulmonary disease: a surface-based morphometry and neuropsychological study - Ji Chen; In-Tsang Lin; Haiyan Zhang; Jianzhong Lin; Shili Zheng; Ming Fan; Jiaxing Zhang (Brain Imaging and Behavior, 2016)

Full-length genomic characterization and molecular evolution of canine parvovirus in China - Ling Zhou; Qinghai Tang; Lijun Shi; Miaomiao Kong; Lin Liang; Qianqian Mao; Bin Bu; Lunguang Yao; Kai Zhao; Shangjin Cui; Élcio Leal (Virus Genes, 2016)

Major mutation events in structural genes of peste des petits ruminants virus through serial passages in vitro - Xiaodong Wu; Fuxiao Liu; Lin Li; Yanli Zou; Shan Liu; Zhiliang Wang (Virus Genes, 2016)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Evaluating Induced Fractures Between a Large Artificial Lake and an Aquifer-Coal Seam System: A Case Study in Tangshan Coal Mine, China - Donglin Dong; Gang Lin; Yu-Feng F. Lin; Mingdong Zhao; Kai Li (Mine Water and the Environment, 2016)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Paleoclimatic record from Chumbur-Kosa section in Sea of Azov region since Marine Isotope Stage 11 - Ye Liang; Tai-bao Yang; Andrey Aleksevitch Velichko; Biao Zeng; Pei-hong Shi; Lin-dong Wang; Yi He; Jie Chen; Yu Chen (Journal of Mountain Science, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Heat injury risk assessment for single-cropping rice in the middle and lower reaches of the Yangtze River under climate change - Lin Meng; Chunyi Wang; Jiquan Zhang (Journal of Meteorological Research, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Microsatellite analysis of the genetic relationships between wild and cultivated giant grouper in the South China Sea - QING WANG; XIANG WANG; ZHENZHEN XIE; YIQI LI; LING XIAO; CHENG PENG; HAIFA ZHANG; SHUISHENG LI; YONG ZHANG; HAORAN LIN (Journal of Genetics, 2016)

Fluid venting and seepage at accretionary ridges: the Four Way Closure Ridge offshore SW Taiwan - Ingo Klaucke; Christian Berndt; Gareth Crutchley; Wu-Cheng Chi; Saulwood Lin; Sina Muff (Geo-Marine Letters, 2016)

Molecular phylogenetic analysis of key Jatropha species inferred from nrDNA ITS and chloroplast (trnL-F and rbcL) sequences - Guo-ye Guo; Sheng-hua Wang; Ying Xu; Lin Tang; Mao-qun Yu; Fang Chen (Genes & Genomics, 2016)

Reconstructing rice phenology curves with frequency-based analysis and multi-temporal NDVI in double-cropping area in Jiangsu, China - Hongshuo Wang; Hui Lin; Darla K. Munroe; Xiaodong Zhang; Pengfei Liu (Frontiers of Earth Science, 2016)

Characterization of the whole chloroplast genome sequence of Acer davidii Franch (Aceraceae) - Yun Jia; Jiao Yang; Yan-Ling He; Ying He; Chuan Niu; Lin-Lin Gong; Zhong-Hu Li (Conservation Genetics Resources, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

A novel dengue virus serotype 1 vaccine candidate based on Japanese encephalitis virus vaccine strain SA14-14-2 as the backbone - Huiqiang Yang; Zhushi Li; Hua Lin; Wei Wang; Jian Yang; Lina Liu; Xianwu Zeng; Yonglin Wu; Yongxin Yu; Yuhua Li (Archives of Virology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Sedimentary facies and sequence stratigraphy of the Silurian at Tabei uplift, Tarim Basin, China - Jianhua Zhao; Changsong Lin; Jingyan Liu; Haijun Yang; Zhenzhong Cai (Arabian Journal of Geosciences, 2016)

Gray algebraic curve model-based roof separation prediction method for the warning of roof fall accidents - Jian-Lin Xie; Jia-Lin Xu; Wei-Bing Zhu (Arabian Journal of Geosciences, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Genetic diversity analysis of Jatropha curcas L. accessions cultivated in Taiwan using inter simple sequence repeats (ISSR) markers - Celimphilo Mavuso; Yong-Pei Wu; Fure-Chyi Chen; Bing-Hong Huang; Su-Ju Lin (Agroforestry Systems, 2016)

Site-related and seasonal variation of bioaerosol emission in an indoor wastewater treatment station: level, characteristics of particle size, and microbial structure - Wenjie Ding; Lin Li; Yunping Han; Jianzhong Liu; Junxin Liu (Aerobiologia, 2016)

A double-index method to classify Kuroshio intrusion paths in the Luzon Strait - Zhida Huang; Hailong Liu; Jianyu Hu; Pengfei Lin (Advances in Atmospheric Sciences, 2016)

Microbial community structure of Arctic seawater as revealed by pyrosequencing - Yang Li; Zhen Wang; Xuezheng Lin (Acta Oceanologica Sinica, 2016)

Spatial structure and seasonal changes of nekton assemblages in the Taiwan Strait - Puqing Song; Longshan Lin; Yuan Li; Zhihui Zhong (Acta Oceanologica Sinica, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

A novel pathogenic bacteria ( Vibrio fortis ) causing enteritis in cultured seahorses, Hippocampus erectus Perry, 1810 - X Wang; Y Zhang; G Qin; W Luo; Q Lin (Journal of Fish Diseases, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Proteomic Analysis of Mechanisms Responsible for the Waterless Preservation of Fenneropenaeus chinensis Based on Cold-Forced Hibernation - Hong-bo Mi; Jingxin Chen; Xiaorong Hou; Lin-Chun Mao (Journal of Aquatic Food Product Technology, 2016)

Efficacy of a Fructus mume Extract Combination with Stable Chlorine in Preventing Bacterial Contamination in Frozen Mackerel ( Scomber japonicus ) Fillets - Bin Zhang; Hui-min Lin; Yan Tang; Shang-gui Deng (Journal of Aquatic Food Product Technology, 2016)

Extracting Protein from Antarctic Krill ( Euphausia superba ) - Xiang-Ming Qi; E. Liao; Lu Wang; Hong Lin; Chang-Hu Xue (Journal of Aquatic Food Product Technology, 2016)

Estimation of winter wheat phenology under the influence of cumulative temperature and soil salinity in the Yellow River Delta, China, using MODIS time-series data - Lin Chu; Chong Huang; Qing-sheng Liu; Gao-huan Liu (International Journal of Remote Sensing, 2016)

Fingerprint analysis and multi-component determination of Zibu Piyin recipe by HPLC with DAD and Q-TOF/MS method - Hong Xiang; Huiying Xu; Libin Zhan; Lin Zhang (Natural Product Research, 2016)

Multivariate Copula-Based Joint Probability Distribution of Water Supply and Demand in Irrigation District - Jinping Zhang; Xiaomin Lin; Bingtuo Guo (Water Resources Management, 2016)

Distribution and haplotype diversity of WKS resistance genes in wild emmer wheat natural populations - Lin Huang; Hanan Sela; Lihua Feng; Qijiao Chen; Tamar Krugman; Jun Yan; Jorge Dubcovsky; Tzion Fahima (Theoretical and Applied Genetics, 2016)

Turbulent transfer coefficient and roughness length in a high-altitude lake, Tibetan Plateau - Zhaoguo Li; Shihua Lyu; Lin Zhao; Lijuan Wen; Yinhuan Ao; Shaoying Wang (Theoretical and Applied Climatology, 2016)

A retrospective study of the occurrence of ischemic-type biliary lesions post liver transplantation - Rui Shi; Ya-Min Zhang; Yong-Lin Deng; Hong Zheng; Cheng Pan; Zhong-Yang Shen (Science China Life Sciences, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

Structure of summer atmospheric boundary layer in the center of Arctic Ocean and its relation with sea ice extent change - LinGen Bian; MingHu Ding; Xiang Lin; ChangGui Lu; ZhiQiu Gao (Science China Earth Sciences, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Transcriptomic analysis of the succulent xerophyte Zygophyllum xanthoxylum in response to salt treatment and osmotic stress - Qing Ma; Ai-Ke Bao; Wei-Wei Chai; Wen-Ying Wang; Jin-Lin Zhang; Yi-Xiao Li; Suo-Min Wang (Plant and Soil, 2016)

Molecular cloning and expression of 1-deoxy-d-xylulose-5-phosphate synthase and 1-deoxy-d-xylulose-5-phosphate reductoisomerase in Dendrobium officinale - Honghong Fan; Qiuju Wu; Xiang Wang; Linsong Wu; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Physiological controls of chrysanthemum DgD27 gene expression in regulation of shoot branching - Chao Wen; Qingcui Zhao; Jing Nie; Guoqin Liu; Lin Shen; Chenxia Cheng; Lin Xi; Nan Ma; Liangjun Zhao (Plant Cell Reports, 2016)

Nitrogen balances and nitrogen-use efficiency of different organic and conventional farming systems - Hung-Chun Lin; Julia A. Huber; Georg Gerl; Kurt-Jürgen Hülsbergen (Nutrient Cycling in Agroecosystems, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

Calcitriol regulates angiotensin-converting enzyme and angiotensin converting-enzyme 2 in diabetic kidney disease - Mei Lin; Ping Gao; Tianya Zhao; Lei He; Mengshi Li; Yaoyao Li; Hua Shui; Xiaoyan Wu (Molecular Biology Reports, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Genetic Variants of VEGF (rs201963 and rs3025039) and KDR (rs7667298, rs2305948, and rs1870377) Are Associated with Glioma Risk in a Han Chinese Population: a Case-Control Study - Jiannan Zhang; Jian Yang; Yuqing Chen; Qin Mao; Shanquan Li; Wenhao Xiong; Yingying Lin; Jie Chen; Jianwei Ge (Molecular Neurobiology, 2016)

Paraquat Induces Cell Death Through Impairing Mitochondrial Membrane Permeability - Chuen-Lin Huang; Chih-Chang Chao; Yi-Chao Lee; Mei-Kuang Lu; Jing-Jy Cheng; Ying-Chen Yang; Vin-Chi Wang; Wen-Chang Chang; Nai-Kuei Huang (Molecular Neurobiology, 2016)

Association Between PARP1 Single Nucleotide Polymorphism and Brain Tumors - Hong Wang; Kun Zhang; Haifeng Qin; Lin Yang; Liyu Zhang; Yanyan Cao (Molecular Neurobiology, 2016)

Discovery of Influenza A virus neuraminidase inhibitors using support vector machine and Naïve Bayesian models - Wenwen Lian; Jiansong Fang; Chao Li; Xiaocong Pang; Ai-Lin Liu; Guan-Hua Du (Molecular Diversity, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Long-term effects of biochar amount on the content and composition of organic matter in soil aggregates under field conditions - Xinliang Dong; Tianyu Guan; Guitong Li; Qimei Lin; Xiaorong Zhao (Journal of Soils and Sediments, 2016)

Biological and pathological activities of interleukin-22 - Mirna Perusina Lanfranca; Yanwei Lin; Jingyuan Fang; Weiping Zou; Timothy Frankel (Journal of Molecular Medicine, 2016)

Galectin-3 suppresses mucosal inflammation and reduces disease severity in experimental colitis - Hwei-Fang Tsai; Chien-Sheng Wu; Yi-Lin Chen; Hsiu-Jung Liao; I-Tsu Chyuan; Ping-Ning Hsu (Journal of Molecular Medicine, 2016)

Meta-Analysis of the Efficiency and Prognosis of Intracranial Aneurysm Treated with Flow Diverter Devices - Gengfan Ye; Meng Zhang; Lin Deng; Xiaohui Chen; Yunyan Wang (Journal of Molecular Neuroscience, 2016)

Serotonin Receptor 2B Mediates Mechanical Hyperalgesia by Regulating Transient Receptor Potential Vanilloid 1 - Yeu-Shiuan Su; Yuan-Yi Chiu; Shih-Yuan Lin; Chih-Cheng Chen; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2016)

A Fluorescence Turn-On Probe for Thiols with a Tunable Dynamic Range - Qian Li; Rui Guo; Weiying Lin (Journal of Fluorescence, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Changes in the activities of starch metabolism enzymes in rice grains in response to elevated CO2 concentration - Li-Yong Xie; Er-Da Lin; Hong-Liang Zhao; Yong-Xiang Feng (International Journal of Biometeorology, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Pediastrum sensu lato (Chlorophyceae) assemblages from surface sediments of lakes and ponds on the Tibetan Plateau - Falko Turner; Liping Zhu; Xinmiao Lü; Ping Peng; Qingfeng Ma; Junbo Wang; Juzhi Hou; Qiuqi Lin; Ruimin Yang; Peter Frenzel (Hydrobiologia, 2016)

Macrobenthos in the central Arabian Gulf: a reflection of climate extremes and variability - Chih-Lin Wei; Gilbert T. Rowe; Mohsin Al-Ansi; Ibrahim Al-Maslamani; Yousria Soliman; Nehad Nour El-Din; Ibrahim S. Al-Ansari; Ismail Al-Shaikh; Antonietta Quigg; Clifton Nunnally; Mohamed A. Abdel-Moati (Hydrobiologia, 2016)

Molecular analysis of type II topoisomerases of Aeromonas hydrophila isolated from fish and levofloxacin-induced resistant isolates in vitro - Ruixue Hu; Na Du; Nan Chen; Li Lin; Yanhua Zhai; Zemao Gu (Folia Microbiologica, 2016)

Reconstructing cephalopod migration with statolith elemental signatures: a case study using Dosidicus gigas - Bi Lin Liu; Jie Cao; Samuel B. Truesdell; Yong Chen; Xin Jun Chen; Si Quan Tian (Fisheries Science, 2016)

Spatial distribution and risk assessment of heavy metals and As pollution in the sediments of a shallow lake - Jiancai Deng; Yuansheng Wang; Xin Liu; Weiping Hu; Jinge Zhu; Lin Zhu (Environmental Monitoring and Assessment, 2016)

Dielectric barrier discharge plasma induced degradation of aqueous atrazine - Jingwei Feng; Lin Jiang; Dan Zhu; Kuizu Su; Dayong Zhao; Jibiao Zhang; Zheng Zheng (Environmental Science and Pollution Research, 2016)

No-tillage effects on N and P exports across a rice-planted watershed - Xinqiang Liang; Zhibo Wang; Yixiang Zhang; Chunyan Zhu; Limin Lin; Lixian Xu (Environmental Science and Pollution Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Trace elements are associated with urinary 8-hydroxy-2′-deoxyguanosine level: a case study of college students in Guangzhou, China - Shaoyou Lu; Lu Ren; Jianzhang Fang; Jiajia Ji; Guihua Liu; Jianqing Zhang; Huimin Zhang; Ruorong Luo; Kai Lin; Ruifang Fan (Environmental Science and Pollution Research, 2016)

Residential cancer cluster investigation nearby a Superfund Study Area with trichloroethylene contamination - David J. Press; Meg McKinley; Dennis Deapen; Christina A. Clarke; Scarlett Lin Gomez (Cancer Causes & Control, 2016)

Resting State fMRI Demonstrates a Disturbance of the Cerebello-Cortical Circuit in Essential Tremor - Wenjie Yin; Wei Lin; Wenbo Li; Shusen Qian; Xin Mou (Brain Topography, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Interpreting sedimentation dynamics at Longxi catchment in the Three Gorges Area, China, using Cs-137 activity, particle size and rainfall erosivity - Jin-zhang Gao; Yi Long; Xin-bao Zhang; Adrian L. Collins; Xiu-bin He; Yun-qi Zhang; Zhong-lin Shi (Journal of Mountain Science, 2016)

Discovery of genes associated with cadmium accumulation from gill of scallop Chlamys farreri based on high-throughput sequencing - Hui Zhang; Yuxiu Zhai; Lin Yao; Yanhua Jiang; Fengling Li (Genes & Genomics, 2016)

Identification and characteristics analysis of toll-like receptors family genes in yak - Daoliang Lan; Baoshan Lin; Xianrong Xiong; Xiaonong Yang; Jian Li (Genes & Genomics, 2016)

Highly distinct chromosomal structures in cowpea (Vigna unguiculata), as revealed by molecular cytogenetic analysis - Aiko Iwata-Otsubo; Jer-Young Lin; Navdeep Gill; Scott A. Jackson (Chromosome Research, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Peptide Regulation of Skin Fibroblast Functions during Their Aging In Vitro - N. S. Lin’kova; A. O. Drobintseva; O. A. Orlova; E. P. Kuznetsova; V. O. Polyakova; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2016)

lncRNA DANCR suppresses odontoblast-like differentiation of human dental pulp cells by inhibiting wnt/β-catenin pathway - Lingling Chen; Zhi Song; Shuheng Huang; Runfu Wang; Wei Qin; Jia Guo; Zhengmei Lin (Cell and Tissue Research, 2016)

miR-138-1* regulates aflatoxin B1-induced malignant transformation of BEAS-2B cells by targeting PDK1 - Yun Wang; Zhan Zhang; Huanqiang Wang; Yudong Zhang; Minghui Ji; Hengsen Xu; Chao Wang; Zhenzhen Sun; Weimin Gao; Shou-Lin Wang (Archives of Toxicology, 2016)

Mitochondrial permeability transition and its regulatory components are implicated in apoptosis of primary cultures of rat proximal tubular cells exposed to lead - Gang Liu; Zhong-Kun Wang; Zhen-Yong Wang; Du-Bao Yang; Zong-Ping Liu; Lin Wang (Archives of Toxicology, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Albedo of coastal landfast sea ice in Prydz Bay, Antarctica: Observations and parameterization - Qinghua Yang; Jiping Liu; Matti Leppäranta; Qizhen Sun; Rongbin Li; Lin Zhang; Thomas Jung; Ruibo Lei; Zhanhai Zhang; Ming Li; Jiechen Zhao; Jingjing Cheng (Advances in Atmospheric Sciences, 2016)

Association between Arctic autumn sea ice concentration and early winter precipitation in China - Na Liu; Lina Lin; Bin Kong; Yingjie Wang; Zhanhai Zhang; Hongxia Chen (Acta Oceanologica Sinica, 2016)

Environmental switching during biofilm development in a cold seep system and functional determinants of species sorting - Weipeng Zhang; Renmao Tian; Yang Bo; Huiluo Cao; Lin Cai; Lianguo Chen; Guowei Zhou; Jin Sun; Xixiang Zhang; Abdulaziz Al‐Suwailem; Pei‐Yuan Qian (Molecular Ecology, 2016)
The functional basis for species sorting theory remains elusive, especially for microbial community assembly in deep‐sea environments. Using artificial surface‐based biofilm models, our recent work revealed taxonomic succession during biofilm development in a newly defined cold seep system, the Thuwal cold seeps II, which comprises a brine pool and the adjacent normal bottom water (NBW) to form a metacommunity via the potential immigration of organisms from one patch to another. Here, we designed an experiment to investigate the effects of environmental switching between the brine pool and the NBW on biofilm assembly, which could reflect environmental filtering effects during bacterial immigration to new environments. Analyses of 16S rRNA genes of 71 biofilm samples suggested that the microbial composition of biofilms established in new environments was determined by both the source community and the incubation conditions. Moreover, a comparison of 18 metagenomes provided evidence for biofilm community assembly that was based primarily on functional features rather than taxonomic identities; metal ion resistance and amino acid metabolism were the major species sorting determinants for the succession of biofilm communities. Genome binning and pathway reconstruction of two bacterial species ( Marinobacter sp. and Oleispira sp.) further demonstrated metal ion resistance and amino acid metabolism as functional traits conferring the survival of habitat generalists in both the brine pool and NBW. The results of this study shed new light on microbial community assembly in special habitats and bridge a gap in species sorting theory.

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Mass accumulation rate and monsoon records from Xifeng, Chinese Loess Plateau, based on a luminescence age model - Thomas Stevens; Jan‐Pieter Buylaert; Huayu Lu; Christine Thiel; Andrew Murray; Manfred Frechen; Shuangwen Yi; Lin Zeng (Journal of Quaternary Science, 2016)
Luminescence dating of loess accumulation in China has raised questions over disturbance and gaps in the record, the magnitude of mass accumulation rates (MARs), and monsoon forcing mechanisms. Here we present a detailed quartz optically stimulated luminescence (OSL) chronology from the Xifeng Chinese Loess Plateau site. We reconstruct MARs and construct an age model for monsoon proxies at the site. The luminescence ages show significant pedogenic and anthropogenic disturbance in material deposited after ca. 20–22 ka. Analysis of other published data suggests that this disturbance may be more common than previously realized. MARs from undisturbed portions of Xifeng vary dramatically, with peaks potentially matching the timing of Heinrich events. The last glacial maximum peak MAR (22–27 ka) matches the Pacific and Greenland dust flux records, although appears earlier than peak MARs seen in many other OSL‐dated Loess Plateau sites. East Asian monsoon grain‐size and magnetic susceptibility records also show several differences between independently dated loess sites. This complicates our understanding of any lag between insolation forcing and monsoon response. Nevertheless, the Xifeng climate proxy changes show apparent broad agreement with the timing of Heinrich events in the North Atlantic, supporting assertions of a climatic teleconnection between the two areas.

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Did a Miocene–Pliocene island isolation sequence structure diversification of funnel web spiders in the Taiwan‐Ryukyu Archipelago? - Yong‐Chao Su; Rafe M. Brown; Yung‐Hau Chang; Chung‐Ping Lin; I‐Min Tso (Journal of Biogeography, 2016)
Aim We tested the competing hypotheses concerning the relative importance of Pleistocene versus Miocene–Pliocene geological events for the formation of endemism in an Asian archipelago using the Macrothele taiwanensis (Hexathelidae) species group. Location Taiwan‐Ryukyu Archipelago. Methods We estimated phylogenetic trees from cytochrome oxidase I subunit ( COI ) and 16S rRNA ( 16S ) gene regions and employed Bayesian ancestral range reconstructions to investigate previously debated models of lineage diversification in the Taiwan‐Ryukyu Archipelago. To evaluate alternative geological timeframes for their importance in shaping the genetic structure of funnel web spiders, we used five time calibration schemes to estimate timing of divergence, infer ancestral distributions, and to reconstruct historical demographic changes in each lineage. We tested taxonomic boundaries with two species delimitation procedures. Results Our results indicate a north‐to‐south isolation sequence of the M. taiwanensis group: the Amami lineage diverged first, then Yaeyama, and finally the Taiwanese lineages. Divergence time estimation and population demographic change analyses indicate that Pleistocene climate fluctuations minimally impacted the genetic structure of these spiders. Instead, estimated divergence events correspond to Miocene–Pliocene geological events, strongly supporting a much older timeframe for diversification. The results of species delimitation analyses coincide well with morphological differences observed among the island populations, reinforcing inferred species boundaries, and at least three potential cryptic species were statistically detected within Taiwan. Main conclusions Miocene–Pliocene geological events appear to have contributed disproportionately to diversification in the M. taiwanensis species group. The clear association between geographical area, genetic structure and statistical species delimitation strongly supports an interpretation of allopatric speciation. We advocate comparing our results with those derived from additional study organisms with similar life histories to further explore the Miocene–Pliocene diversification hypothesis.

Unchanged carbon balance driven by equivalent responses of production and respiration to climate change in a mixed‐grass prairie - Xia Xu; Zheng Shi; Xuecheng Chen; Yang Lin; Shuli Niu; Lifen Jiang; Ruiseng Luo; Yiqi Luo (Global Change Biology, 2016)
Responses of grassland carbon (C) cycling to climate change and land use remain a major uncertainty in model prediction of future climate. To explore the impacts of global change on ecosystem C fluxes and the consequent changes in C storage, we have conducted a field experiment with warming (+3 °C), altered precipitation (doubled and halved), and annual clipping at the end of growing seasons in a mixed‐grass prairie in Oklahoma, USA , from 2009 to 2013. Results showed that although ecosystem respiration ( ER ) and gross primary production ( GPP ) negatively responded to warming, net ecosystem exchange of CO 2 ( NEE ) did not significantly change under warming. Doubled precipitation stimulated and halved precipitation suppressed ER and GPP equivalently, with the net outcome being unchanged in NEE . These results indicate that warming and altered precipitation do not necessarily have profound impacts on ecosystem C storage. In addition, we found that clipping enhanced NEE due to a stronger positive response of GPP compared to ER , indicating that clipping could potentially be an effective land practice that could increase C storage. No significant interactions between warming, altered precipitation, and clipping were observed. Meanwhile, we found that belowground net primary production ( BNPP ) in general was sensitive to climate change and land use though no significant changes were found in NPP across treatments. Moreover, negative correlations of the ER / GPP ratio with soil temperature and moisture did not differ across treatments, highlighting the roles of abiotic factors in mediating ecosystem C fluxes in this grassland. Importantly, our results suggest that belowground C cycling (e.g., BNPP ) could respond to climate change with no alterations in ecosystem C storage in the same period.

How does habitat filtering affect the detection of conspecific and phylogenetic density dependence? - Junjie Wu; Nathan G. Swenson; Calum Brown; Caicai Zhang; Jie Yang; Xiuqin Ci; Jie Li; Liqing Sha; Min Cao; Luxiang Lin (Ecology, 2016)
Conspecific negative density dependence ( CNDD ) has been recognized as a key mechanism underlying species coexistence, especially in tropical forests. Recently, some studies have reported that seedling survival is also negatively correlated with the phylogenetic relatedness between neighbors and focal individuals, termed phylogenetic negative density dependence ( PNDD ). In contrast to CNDD or PNDD , shared habitat requirements between closely related individuals are thought to be a cause of observed positive effects of closely related neighbors, which may affect the strength and detectability of CNDD or PNDD . In order to investigate the relative importance of these mechanisms for tropical tree seedling survival, we used generalized linear mixed models to analyze how the survival of more than 10 000 seedlings of woody plant species related to neighborhood and habitat variables in a tropical rainforest in southwest China. By comparing models with and without habitat variables, we tested how habitat filtering affected the detection of CNDD and PNDD . The best‐fitting model suggested that CNDD and habitat filtering played key roles in seedling survival, but that, contrary to our expectations, phylogenetic positive density dependence ( PPDD ) had a distinct and important effect. While habitat filtering affected the detection of CNDD by decreasing its apparent strength, it did not explain the positive effects of closely related neighbors. Our results demonstrate that a failure to control for habitat variables and phylogenetic relationships may obscure the importance of conspecific and heterospecific neighbor densities for seedling survival.

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

Experimental study of drained anisotropy of granular soils involving rotation of principal stress direction - Huan Xiong; Lin Guo; Yuanqiang Cai; Zhongxuan Yang (European Journal of Environmental and Civil Engineering, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Asymmetric synthesis and biological activities of natural product (+)-balasubramide and its derivatives - Jun Li; Jianzu Li; Yuan Xu; Yunjie Wang; Luyong Zhang; Li Ding; Yining Xuan; Tao Pang; Hansen Lin (Natural Product Research, 2016)

Lasiodiplodins from mangrove endophytic fungus Lasiodiplodia sp. 318# - Jing Li; Yanyu Xue; Jie Yuan; Yongjun Lu; Xun Zhu; Yongcheng Lin; Lan Liu (Natural Product Research, 2016)

Comparison of MERIS, MODIS, SeaWiFS-derived particulate organic carbon, and in situ measurements in the South China Sea - S.B. Hu; W.X. Cao; G.F. Wang; Z.T. Xu; J. F. Lin; W.J. Zhao; Y.Z. Yang; W. Zhou; Z.H. Sun; L.J. Yao (International Journal of Remote Sensing, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Impact of previous one-step variation in positively long-range correlated processes - Zuntao Fu; Fenghua Xie; Naiming Yuan; Lin Piao (Theoretical and Applied Climatology, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

Experimental Investigation on Dilation Mechanisms of Land-Facies Karamay Oil Sand Reservoirs under Water Injection - Botao Lin; Yan Jin; Huiwen Pang; Amy B. Cerato (Rock Mechanics and Rock Engineering, 2016)

Modified Formula for the Tensile Strength as Obtained by the Flattened Brazilian Disk Test - Hang Lin; Wei Xiong; Qixiang Yan (Rock Mechanics and Rock Engineering, 2016)

Escitalopram reversed the traumatic stress-induced depressed and anxiety-like symptoms but not the deficits of fear memory - Chen-Cheng Lin; Che-Se Tung; Yia-Ping Liu (Psychopharmacology, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Molecular diversity of microbial eukaryotes in sea water from Fildes Peninsula, King George Island, Antarctica - Wei Luo; Huirong Li; Shengquan Gao; Yong Yu; Ling Lin; Yinxin Zeng (Polar Biology, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Wall stretch and thromboxane A2 activate NO synthase (eNOS) in pulmonary arterial smooth muscle cells via H2O2 and Akt-dependent phosphorylation - Hae Jin Kim; Hae Young Yoo; Ji Hyun Jang; Hai Yue Lin; Eun Yeong Seo; Yin Hua Zhang; Sung Joon Kim (Pflügers Archiv - European Journal of Physiology, 2016)

Changes in phosphorus use and losses in the food chain of China during 1950–2010 and forecasts for 2030 - Zhaohai Bai; Lin Ma; Wenqi Ma; Wei Qin; Gerard L. Velthof; Oene Oenema; Fusuo Zhang (Nutrient Cycling in Agroecosystems, 2016)

GluR2-3Y Inhibits the Acquisition and Reinstatement of Morphine-Induced Conditioned Place Preference in Rats - Xiao-Jing Lin; Jian-Jun Zhang; Long-Chuan Yu (Neuroscience Bulletin, 2016)

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Identification of cell types, tissues and pathways affected by risk loci in psoriasis - Yan Lin; Pan Zhao; Changbing Shen; Songke Shen; Xiaodong Zheng; Xianbo Zuo; Sen Yang; Xuejun Zhang; Xianyong Yin (Molecular Genetics and Genomics, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Minocycline Attenuates Neonatal Germinal-Matrix-Hemorrhage-Induced Neuroinflammation and Brain Edema by Activating Cannabinoid Receptor 2 - Jun Tang; Qianwei Chen; Jing Guo; Liming Yang; Yihao Tao; Lin Li; Hongping Miao; Hua Feng; Zhi Chen; Gang Zhu (Molecular Neurobiology, 2016)

Serum Uric Acid Levels and Outcomes After Acute Ischemic Stroke - Zhongchao Wang; Yanlin Lin; Yuxiu Liu; Ying Chen; Bin Wang; Changgui Li; Shengli Yan; Yangang Wang; Wenjuan Zhao (Molecular Neurobiology, 2016)

Spatial and Age-Dependent Hair Cell Generation in the Postnatal Mammalian Utricle - Zhen Gao; Michael C. Kelly; Dehong Yu; Hao Wu; Xi Lin; Fang-lu Chi; Ping Chen (Molecular Neurobiology, 2016)

Major zircon megacryst suites of the Indo-Pacific lithospheric margin (ZIP) and their petrogenetic and regional implications - Lin Sutherland; Ian Graham; Gregory Yaxley; Richard Armstrong; Gaston Giuliani; Paul Hoskin; Victor Nechaev; Jon Woodhead (Mineralogy and Petrology, 2016)

Predicted structure of MIF/CD74 and RTL1000/CD74 complexes - Roberto Meza-Romero; Gil Benedek; Lin Leng; Richard Bucala; Arthur A. Vandenbark (Metabolic Brain Disease, 2016)

Long-term variations of estimated global solar radiation and the influencing factors in Hunan province, China during 1980–2013 - Ling Zou; Aiwen Lin; Lunche Wang; Xiangao Xia; Wei Gong; Hongji Zhu; Zhenzhen Zhao (Meteorology and Atmospheric Physics, 2016)

Millennium recurrence interval of morphogenic earthquakes on the Qingchuan fault, northeastern segment of the Longmen Shan Thrust Belt, China - Aiming Lin; Bing Yan; Gang Rao (Journal of Seismology, 2016)

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Molecular characterization of FLOWERING LOCUS T(FT)genes from bamboo (Phyllostachys violascens) - Xiaoqin Guo; Yi Wang; Qian Wang; Zaien Xu; Xinchun Lin (Journal of Plant Biochemistry and Biotechnology, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

PRL-3 promotes gastric cancer migration and invasion through a NF-κB-HIF-1α-miR-210 axis - Cheng Zhang; Wei Tian; Lin Meng; Like Qu; Chengchao Shou (Journal of Molecular Medicine, 2016)

MiR-93 Targeting EphA4 Promotes Neurite Outgrowth from Spinal Cord Neurons - Xiaogang Chen; Huilin Yang; Xiaoqing Zhou; Lin Zhang; Xiaoqing Lu (Journal of Molecular Neuroscience, 2016)

Ameliorative effects of Qingfei Tongluo formula on experimental mycoplasmal pneumonia in mice - Yong-hong Jiang; Jian-er Yu; Ai-hua Guo; Xiao Li; Yan Lin; Zhi-yan Jiang; Zhen Xiao (Journal of Natural Medicines, 2016)

Development of Home-Based Frailty Detection Device Using Wireless Sensor Networks - Chung-Chih Lin; Chun-Chang Chen; Pay-Shin Lin; Ren-Guey Lee; Jing-Siang Huang; Tsai-Hsuan Tsai; Yu-Chuan Chang (Journal of Medical and Biological Engineering, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

On the timing and forcing mechanism of a mid-Miocene arid climate transition at the NE margins of the Tibetan Plateau: stratigraphic and sedimentologic evidence from the Sikouzi Section - Xiubin Lin; Karl-Heinz Wyrwoll; Hanlin Chen; Xiaogan Cheng (International Journal of Earth Sciences, 2016)

Detrital zircon U–Pb geochronology of the Siwalik Group of the Nepal Himalaya: implications for provenance analysis - Upendra Baral; Ding Lin; Deepak Chamlagain (International Journal of Earth Sciences, 2016)

MicroRNA-29 regulates high-glucose-induced apoptosis in human retinal pigment epithelial cells through PTEN - Xiaohui Lin; Xiyuan Zhou; Danning Liu; Lixia Yun; Lina Zhang; Xiaohai Chen; Qinghe Chai; Langen Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Low BIK outside-inside-out interactive inflammation immune-induced transcription-dependent apoptosis through FUT3-PMM2-SQSTM1-SFN-ZNF384 - Juxiang Huang; Lin Wang; Minghu Jiang; Qingchun Chen; Xiaoyu Zhang; Yangming Wang; Zhenfu Jiang; Zhongjie Zhang (Immunologic Research, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Sequences analyses and expression profiles in tissues and embryos of Japanese flounder (Paralichthys olivaceus) PRDM1 - Conghui Liu; Wei Liu; Lin Fan; Jinxiang Liu; Peizhen Li; Wei Zhang; Jinning Gao; Zan Li; Quanqi Zhang; Xubo Wang (Fish Physiology and Biochemistry, 2016)

Species-specific and generic biomass equations for seedlings and saplings of European tree species - Peter Annighöfer; Aitor Ameztegui; Christian Ammer; Philippe Balandier; Norbert Bartsch; Andreas Bolte; Lluís Coll; Catherine Collet; Jörg Ewald; Nico Frischbier; Tsegay Gebereyesus; Josephine Haase; et al. (European Journal of Forest Research, 2016)

Evaluating the primary and ready biodegradability of dianilinodithiophosphoric acid - Weixiong Lin; Shuiyu Sun; Pingting Xu; Yongkang Dai; Jie Ren (Environmental Monitoring and Assessment, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

Degradation of benzophenone-3 by the ozonation in aqueous solution: kinetics, intermediates and toxicity - Yang Guo; Qiaoxin Lin; Bingbing Xu; Fei Qi (Environmental Science and Pollution Research, 2016)

Soil washing in combination with homogeneous Fenton-like oxidation for the removal of 2,4,4′-trichlorodiphenyl from soil contaminated with capacitor oil - Xiao-Hong Ma; Ling Zhao; Zhi-Rong Lin; Yuan-Hua Dong (Environmental Science and Pollution Research, 2016)

Vermicomposting of sludge from animal wastewater treatment plant mixed with cow dung or swine manure using Eisenia fetida - Dan Xie; Weibing Wu; Xiaoxia Hao; Dongmei Jiang; Xuewei Li; Lin Bai (Environmental Science and Pollution Research, 2016)

Effects of dicyandiamide and dolomite application on N2O emission from an acidic soil - Muhammad Shaaban; Yupeng Wu; Qi-an Peng; Shan Lin; Yongliang Mo; Lei Wu; Ronggui Hu; Wei Zhou (Environmental Science and Pollution Research, 2016)

Erratum to: The Topographic Design of River Channels for Form-Process Linkages - Rocko A. Brown; Gregory B. Pasternack; Tin Lin (Environmental Management, 2016)

The Topographic Design of River Channels for Form-Process Linkages - Rocko A. Brown; Gregory B. Pasternack; Tin Lin (Environmental Management, 2016)

Characteristics, sources and health risk assessment of toxic heavy metals in PM2.5 at a megacity of southwest China - Youping Li; Zhisheng Zhang; Huifang Liu; Hong Zhou; Zhongyu Fan; Mang Lin; Dalei Wu; Beicheng Xia (Environmental Geochemistry and Health, 2016)

Identification and Evaluation of Reliable Reference Genes in the Medicinal Fungus Shiraia bambusicola - Liang Song; Tong Li; Li Fan; Xiao-Ye Shen; Cheng-Lin Hou (Current Microbiology, 2016)

Aesthetic preference recognition of 3D shapes using EEG - Lin Hou Chew; Jason Teo; James Mountstephens (Cognitive Neurodynamics, 2016)

Regeneration of cerium(IV) in different spent chromium-etching solutions collected from thin-film transistor liquid crystal display manufacturing factories - Kuo-Lin Huang; Te-San Chen; Ren-Wei Tsai; Yu-Syuan Chen (Clean Technologies and Environmental Policy, 2016)

Cloning and expression analysis of betalain biosynthesis genes in Amaranthus tricolor - Xueli Zheng; Shengcai Liu; Chunzhen Cheng; Rongfang Guo; Yukun Chen; Liyang Xie; Yuyuan Mao; Yuling Lin; Zihao Zhang; Zhongxiong Lai (Biotechnology Letters, 2016)

Interactions of early adversity with stress-related gene polymorphisms impact regional brain structure in females - Arpana Gupta; Jennifer Labus; Lisa A. Kilpatrick; Mariam Bonyadi; Cody Ashe-McNalley; Nuwanthi Heendeniya; Sylvie Bradesi; Lin Chang; Emeran A. Mayer (Brain Structure and Function, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Manganese elevates manganese superoxide dismutase protein level through protein kinase C and protein tyrosine kinase - Sufen Li; Lin Lu; Xiudong Liao; Tianquan Gao; Funing Wang; Liyang Zhang; Lin Xi; Songbai Liu; Xugang Luo (BioMetals, 2016)

Incorporation of zinc into the coccoliths of the microalga Emiliania huxleyi - Giulia Santomauro; Wei-Lin Sun; Franz Brümmer; Joachim Bill (BioMetals, 2016)

Complete mitochondrial genomes render the Night Heron genus Gorsachius non-monophyletic - Xiaoping Zhou; Chengte Yao; Qingxian Lin; Wenzhen Fang; Xiaolin Chen (Journal of Ornithology, 2016)

Heterologous expression of two Physcomitrella patens group 3 late embryogenesis abundant protein (LEA3) genes confers salinity tolerance in arabidopsis - Jing Du; Lei Wang; Xiaochen Zhang; Xuan Xiao; Fang Wang; Pingliang Lin; Fang Bao; Yong Hu; Yikun He (Journal of Plant Biology, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Assessment and comparison of in vitro immunoregulatory activity of three astaxanthin stereoisomers - Weihong Sun; Lihong Xing; Hong Lin; Kailiang Leng; Yuxiu Zhai; Xiaofang Liu (Journal of Ocean University of China, 2016)

Genetic transformation of Nannochloropsis oculata with a bacterial phleomycin resistance gene as dominant selective marker - Xiaolei Ma; Kehou Pan; Lin Zhang; Baohua Zhu; Guanpin Yang; Xiangyang Zhang (Journal of Ocean University of China, 2016)

Three-dimensional water quality model based on FVCOM for total load control management in Guan River Estuary, Northern Jiangsu Province - Li Zhang; Weibo Lin; Keqiang Li; Jianming Sheng; Aihong Wei; Feng Luo; Yan Wang; Xiulin Wang; Longjun Zhang (Journal of Ocean University of China, 2016)

Comprehensive analysis of tropomyosin isoforms in skeletal muscles by top-down proteomics - Yutong Jin; Ying Peng; Ziqing Lin; Yi-Chen Chen; Liming Wei; Timothy A. Hacker; Lars Larsson; Ying Ge (Journal of Muscle Research and Cell Motility, 2016)

Review of studies on land use and land cover change in Nepal - Basanta Paudel; Yi-li Zhang; Shi-cheng Li; Lin-shan Liu; Xue Wu; Narendra Raj Khanal (Journal of Mountain Science, 2016)

Experimental analysis for the dynamic initiation mechanism of debris flows - Chi Li; Wen-hui Zhu; Lin Li; Xiao-bing Lu; De Yao; Farshad Amini (Journal of Mountain Science, 2016)

Environmental and cortisol-mediated control of Ca2+ uptake in tilapia (Oreochromis mossambicus) - Chia-Hao Lin; Wei-Chun Kuan; Bo-Kai Liao; Ang-Ni Deng; Deng-Yu Tseng; Pung-Pung Hwang (Journal of Comparative Physiology B, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

Estimation and analysis of GPS satellite DCB based on LEO observations - Jian Lin; Xinan Yue; Shufan Zhao (GPS Solutions, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Molecular characterization and detection of a recombinant isolate of bamboo mosaic virus from China - Wenwu Lin; Fangluan Gao; Wenting Yang; Chaowei Yu; Jie Zhang; Lingli Chen; Zujian Wu; Yau-Heiu Hsu; Lianhui Xie (Archives of Virology, 2016)

Genetic diversity and molecular evolution of arabis mosaic virus based on the CP gene sequence - Fangluan Gao; Wuzhen Lin; Jianguo Shen; Furong Liao (Archives of Virology, 2016)

Complete genome sequence of a Chuzan virus strain isolated for the first time in mainland China - Heng Yang; Lei Xiao; Jinxing Meng; Heli Xiong; Lin Gao; Defang Liao; Huachun Li (Archives of Virology, 2016)

Metabolic activation of furan moiety makes Diosbulbin B hepatotoxic - Weiwei Li; Dongju Lin; Huiyuan Gao; Youjun Xu; Dongya Meng; Charles Vincent Smith; Ying Peng; Jiang Zheng (Archives of Toxicology, 2016)

Oxidative stress-induced apoptotic insults to rat osteoblasts are attenuated by nitric oxide pretreatment via GATA-5-involved regulation of Bcl-X L gene expression and protein translocation - Gong-Jhe Wu; Weu Wang; Yi-Ling Lin; Shing Hwa Liu; Ruei-Ming Chen (Archives of Toxicology, 2016)

Heavy metals in deep groundwater within coal mining area, northern Anhui province, China: concentration, relationship, and source apportionment - Manli Lin; Weihua Peng; Herong Gui (Arabian Journal of Geosciences, 2016)

Application of the non-seismic geophysical method in the deep geological structure study of Benxi-Huanren area - Chong Peng; Lin-Fu Xue; Zheng-Hong Liu; Hai-Yan Liu (Arabian Journal of Geosciences, 2016)

Oasis microclimate effect on the dust deposition in Cele Oasis at southern Tarim Basin, China - Lishuai Xu; Guijin Mu; Xiao Ren; Dejun Wan; Junxia He; Yongchong Lin (Arabian Journal of Geosciences, 2016)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Knockdown of α-synuclein in cerebral cortex improves neural behavior associated with apoptotic inhibition and neurotrophin expression in spinal cord transected rats - You-Cui Wang; Guo-Ying Feng; Qing-Jie Xia; Yue Hu; Yang Xu; Liu-lin Xiong; Zhi-wei Chen; Hang-Ping Wang; Ting-Hua Wang; Xue Zhou (Apoptosis, 2016)

Hemostasis Plug for an Electromagnetic Thermotherapy and Its Application for Liver Laceration - Chung-Hsien Liu; Sheng-Chieh Huang; Ying-Jui Chao; Xi-Zhang Lin; Gwo-Bin Lee (Annals of Biomedical Engineering, 2016)

Historical change and future scenarios of sea level rise in Macau and adjacent waters - Lin Wang; Gang Huang; Wen Zhou; Wen Chen (Advances in Atmospheric Sciences, 2016)

Community structure and spatial-temporal variation of netz-phytoplankton in the Bering Sea in summer - Yu Wang; Peng Xiang; Youyin Ye; Gengming Lin; Qingliang Yang; Heshan Lin; Mao Lin (Acta Oceanologica Sinica, 2016)

Entropy‐based spatiotemporal patterns of precipitation regimes in the Huai River basin, China - Qiang Zhang; Yongjie Zheng; Vijay P. Singh; Mingzhong Xiao; Lin Liu (International Journal of Climatology, 2016)
Spatiotemporal patterns of precipitation regimes in terms of precipitation amount and number of precipitation days at different time scales are investigated using the entropy‐based methodologies in the Huai River basin, China. Trends of precipitation variability are quantitatively evaluated using the modified Mann–Kendall trend test method. Correlations between the largest 7‐day precipitation amount (R × 7day) and precipitation variability within 1 year are also analysed. Results indicate the following: (1) there is increasing nonuniformity of annual precipitation amount and annual precipitation days from south to north in the Huai River basin, indicating larger precipitation variability in the northern parts. Transition of precipitation changes is evident in the basin which is reflected by decreasing precipitation variability in the north and increasing precipitation variability in the south. (2) The disorder indices (DIs) exhibit variations at different time scales. In general, precipitation variability is larger at shorter time scales, such as daily, and is smaller at longer time scales, such as annual. (3) Significant relations are identified between the DI and extreme precipitation events, i.e. significant relations between apportionment DI and the largest 7‐day precipitation amount and it is particularly the case in the central and southwestern parts. Thus, it can be said that higher precipitation variability is due to higher frequency of extreme precipitation regimes. Results of this study are of practical significance for planning and management of water resources and agricultural irrigation and agricultural activities during climate change and particularly for enhancement of measures for mitigation of consequences of climate change.

Causes of uncertainty in China's net primary production over the 21st century projected by the CMIP5 Earth system models - Tao Wang; Xin Lin; Yongwen Liu; Sarah Dantec‐Nédélec; Catherine Ottlé (International Journal of Climatology, 2016)
Net primary production is the initial step of the carbon cycle in which atmospheric CO 2 is fixed by plants. The responses of net primary production ( NPP ) to climate change and CO 2 are key processes that have the potential to significantly affect the climate–carbon feedback and future atmospheric CO 2 levels. Understanding future NPP changes is important for China that became the world's largest CO 2 emitter since 2006. Here, we analysed NPP changes in China under the four emission scenarios from 11 Earth system models participating in the Coupled Model Intercomparison Project Phase 5. We find a general increase of NPP over the 21st century under the four emission scenarios, with the large percentage increase in northwestern China and Qinghai–Tibetan Plateau. However, there is a large model spread in the increase of NPP at both country and local scales. We present a statistical approach to assess various processes to explain this large spread, and find that the large spread at the country level is predominantly attributed to inter‐model difference in parameterization of CO 2 fertilization effect within each emission scenario. But the parameterization of CO 2 fertilization effect not always dominates over the model spread across China. When it comes to the local scale, the model spread can be significantly contributed by inter‐model difference in parameterization of NPP responses to precipitation along with precipitation projection in northwestern China. Our findings provide the reasons for divergent responses of future NPP through process decomposition and are the first to pinpoint that the model process dominating over the uncertainty exhibits regional dependence.

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yu Lin Yong; Li Lee Chew; Choon Weng Lee; Ving Ching Chong (Marine Biology Research, 2016)

Experimental Investigation on Non-Darcian Flow in Unbound Graded Aggregate Material of Highway Pavement - Han-Cheng Dan; Lin-Hua He; Bo Xu (Transport in Porous Media, 2016)

A remorin gene is implicated in quantitative disease resistance in maize - Tiffany M. Jamann; Xingyu Luo; Laura Morales; Judith M. Kolkman; Chia-Lin Chung; Rebecca J. Nelson (Theoretical and Applied Genetics, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Fine mapping of a dominantly inherited powdery mildew resistance major-effect QTL, Pm1.1, in cucumber identifies a 41.1 kb region containing two tandemly arrayed cysteine-rich receptor-like protein kinase genes - Xuewen Xu; Ting Yu; Ruixue Xu; Yang Shi; Xiaojian Lin; Qiang Xu; Xiaohua Qi; Yiqun Weng; Xuehao Chen (Theoretical and Applied Genetics, 2016)

Sample Management: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - Michael J. Redrup; Harue Igarashi; Jay Schaefgen; Jenny Lin; Lisa Geisler; Mohamed Ben M’Barek; Subramanian Ramachandran; Thales Cardoso; Vera Hillewaert (The AAPS Journal, 2016)

Influence of Drug Properties and Formulation on In Vitro Drug Release and Biowaiver Regulation of Oral Extended Release Dosage Forms - Zhongqiang Lin; Deliang Zhou; Stephen Hoag; Yihong Qiu (The AAPS Journal, 2016)

Evaluating and Reporting the Immunogenicity Impacts for Biological Products—a Clinical Pharmacology Perspective - Yow-Ming C. Wang; Jie Wang; Yuen Yi Hon; Lin Zhou; Lanyan Fang; Hae Young Ahn (The AAPS Journal, 2016)

Statistic inversion of multi-zone transition probability models for aquifer characterization in alluvial fans - Lin Zhu; Zhenxue Dai; Huili Gong; Carl Gable; Pietro Teatini (Stochastic Environmental Research and Risk Assessment, 2016)

Exploring spatiotemporal relationships among meteorological, agricultural, and hydrological droughts in Southwest China - Zhiyong Wu; Yun Mao; Xiaoyan Li; Guihua Lu; Qingxia Lin; Huating Xu (Stochastic Environmental Research and Risk Assessment, 2016)

Histone modifications in DNA damage response - Lin-Lin Cao; Changchun Shen; Wei-Guo Zhu (Science China Life Sciences, 2016)

Mechanical Behavior of Brittle Rock-Like Specimens with Pre-existing Fissures Under Uniaxial Loading: Experimental Studies and Particle Mechanics Approach - Ri-hong Cao; Ping Cao; Hang Lin; Cheng-zhi Pu; Ke Ou (Rock Mechanics and Rock Engineering, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Pseudoginsenoside-F11 inhibits methamphetamine-induced behaviors by regulating dopaminergic and GABAergic neurons in the nucleus accumbens - Kequan Fu; Huiyang Lin; Yoshiaki Miyamoto; Chunfu Wu; Jingyu Yang; Kyosuke Uno; Atsumi Nitta (Psychopharmacology, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

A new deep-sea hydroid (Cnidaria: Hydrozoa) from the Bering Sea Basin reveals high genetic relevance to Arctic and adjacent shallow-water species - Xikun Song; Cinzia Gravili; Jianjun Wang; Yacheng Deng; Yongqiang Wang; Lu Fang; Heshan Lin; Shaoqing Wang; Yiting Zheng; Junhui Lin (Polar Biology, 2016)

Trade-off between seed defensive traits and impacts on interaction patterns between seeds and rodents in forest ecosystems - Zhibin Zhang; Zhenyu Wang; Gang Chang; Xianfeng Yi; Jiqi Lu; Zhishu Xiao; Hongmao Zhang; Lin Cao; Fusheng Wang; Hongjun Li; Chuan Yan (Plant Ecology, 2016)

Observation of summertime upwelling off the eastern and northeastern coasts of Hainan Island, China - Peigen Lin; Jianyu Hu; Quanan Zheng; Zhenyu Sun; Jia Zhu (Ocean Dynamics, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

A CGE analysis of carbon market impact on CO2 emission reduction in China: a technology-led approach - Lin Yang; Yunfei Yao; Jiutian Zhang; Xian Zhang; Karl J. McAlinden (Natural Hazards, 2016)

Natural hazards knowledge and risk perception of Wujie indigenous community in Taiwan - Giulia Roder; Tjuku Ruljigaljig; Ching-Weei Lin; Paolo Tarolli (Natural Hazards, 2016)

GSTM1 Null Genotype and GSTP1 Ile105Val Polymorphism Are Associated with Alzheimer’s Disease: a Meta-Analysis - Mo Wang; Yu Li; Lulu Lin; Guijun Song; Teng Deng (Molecular Neurobiology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Inhibition of Rac1 Activity in the Hippocampus Impairs the Forgetting of Contextual Fear Memory - Lizhu Jiang; Rongrong Mao; Qixin Zhou; Yuexiong Yang; Jun Cao; Yuqiang Ding; Yuan Yang; Xia Zhang; Lingjiang Li; Lin Xu (Molecular Neurobiology, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Fenpropathrin, a Widely Used Pesticide, Causes Dopaminergic Degeneration - Jing Xiong; Xiaowei Zhang; Jinsha Huang; Chunnuan Chen; Zhenzhen Chen; Ling Liu; Guoxin Zhang; Jiaolong Yang; Zhentao Zhang; Zhaohui Zhang; Zhicheng Lin; Nian Xiong; et al. (Molecular Neurobiology, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Therapeutic Intervention of Learning and Memory Decays by Salidroside Stimulation of Neurogenesis in Aging - Huijuan Jin; Lei Pei; Xiaogang Shu; Xin Yang; Tianhua Yan; Yan Wu; Na Wei; Honglin Yan; Shan Wang; Chengye Yao; Dan Liu; Qing Tian; et al. (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Controversial opinion: evaluation of EGR1 and LAMA2 loci for high myopia in Chinese populations - Fang-yu Lin; Zhu Huang; Ning Lu; Wei Chen; Hui Fang; Wei Han (Journal of Zhejiang University-SCIENCE B, 2016)

Temporal change in soil macropores measured using tension infiltrometer under different land uses and slope positions in subtropical China - Zhongbin Zhang; Lin Lin; Yi Wang; Xinhua Peng (Journal of Soils and Sediments, 2016)

The foliar spray of Rhodopseudomonas palustris grown under Stevia residue extract promotes plant growth via changing soil microbial community - Jiangbing Xu; Youzhi Feng; Yanling Wang; Xiaosan Luo; Jianwu Tang; Xiangui Lin (Journal of Soils and Sediments, 2016)

A Consortium of Three Plant Growth-Promoting Rhizobacterium Strains Acclimates Lycopersicon esculentum and Confers a Better Tolerance to Chilling Stress - Chao Wang; Cui Wang; Yan-Lin Gao; Yun-Peng Wang; Jian-Hua Guo (Journal of Plant Growth Regulation, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

TGF-β induces miR-30d down-regulation and podocyte injury through Smad2/3 and HDAC3-associated transcriptional repression - Lin Liu; Wenjun Lin; Qin Zhang; Wangsen Cao; Zhihong Liu (Journal of Molecular Medicine, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

High Sensitivity Bacillus thuringiensis Cry1Ac Protein Detections Using Fluorescein Diacetate Nanoparticles - Cui Liu; Zhen Zhou; Linling Zou; Yuan-Cheng Cao; Jun’An Liu; Yongjun Lin (Journal of Fluorescence, 2016)

Tectonic evolution of Tarim basin in Cambrian–Ordovician and its implication for reservoir development, NW China - Yu BINGSONG; RUAN ZHUANG; ZHANG CONG; PAN YINGLU; LIN CHANGSONG; WANG LIDONG (Journal of Earth System Science, 2016)

Monazite U–Th–Pb EPMA and zircon U–Pb SIMS chronological constraints on the tectonic, metamorphic, and thermal events in the inner part of the Variscan orogen, example from the Sioule series, French Massif Central - Damien Do Couto; Michel Faure; Romain Augier; Alain Cocherie; Philippe Rossi; Xian-Hua Li; Wei Lin (International Journal of Earth Sciences, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Characterization of resistance to multiple fungicides in Botrytis cinerea populations from Asian ginseng in northeastern China - Xiao Hong Lu; Xiao Lin Jiao; Jianjun J. Hao; Amanda Juan Chen; Wei Wei Gao (European Journal of Plant Pathology, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Changes of lead speciation and microbial toxicity in soil treated with repeated Pb exposure in the presence of BDE209 - Rong Zhang; Wei Zhang; Gao Liu; Kuangfei Lin; Rongbing Fu (Environmental Science and Pollution Research, 2016)

Degradation of artificial sweetener saccharin in aqueous medium by electrochemically generated hydroxyl radicals - Heng Lin; Jie Wu; Nihal Oturan; Hui Zhang; Mehmet A. Oturan (Environmental Science and Pollution Research, 2016)

Sources appointment and ecological risk assessment of polycyclic aromatic hydrocarbons (PAHs) in sediments of Erhai Lake, a low-latitude and high-altitude lake in southwest China - Yuan Hezhong; Zhang Enlou; Lin Qi; Wang Rong; Liu Enfeng (Environmental Science and Pollution Research, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Effect of butyl paraben on the development and microbial composition of periphyton - Chaofeng Song; Juan Lin; Xiaolong Huang; Yonghong Wu; Jiantong Liu; Chenxi Wu (Ecotoxicology, 2016)

Phosphorus-controlled trace element distribution in zircon revealed by NanoSIMS - Wei Yang; Yangting Lin; Jialong Hao; Jianchao Zhang; Sen Hu; Huaiwei Ni (Contributions to Mineralogy and Petrology, 2016)

Development of a multiplex event-specific PCR assay for detection of genetically modified rice - J. Lu; G.Z. Ji; G. Li; Y.F. Wu; J. Yang; S.L. Lin; D.L. Yang; J.N. Zhao; W.M. Xiu (Cereal Research Communications, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Bioaccumulation of Metals in Tissues of Seahorses Collected from Coastal China - Wei Zhang; Yanhong Zhang; Li Zhang; Qiang Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Static and dynamic posterior cingulate cortex nodal topology of default mode network predicts attention task performance - Pan Lin; Yong Yang; Jorge Jovicich; Nicola De Pisapia; Xiang Wang; Chun S. Zuo; James Jonathan Levitt (Brain Imaging and Behavior, 2016)

Increased Oxidative DNA Damage in Placenta Contributes to Cadmium-Induced Preeclamptic Conditions in Rat - Xiaojie Zhang; Zhangye Xu; Feng Lin; Fan Wang; Duyun Ye; Yinping Huang (Biological Trace Element Research, 2016)

Effects of Supplemental Chromium Source and Concentration on Growth Performance, Carcass Traits, and Meat Quality of Broilers Under Heat Stress Conditions - Yanling Huang; Jian Yang; Fang Xiao; Karen Lloyd; Xi Lin (Biological Trace Element Research, 2016)

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Signaling mechanisms of plant cryptochromes in Arabidopsis thaliana - Bobin Liu; Zhaohe Yang; Adam Gomez; Bin Liu; Chentao Lin; Yoshito Oka (Journal of Plant Research, 2016)

miR156 modulates rhizosphere acidification in response to phosphate limitation in Arabidopsis - Kai Jian Lei; Ya Ming Lin; Guo Yong An (Journal of Plant Research, 2016)

Soil organic carbon pool along different altitudinal level in the Sygera Mountains, Tibetan Plateau - He-ping Ma; Xiao-lin Yang; Qi-qiang Guo; Xin-jun Zhang; Chen-ni Zhou (Journal of Mountain Science, 2016)

Applying systematic conservation planning to constitute a protection strategy for broad-leaved Korean pine forests in Changbai Mountains, China - Lin Ma; Gong-qi Sun; Yi Qu; Jun-qing Li (Journal of Mountain Science, 2016)

Experimental study of motion characteristics of rock slopes with weak intercalation under seismic excitation - Zhen-Lin Chen; Xiao Hu; Qiang Xu (Journal of Mountain Science, 2016)

Functional analysis of PI-like gene in relation to flower development from bamboo (Bambusa oldhamii) - LONGFEI ZHU; YAN SHI; QIAOLU ZANG; QUAN SHI; SHINAN LIU; YINGWU XU; XINCHUN LIN (Journal of Genetics, 2016)

One-step RT-LAMP analysis for efficient detection of Odontoglossum ringspot virus from Oncidiinae hybrids (Orchidaceae) - Chi-Chu Tsai; Chun-Yen Huang; I-Szu Weng; Wen-Lin Liu; Chang-Hung Chou (Journal of General Plant Pathology, 2016)

Experimental study of the effect of shallow groundwater table on soil thermal properties - Jianmei Jiang; Lin Zhao; Yijian Zeng; Zhe Zhai (Frontiers of Earth Science, 2016)

Human-, Ovine-, and Bovine-Specific Viral Source Tracking Tools to Discriminate Between the Major Fecal Sources in Agricultural Waters - Marta Rusiñol; Elaine Moriarty; Susan Lin; Sílvia Bofill-Mas; Brent Gilpin (Food and Environmental Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Development of SNP markers in lined seahorse (Hippocampus erectus) based on transcriptome sequencing - Hongyue Qu; Wei Luo; Qiang Lin (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Pretreatment of Miscanthus by NaOH/Urea Solution at Room Temperature for Enhancing Enzymatic Hydrolysis - Hongming Lou; Qiaoyan Hu; Xueqing Qiu; Xiuli Li; Xuliang Lin (BioEnergy Research, 2016)

Production of 2,3-Butanediol from Sucrose by a Klebsiella Species - Fengxue Xin; Anindya Basu; Michelle Cheung Weng; Kun-Lin Yang; Jianzhong He (BioEnergy Research, 2016)

Immunoenhancement with flagellin as an adjuvant to whole-killed rabies vaccine in mice - Xing-xing Xiao; Yun Zhang; Ji-xing Liu; Qiao-lin Wei; Xiang-ping Yin (Archives of Virology, 2016)

Mono(2-ethylhexyl)phthalate accumulation disturbs energy metabolism of fat cells - Huai-chih Chiang; Ya-Ting Kuo; Chih-Che Shen; Yi-Hua Lin; Shu-Li Wang; Tsui-Chun Tsou (Archives of Toxicology, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

A statistical view for Chinese zooarchaeology: from the Neolithic to Pre-Han periods - Minghao Lin (Archaeological and Anthropological Sciences, 2016)

Improved random noise attenuation using f−x empirical mode decomposition and local similarity - Shu-Wei Gan; Shou-Dong Wang; Yang-Kang Chen; Jiang-Long Chen; Wei Zhong; Cheng-Lin Zhang (Applied Geophysics, 2016)

Two-dimensional inversion of spectral induced polarization data using MPI parallel algorithm in data space - Zhi-Yong Zhang; Han-Dong Tan; Kun-Peng Wang; Chang-Hong Lin; Bin Zhang; Mao-Bi Xie (Applied Geophysics, 2016)

Research on RTP aeromagnetic gradient data and its applicability in different latitudes - Lin Li; Hua Guo; Ping Wang; Wei-Jie Jia (Applied Geophysics, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Calibration of HY-2A satellite significant wave heights with in situ observation - Hailong Peng; Mingsen Lin (Acta Oceanologica Sinica, 2016)

Reducing GPS carrier phase errors in the measurement and position domains for short-distance static relative positioning - Chao Liu; Peng Lin; Xingwang Zhao; Jingxiang Gao (Acta Geodaetica et Geophysica, 2016)

A novel metalloproteinase virulence factor is involved in B acillus thuringiensis pathogenesis in nematodes and insects - Donghai Peng; Jian Lin; Qiong Huang; Wen Zheng; Guoqiang Liu; Jinshui Zheng; Lei Zhu; Ming Sun (Environmental Microbiology, 2016)
Summary The Gram‐positive soil bacterium B acillus thuringiensis has been developed as the leading microbial insecticide for years. The pathogenesis of B . thuringiensis requires common extracellular factors that depend on the PlcR regulon, which regulates a large number of virulence factors; however, the precise role of many of these proteins is not known. In this study, we describe the complete lifecycle of a nematicidal B . thuringiensis strain in the free living nematode C aenorhabditis elegans using in vitro and in vivo molecular techniques to follow host and bacterial effectors during the infection process. We then focus on the metalloproteinase ColB , a collagenase, which was found highly important for destruction of the intestine thereby facilitates the adaptation and colonization of B . thuringiensis in C . elegans. In vivo green fluorescent protein ( GFP ) reporter‐gene studies showed that ColB expression is highly induced and regulated by the global activator PlcR . Finally, we demonstrated that ColB also takes part in B . thuringiensis virulence in an insect model following injection and oral infection. Indeed, addition of purified ColB accelerates the action of Cry toxin proteins in insects, too . These results give novel insights into host adaptation for B . thuringiensis and other B . cereus group bacteria and highlight the role of collagenase metalloproteases to synergize infection process.

Decrease of Lipid Oxidation for Dried Shrimp ( Acetes chinensis ) Preservation Using Alkaline Lipase Hydrolysis Technology - Jianhua Liu; Peicheng Zhao; Lin Liu; Jianyou Zhang; Shulai Liu; Zhifei Zhang; Yuting Ding (Journal of Aquatic Food Product Technology, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

Durability of reactive magnesia-activated slag-stabilized low plasticity clay subjected to drying–wetting cycle - Yan-Jun Du; Yu-Lin Bo; Fei Jin; Chen-Yang Liu (European Journal of Environmental and Civil Engineering, 2016)

Liposome containing cinnamon oil with antibacterial activity against methicillin-resistant Staphylococcus aureus biofilm - Haiying Cui; Wei Li; Changzhu Li; Saritporn Vittayapadung; Lin Lin (Biofouling, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Effect of Temperature and pH on the Sorption of Dibutyl Phthalate on Humic Acid - Minling Gao; Xiaolei Gong; Mengting Lv; Wenhua Song; Xiaojun Ma; Yun Qi; Lin Wang (Water, Air, & Soil Pollution, 2016)

Clustering Quantile Regression-Based Drought Trends in Taiwan - Jenq-Tzong Shiau; Jia-Wei Lin (Water Resources Management, 2016)

Complete chloroplast genome sequences of Eucommia ulmoides: genome structure and evolution - Lin Wang; Ta-na Wuyun; Hongyan Du; Depeng Wang; Deming Cao (Tree Genetics & Genomes, 2016)

Therapy with the Combination of Amlodipine and Irbesartan Has Persistent Preventative Effects on Stroke Onset Associated with BDNF Preservation on Cerebral Vessels in Hypertensive Rats - Yu Hasegawa; Takashi Nakagawa; Ken Uekawa; Mingjie Ma; Bowen Lin; Hiroaki Kusaka; Tetsuji Katayama; Daisuke Sueta; Kensuke Toyama; Nobutaka Koibuchi; Shokei Kim-Mitsuyama (Translational Stroke Research, 2016)

Identification and molecular mapping of Rps11, a novel gene conferring resistance to Phytophthora sojae in soybean - Jieqing Ping; Joshua C. Fitzgerald; Chunbao Zhang; Feng Lin; Yonghe Bai; Dechun Wang; Rajat Aggarwal; Maqsood Rehman; Oswald Crasta; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Spatial analysis of gastric cancer morbidity in regions of rapid urbanization: a case study in Xiamen, China - JiLai Liu; XinHu Li; Tao Lin; Long Dai; GuoQin Zhang; ChaoSheng Zhang; Hong Ye; Vee Gibson; QianJun Zhao (Stochastic Environmental Research and Risk Assessment, 2016)

Transgenic Bt cotton driven by the green tissue-specific promoter shows strong toxicity to lepidopteran pests and lower Bt toxin accumulation in seeds - Qing Wang; Yi Zhu; Lin Sun; Lebin Li; Shuangxia Jin; Xianlong Zhang (Science China Life Sciences, 2016)

Joint observation results of Na layer and ionosphere in Wuhan during the Total Solar Eclipse - XueWu Cheng; Yong Yang; ZeLong Wang; FaQuan Li; GuoTao Yang; ZhengYu Zhao; Wei Gong; JiHong Wang; Xiong Hu; Xin Lin; XiaoCheng Wu; ShaLei Song; et al. (Science China Earth Sciences, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

CarHSFB2, a Class B Heat Shock Transcription Factor, Is Involved in Different Developmental Processes and Various Stress Responses in Chickpea (Cicer Arietinum L.) - Hao Ma; Chuntao Wang; Bin Yang; Huiying Cheng; Ze Wang; Abudoukeyumu Mijiti; Cai Ren; Guanghang Qu; Hua Zhang; Lin Ma (Plant Molecular Biology Reporter, 2016)

Phosphorus amendment mitigates nitrogen addition-induced phosphorus limitation in two plant species in a desert steppe, China - Juying Huang; Hailong Yu; Henry Lin; Yu Zhang; Eric B. Searle; Zhiyou Yuan (Plant and Soil, 2016)

Ranking of mechanisms governing the phytoavailability of cadmium in agricultural soils using a mechanistic model - Zhongbing Lin; André Schneider; Thibault Sterckeman; Christophe Nguyen (Plant and Soil, 2016)

Quantitative phosphoproteomic analysis of early seed development in rice (Oryza sativa L.) - Jiehua Qiu; Yuxuan Hou; Xiaohong Tong; Yifeng Wang; Haiyan Lin; Qing Liu; Wen Zhang; Zhiyong Li; Babi R. Nallamilli; Jian Zhang (Plant Molecular Biology, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Taxonomic Study of the Genus Apalacris Walker (Orthoptera: Catantopidae) - Z M Zheng; L L Lin; Y Niu (Neotropical Entomology, 2016)

Onychomycosis Associated with Exophiala oligosperma in Taiwan - Yu-Min Wen; Ranjith Kumar Rajendran; Ying-Fang Lin; Roland Kirschner; Sindy Hu (Mycopathologia, 2016)

Discovery of microRNAs and transcript targets related to witches’ broom disease in Paulownia fortunei by high-throughput sequencing and degradome approach - Suyan Niu; Guoqiang Fan; Minjie Deng; Zhenli Zhao; Enkai Xu; Lin Cao (Molecular Genetics and Genomics, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Thaw-induced slope failures and stability analyses in permafrost regions of the Qinghai-Tibet Plateau, China - Fujun Niu; Jing Luo; Zhanju Lin; Jianhong Fang; Minghao Liu (Landslides, 2016)

Influence of water-dispersible colloids from organic manure on the mechanism of metal transport in historically contaminated soils: coupling colloid fractionation with high-energy synchrotron analysis - Qi Lin; Xin Xu; Qibei Bao; Kokyo Oh; Dongling Chen; Lijuan Zhang; Xiaodong Shen (Journal of Soils and Sediments, 2016)

Arsenite and arsenate leaching and retention on iron (hydr)oxide-coated sand column - Yin Wang; Lin Sun; Tao Han; Youbin Si; Rongfu Wang (Journal of Soils and Sediments, 2016)

Response of CaCl2-extractable heavy metals, polychlorinated biphenyls, and microbial communities to biochar amendment in naturally contaminated soils - Wei Liu; Shutao Wang; Peng Lin; Hanwen Sun; Juan Hou; Qingqing Zuo; Rong Huo (Journal of Soils and Sediments, 2016)

Inhibition of AMPK through Lyn-Syk-Akt enhances FcεRI signal pathways for allergic response - Kai-Chun Lin; Duen-Yi Huang; De-Wei Huang; Shiang-Jong Tzeng; Wan-Wan Lin (Journal of Molecular Medicine, 2016)

Scutellarin Alleviates Behavioral Deficits in a Mouse Model of Multiple Sclerosis, Possibly Through Protecting Neural Stem Cells - Wei-Wei Wang; Lin Lu; Tian-Hao Bao; Hong-Miao Zhang; Jing Yuan; Wei Miao; Shu-Fen Wang; Zhi-Cheng Xiao (Journal of Molecular Neuroscience, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Neuroprotective Effect Is Driven Through the Upregulation of CB1 Receptor in Experimental Autoimmune Encephalomyelitis - Zhi-Yin Lou; Wen-Bo Yu; Jie Chen; Lin Li; Li-Sheng Jiang; Bao-Guo Xiao; Zhen-Guo Liu (Journal of Molecular Neuroscience, 2016)

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Production of CCL20 on nucleus pulposus cells recruits IL-17-producing cells to degenerated IVD tissues in rat models - Yuanqiang Zhang; Lian Liu; Shuaishuai Wang; Yunpeng Zhao; Yi Liu; Jingkun Li; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2016)

A Clinical and Kinematical Evaluation of Trajectory Planning Software for Posterior Atlantoaxial Transarticular Screw Fixation Surgery - Andy Chien; Yao-Hung Wang; Dar-Ming Lai; Ying-Sian Chen; Wen-Kai Chou; Been-Der Yang; Jaw-Lin Wang (Journal of Medical and Biological Engineering, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

On the control of Microcystis aeruginosa and Synechococccus species using an algicidal bacterium, Stenotrophomonas F6, and its algicidal compounds cyclo-(Gly-Pro) and hydroquinone - Shengqin Lin; Mengxin Geng; Xianglong Liu; Jing Tan; Hong Yang (Journal of Applied Phycology, 2016)

Diesel degradation in soil catalyzed by the addition of a bioagent - Y. Lin; J.-J. Lay; W. K. Shieh (International Journal of Environmental Science and Technology, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Different hydrodynamic conditions on the deposition of organic carbon in sediment of two reservoirs - Zhao Luo; Ji-Ming Ma; Shuang-Ling Zheng; Chun-Zi Nan; Lin-Mei Nie (Hydrobiologia, 2016)

Patterns of succession between bloom-forming cyanobacteria Aphanizomenon flos-aquae and Microcystis and related environmental factors in large, shallow Dianchi Lake, China - Yanlong Wu; Lin Li; Lingling Zheng; Gongyuan Dai; Haiyan Ma; Kun Shan; Huadong Wu; Qichao Zhou; Lirong Song (Hydrobiologia, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Establishment from the snout and kidney of goldfish, Carassius auratus, of two new cell lines and their susceptibility to infectious pancreatic necrosis virus - Hongli Jing; Longying Gao; Min Zhang; Na Wang; Xiangmei Lin; Lifeng Zhang; Shaoqiang Wu (Fish Physiology and Biochemistry, 2016)

Ya-fish (Schizothorax prenanti) spexin: identification, tissue distribution and mRNA expression responses to periprandial and fasting - Hongwei Wu; Fangjun Lin; Hu Chen; Ju Liu; Yundi Gao; Xin Zhang; Jin Hao; Defang Chen; Dengyue Yuan; Tao Wang; Zhiqiong Li (Fish Physiology and Biochemistry, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

Panobinostat PK/PD profile in combination with bortezomib and dexamethasone in patients with relapsed and relapsed/refractory multiple myeloma - Song Mu; Yoshiaki Kuroda; Hirohiko Shibayama; Masayuki Hino; Takeshi Tajima; Claudia Corrado; Rong Lin; Edward Waldron; Florence Binlich; Kenshi Suzuki (European Journal of Clinical Pharmacology, 2016)

Hyperspectral analysis of soil organic matter in coal mining regions using wavelets, correlations, and partial least squares regression - Lixin Lin; Yunjia Wang; Jiyao Teng; Xuchen Wang (Environmental Monitoring and Assessment, 2016)

Effects of grafting on the cadmium accumulation characteristics of the potential Cd-hyperaccumulator Solanum photeinocarpum - Lijin Lin; Daiyu Yang; Xun Wang; Ming’an Liao; Zhihui Wang; Xiulan Lv; Fuyi Tang; Dong Liang; Hui Xia; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Aerobic debromination of BDE-209 by Rhodococcus sp. coupled with zerovalent iron/activated carbon - Lili Liu; Yacong Zhang; Ruihong Liu; Zhiping Wang; Feng Xu; Yilun Chen; Kuangfei Lin (Environmental Science and Pollution Research, 2016)

Mitigation of cadmium and arsenic in rice grain by applying different silicon fertilizers in contaminated fields - Hong-Yan Wang; Shi-Lin Wen; Peng Chen; Lu Zhang; Kuang Cen; Guo-Xin Sun (Environmental Science and Pollution Research, 2016)

Effect of resin content and substrate on the emission of BTEX and carbonyls from low-VOC water-based wall paint - Ping Zhao; Yu-Hsiang Cheng; Chi-Chi Lin; Yu-Lin Cheng (Environmental Science and Pollution Research, 2016)

Levels, distributions and correlations of polybrominated diphenyl ethers in air and dust of household and workplace in Shanghai, China: implication for daily human exposure - Feng Xu; Weibiao Tang; Wei Zhang; Lili Liu; Kuangfei Lin (Environmental Science and Pollution Research, 2016)

Degradation of oxcarbazepine by UV-activated persulfate oxidation: kinetics, mechanisms, and pathways - Lingjun Bu; Shiqing Zhou; Zhou Shi; Lin Deng; Guangchao Li; Qihang Yi; Naiyun Gao (Environmental Science and Pollution Research, 2016)

Cytotoxicity and mutagenicity of sidestream cigarette smoke particulate matter of different particle sizes - Xiang Li; Bencheng Lin; Huashan Zhang; Fuwei Xie; Na Ta; Lei Tian; Huimin Liu; Zhuge Xi (Environmental Science and Pollution Research, 2016)

Ambient air particulates and particulate-bound mercury Hg(p) concentrations: dry deposition study over a Traffic, Airport, Park (T.A.P.) areas during years of 2011–2012 - Guor-Cheng Fang; Yen-Heng Lin; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2016)

Isolation and Characterization of the Lytic Cold-Active Bacteriophage MYSP06 from the Mingyong Glacier in China - Mingyuan Li; Jilian Wang; Qi Zhang; Lianbing Lin; Anxin Kuang; Luis Alberto Materon; Xiuling Ji; Yunlin Wei (Current Microbiology, 2016)

Relative importance of tropical SST anomalies in maintaining the Western North Pacific anomalous anticyclone during El Niño to La Niña transition years - Zesheng Chen; Zhiping Wen; Renguang Wu; Xiaobin Lin; Jiabao Wang (Climate Dynamics, 2016)

Potential negative effects of groundwater dynamics on dry season convection in the Amazon River basin - Yen-Heng Lin; Min-Hui Lo; Chia Chou (Climate Dynamics, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Ecological Risk Assessment of EDTA-Assisted Phytoremediation of Cd Under Different Cultivation Systems - Jie Luo; Shihua Qi; X. W. Sophie Gu; Tao Hou; Lihong Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Early Life Exposure to Ractopamine Causes Endocrine-Disrupting Effects in Japanese Medaka (Oryzias latipes) - Liwei Sun; Sisi Wang; Xia Lin; Hana Tan; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2016)

Alcohol consumption and rates of cancer screening: Is cancer risk overestimated? - Lin Mu; Kenneth J. Mukamal (Cancer Causes & Control, 2016)

Effects of Supplemental Chromium Source and Concentration on Growth, Carcass Characteristics, and Serum Lipid Parameters of Broilers Reared Under Normal Conditions - Cancai Zheng; Yanling Huang; Fang Xiao; Xi Lin; Karen Lloyd (Biological Trace Element Research, 2016)

Isolation, complete genome sequencing, and phylogenetic analysis of the first Chuzan virus in China - Fang Wang; Jun Lin; Jitao Chang; Yingying Cao; Shaomin Qin; Jianmin Wu; Li Yu (Virus Genes, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Characteristics of diffuse pollution of nitrogen and phosphorous from a small town in the hilly area of the central Sichuan Basin, China - Xiao-lin Yang; Xi Shen; Bo Zhu (Journal of Mountain Science, 2016)

Variation of cavity gas pressure in slopes with weak intercalation under seismic load - Xiao-qun Wang; Zhen-lin Chen; Zhou Zhou; Man Shen (Journal of Mountain Science, 2016)

Spatial and temporal variations of global frictional torque during the period 1948–2011 - He Gong; Mei Huang; Lin Zhu; Shengli Guo; Yaping Shao (Journal of Meteorological Research, 2016)

A coupled experiment with LICOM2 as the ocean component of CESM1 - Pengfei Lin; Hailong Liu; Wei Xue; Huimin Li; Jinrong Jiang; Mirong Song; Yi Song; Fuchang Wang; Minghua Zhang (Journal of Meteorological Research, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Implication of the chemical index of alteration as a paleoclimatic perturbation indicator: an example from the lower Neoproterozoic strata of Aksu, Xinjiang, NW China - Haifeng Ding; Dongsheng Ma; Chunyan Yao; Qizhong Lin; Linhai Jing (Geosciences Journal, 2016)

A comparative study of landslide susceptibility maps using logistic regression, frequency ratio, decision tree, weights of evidence and artificial neural network - Liang-Jie Wang; Min Guo; Kazuhide Sawada; Jie Lin; Jinchi Zhang (Geosciences Journal, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

A simple method to extract tropical monsoon forests using NDVI based on MODIS data: A case study in South Asia and Peninsula Southeast Asia - Sen Lin; Ronggao Liu (Chinese Geographical Science, 2016)

Carbon stock of larch plantations and its comparison with an old-growth forest in northeast China - Guang Qi; Hua Chen; Li Zhou; Xinchuang Wang; Wangming Zhou; Lin Qi; Yuhua Yang; Fengling Yang; Qingli Wang; Limin Dai (Chinese Geographical Science, 2016)

Influencing factors of seed long-distance dispersal on a fragmented forest landscape on Changbai Mountains, China - Fuqiang Zhao; Lin Qi; Lei Fang; Jian Yang (Chinese Geographical Science, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Characterization of the novel T4-like Salmonella enterica bacteriophage STP4-a and its endolysin - Meng Li; Mengzhe Li; Hong Lin; Jingxue Wang; Yanqiu Jin; Feng Han (Archives of Virology, 2016)

Molecular characterization of coxsackievirus A21 in Shandong, China - Suting Wang; Minglei Xu; Xiaojuan Lin; Yao Liu; Ping Xiong; Lijuan Wang; Aiqiang Xu; Zexin Tao; Dongfeng Zhang (Archives of Virology, 2016)

A new method of deep carbonate lithology identification at the Tadong uplift in the eastern section of the Tarim Basin - Jingyan Liu; Qian Chang; Changsong Lin; Junlong Zhang; Feng He; Shiqiang Xia (Arabian Journal of Geosciences, 2016)

A bibliometric analysis of oyster research from 1991 to 2014 - Lin Guo; Fei Xu; Zhigang Feng; Guofan Zhang (Aquaculture International, 2016)

Effects of total replacement of fish oil on growth performance, lipid metabolism and antioxidant capacity in tilapia (Oreochromis niloticus) - Xianghe Peng; Fajian Li; Shimei Lin; Yongjun Chen (Aquaculture International, 2016)

The effect of different feeding rates on growth, feed efficiency and immunity of juvenile Penaeus monodon - Jin Niu; Xu Chen; Yun-Qiang Zhang; Li-Xia Tian; Hei-Zhao Lin; Jun Wang; Yun Wang; Yong-Jian Liu (Aquaculture International, 2016)

Estimates of genetic parameters for growth-related traits of the red swamp crayfish, Procambarus clarkii - Fei Li; Zhi-min Gu; Xi-lian Li; Jian-lin Guo; Yong-yi Jia; Yu-fei Zhang; Xian-ming Huang; Wen-min Zhang (Aquaculture International, 2016)

Application of a Bayesian method to data-poor stock assessment by using Indian Ocean albacore (Thunnus alalunga) stock assessment as an example - Wenjiang Guan; Lin Tang; Jiangfeng Zhu; Siquan Tian; Liuxiong Xu (Acta Oceanologica Sinica, 2016)

Evaluation of abundant hydrocarbon-generation depressions in the deepwater area of Qiongdongnan Basin, South China Sea - Zhen Liu; Zhipeng Sun; Zisong Wang; Wei Zhang; Tingan Li; Weijun He; Fengxia Li; Shang Cao; Jingjing Liu; Lu Lin (Acta Oceanologica Sinica, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

Transcriptomic response during phage infection of a marine cyanobacterium under phosphorus‐limited conditions - Xingqin Lin; Huiming Ding; Qinglu Zeng (Environmental Microbiology, 2016)
Summary The transcriptomic responses of bacteria to environmental stresses have been studied extensively, yet we know little about how the stressed cells respond to bacteriophage infection. Here, we conducted the first whole transcriptome sequencing (RNA‐seq) study of stressed bacteria to phage infection by infecting the marine picocyanobacterium P rochlorococcus NATL2A with cyanomyovirus P ‐ SSM 2 under P limitation, a strong selective force in the oceans. Transcripts of the P ‐acquisition genes in the uninfected cells were enriched after P limitation, including the high‐affinity phosphate‐binding protein gene pstS . They were still enriched in the infected cells under P ‐limited conditions. In contrast, transcripts of adenosine triphosphate (ATP) synthase and ribosomal protein genes were depleted in the uninfected cells after P limitation but were enriched during phage infection of P ‐starved cells. Cyanophage P ‐SSM2 contains pstS , and pstS and its adjacent gene g247 of unknown function were the only phage genes that were enriched under P ‐limited conditions. We further found that the host pstS transcript number per cell decreased after infection, however, it was still much higher in the P ‐limited infected cells than that in the nutrient‐replete cells. Moreover, phage pstS transcript number per cell was ∼20 times higher than the host copy, which may help maintain the host phosphate uptake rate during infection.

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Stochastic dilution effects weaken deterministic effects of niche‐based processes in species rich forests - Xugao Wang; Thorsten Wiegand; Nathan J. B. Kraft; Nathan G. Swenson; Stuart J. Davies; Zhanqing Hao; Robert Howe; Yiching Lin; Keping Ma; Xiangcheng Mi; Sheng‐Hsin Su; I‐Fang Sun; et al. (Ecology, 2016)
Recent theory predicts that stochastic dilution effects may result in species‐rich communities with statistically independent species spatial distributions, even if the underlying ecological processes structuring the community are driven by deterministic niche differences. Stochastic dilution is a consequence of the stochastic geometry of biodiversity where the identities of the nearest neighbors of individuals of a given species are largely unpredictable. Under such circumstances, the outcome of deterministic species interactions may vary greatly among individuals of a given species. Consequently, nonrandom patterns in the biotic neighborhoods of species, which might be expected from coexistence or community assembly theory (e.g., individuals of a given species are neighbored by phylogenetically similar species), are weakened or do not emerge, resulting in statistical independence of species spatial distributions. We used data on phylogenetic and functional similarity of tree species in five large forest dynamics plots located across a gradient of species richness to test predictions of the stochastic dilution hypothesis. To quantify the biotic neighborhood of a focal species we used the mean phylogenetic (or functional) dissimilarity of the individuals of the focal species to all species within a local neighborhood. We then compared the biotic neighborhood of species to predictions from stochastic null models to test if a focal species was surrounded by more or less similar species than expected by chance. The proportions of focal species that showed spatial independence with respect to their biotic neighborhoods increased with total species richness. Locally dominant, high‐abundance species were more likely to be surrounded by species that were statistically more similar or more dissimilar than expected by chance. Our results suggest that stochasticity may play a stronger role in shaping the spatial structure of species rich tropical forest communities than it does in species poorer forests. These findings represent an important step towards understanding the factors that govern the spatial configuration of local biotic communities. The stochastic dilution effect is a simple geometric mechanism that can explain why species’ spatial distributions in species‐rich communities approximate independence from their biotic neighborhood, even if deterministic niche processes are in effect.

One-step Real-time Food Quality Analysis by Simultaneous DSC–FTIR Microspectroscopy - Shan-Yang Lin; Chih-Cheng Lin (Critical Reviews in Food Science and Nutrition, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

Two new alkaloids from Melodinus hemsleyanus Diels - Pu-Zhao Zhang; Ya-Mei Zhang; Jian Gu; Guo-Lin Zhang (Natural Product Research, 2016)

A new flavonol glycoside from the florets of Carthamus tinctorius L. - Xue Xie; Jianming Zhou; Lin Sun; Hongda Zhang; Yiwu Zhao; Yaling Song; Xuejing Wang; Fuyong Ni; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)

New phenyl derivatives from endophytic fungus Botryosphaeria sp. SCSIO KcF6 derived of mangrove plant Kandelia candel - Zhi-ran Ju; Xiaochu Qin; Xiu-ping Lin; Jun-feng Wang; Kumaravel Kaliyaperumal; Yong-qi Tian; Juan Liu; Fen Liu; Zhengchao Tu; Shi-hai Xu; Yonghong Liu (Natural Product Research, 2016)

PhnW-PhnX Pathway in Dinoflagellates Not Functional to Utilize Extracellular Phosphonates - Yudong Cui; Xin Lin; Huan Zhang; Lingxiao Lin; Senjie Lin (Frontiers in Marine Science, 2016)

Crayfish Carapace Powder Adsorbing Heavy Metal Ions from Aqueous Solution: Capacity, Characterization, Mechanism - Yuntao Wang; Sujuan Wang; Hao Sun; Jieqiong Lei; Ting Ye; Liufeng Lin; Ling Wang (Journal of Aquatic Food Product Technology, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

Rainfall-Runoff Prediction Using Dynamic Typhoon Information and Surface Weather Characteristic Considering Monsoon Effects - Chih-Chiang Wei; Nien-Sheng Hsu; Chien-Lin Huang (Water Resources Management, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Characteristic pollen source area and vertical pollen dispersal and deposition in a mixed coniferous and deciduous broad-leaved woodland in the Changbai mountains, northeast China - Shengrui Zhang; Qinghai Xu; Marie-José Gaillard; Xianyong Cao; Jianyong Li; Liyan Zhang; Yuecong Li; Fang Tian; Liping Zhou; Fengyou Lin; Xiaolan Yang (Vegetation History and Archaeobotany, 2016)

Effect of Initial Stress on a Fiber-Reinforced Thermoelastic Porous Media Without Energy Dissipation - Qi-lin Xiong; Xiao-geng Tian (Transport in Porous Media, 2016)

Quantifying the reliability of four global datasets for drought monitoring over a semiarid region - Pari-Sima Katiraie-Boroujerdy; Nasrin Nasrollahi; Kuo-lin Hsu; Soroosh Sorooshian (Theoretical and Applied Climatology, 2016)

Time irreversibility of mean temperature anomaly variations over China - Fenghua Xie; Zuntao Fu; Lin Piao; Jiangyu Mao (Theoretical and Applied Climatology, 2016)

Developing a reliable model for aquifer vulnerability - Cheng-Shin Jang; Chien-Wen Lin; Ching-Ping Liang; Jui-Sheng Chen (Stochastic Environmental Research and Risk Assessment, 2016)

Efficacy of dexmedetomidine with cognitive behavioral therapy for treating chronic insomnia related to conditioned arousal: a randomized controlled trial - Xunjun Li; Xiaojiang Jiang; Yazhen Liu; Ying Lang; Yuanyuan Ye; Ling Lin; Juan Liu; Yuanfeng Zhang (Sleep and Biological Rhythms, 2016)

Sleep medicine in Taiwan - Ning-Hung Chen; Liang-Wen Hang; Chia-Mo Lin (Sleep and Biological Rhythms, 2016)

Radioactive source terms for the Fukushima nuclear accident - WuHui Lin; LiQi Chen; Wen Yu; Hao Ma; Zhi Zeng; Shi Zeng (Science China Earth Sciences, 2016)

Toward a unified model of Altaids geodynamics: Insight from the Palaeozoic polycyclic evolution of West Junggar (NW China) - Flavien Choulet; Michel Faure; Dominique Cluzel; Yan Chen; Wei Lin; Bo Wang; Bei Xu (Science China Earth Sciences, 2016)

Study on Optimal Grouting Timing for Controlling Uplift Deformation of a Super High Arch Dam - Peng Lin; Xiaoxu Zhu; Qingbin Li; Hongyuan Liu; Yongjun Yu (Rock Mechanics and Rock Engineering, 2016)

Dopaminergic genetic variation moderates the effect of nicotine on cigarette reward - Paul T. Harrell; Hui-Yi Lin; Jong Y. Park; Melissa D. Blank; David J. Drobes; David E. Evans (Psychopharmacology, 2016)

A Strategy for a Routine Pattern Informatics Operation Applied to Taiwan - Ling-Yun Chang; Chien-chih Chen; Yi-Hsuan Wu; Tzu-Wei Lin; Chien-Hsin Chang; Chih-Wen Kan (Pure and Applied Geophysics, 2016)

Sphere-formation culture of testicular germ cells in the common marmoset, a small New World monkey - Zachary Yu-Ching Lin; Orie Hikabe; Sadafumi Suzuki; Takamasa Hirano; Haruhiko Siomi; Erika Sasaki; Masanori Imamura; Hideyuki Okano (Primates, 2016)

A set of GFP-based organelle marker lines combined with DsRed-based gateway vectors for subcellular localization study in rice (Oryza sativa L.) - Tsung-Meng Wu; Ke-Chun Lin; Wei-Shiang Liau; Yun-Yang Chao; Ling-Hung Yang; Szu-Yun Chen; Chung-An Lu; Chwan-Yang Hong (Plant Molecular Biology, 2016)

A Role for Low Density Lipoprotein Receptor-Related Protein 1 in the Cellular Uptake of Tissue Plasminogen Activator in the Lungs - Swan Lin; Jennifer Racz; Melissa F. Tai; Kristina M. Brooks; Phillip Rzeczycki; Lauren J. Heath; Michael W. Newstead; Theodore J. Standiford; Gus R. Rosania; Kathleen A. Stringer (Pharmaceutical Research, 2016)

Temporal Information of Directed Causal Connectivity in Multi-Trial ERP Data using Partial Granger Causality - Vahab Youssofzadeh; Girijesh Prasad; Muhammad Naeem; KongFatt Wong-Lin (Neuroinformatics, 2016)

Climatic characteristics of thunderstorm days and the influence of atmospheric environment in Northwestern China - Ye Yu; Jiang-lin Li; Jin Xie; Chuan Liu (Natural Hazards, 2016)

Transplantation of Cerebral Dopamine Neurotrophic Factor Transducted BMSCs in Contusion Spinal Cord Injury of Rats: Promotion of Nerve Regeneration by Alleviating Neuroinflammation - Hua Zhao; Lei Cheng; Xinwen Du; Yong Hou; Yi Liu; Zhaoqiang Cui; Lin Nie (Molecular Neurobiology, 2016)

Activation of Transient Receptor Potential Vanilloid 4 is Involved in Neuronal Injury in Middle Cerebral Artery Occlusion in Mice - Pinghui Jie; Zihong Lu; Zhiwen Hong; Lin Li; Libin Zhou; Yingchun Li; Rong Zhou; Yebo Zhou; Yimei Du; Lei Chen; Ling Chen (Molecular Neurobiology, 2016)

Intrathymic Tfh/B Cells Interaction Leads to Ectopic GCs Formation and Anti-AChR Antibody Production: Central Role in Triggering MG Occurrence - Xiaoyan Zhang; Shasha Liu; Ting Chang; Jiang Xu; Chunmei Zhang; Feng Tian; Yuanjie Sun; Chaojun Song; Wei Yi; Hong Lin; Zhuyi Li; Kun Yang (Molecular Neurobiology, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Smad signal pathway regulates angiogenesis via endothelial cell in an adipose-derived stromal cell/endothelial cell co-culture, 3D gel model - Shiyu Lin; Jing Xie; Tao Gong; Sirong Shi; Tao Zhang; Na Fu; Yunfeng Lin (Molecular and Cellular Biochemistry, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Resveratrol prevents renal lipotoxicity in high-fat diet-treated mouse model through regulating PPAR-α pathway - Yan Zhou; Suxian Lin; Lihe Zhang; Yongji Li (Molecular and Cellular Biochemistry, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Critical role of IL-6 in dendritic cell-induced allergic inflammation of asthma - Yen-Lin Lin; Shun-Hua Chen; Jiu-Yao Wang (Journal of Molecular Medicine, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Biodegradation of atrazine by Arthrobacter sp. C3, isolated from the herbicide-contaminated corn field - H. Wang; Y. Liu; J. Li; M. Lin; X. Hu (International Journal of Environmental Science and Technology, 2016)

Soil Nitrous oxide and Carbon dioxide emissions following incorporation of above- and below-ground biomass of green bean - M. Shaaban; Q. Peng; R. Hu; S. Lin; J. Zhao (International Journal of Environmental Science and Technology, 2016)

Anti-angiogenic and anti-inflammatory effect of Magnolol in the oxygen-induced retinopathy model - Boyu Yang; Yue Xu; Shanshan Yu; Yongsheng Huang; Lin Lu; Xiaoling Liang (Inflammation Research, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea - Haifeng Jia; Cheng Zhang; Tariq Pervaiz; Pengcheng Zhao; Zhongjie Liu; Baoju Wang; Chen Wang; Lin Zhang; Jinggui Fang; Jianpu Qian (Functional & Integrative Genomics, 2016)

Exome sequencing identified FGF12 as a novel candidate gene for Kashin-Beck disease - Feng Zhang; Lanlan Dai; Weimin Lin; Wenyu Wang; Xuanzhu Liu; Jianguo Zhang; Tielin Yang; Xiaogang Liu; Hui Shen; Xiangding Chen; Lijun Tan; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Perceived reputation of others modulates empathic neural responses - Li Zheng; Qianfeng Wang; Xuemei Cheng; Lin Li; Guang Yang; Lining Sun; Xiaoli Ling; Xiuyan Guo (Experimental Brain Research, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Isolation, purification, and identification of antialgal substances in green alga Ulva prolifera for antialgal activity against the common harmful red tide microalgae - Ying-ying Sun; Hui Wang; Gan-lin Guo; Yin-fang Pu; Bin-lun Yan; Chang-hai Wang (Environmental Science and Pollution Research, 2016)

Oxidation of aniline aerofloat in flotation wastewater by sodium hypochlorite solution - Weixiong Lin; Jing Tian; Jie Ren; Pingting Xu; Yongkang Dai; Shuiyu Sun; Chun Wu (Environmental Science and Pollution Research, 2016)

Predicting biofilm thickness and biofilm viability based on the concentration of carbon-nitrogen-phosphorus by support vector regression - Shanshan Lin; Xinmin Wang; Yunlong Chao; Yude He; Ming Liu (Environmental Science and Pollution Research, 2016)

Subcellular distribution and uptake mechanism of di-n-butyl phthalate in roots of pumpkin (Cucurbita moschata) seedlings - Qingqi Lin; Xiuhong Yang; Xiongfei Huang; Shizhong Wang; Yuanqing Chao; Rongliang Qiu (Environmental Science and Pollution Research, 2016)

Effect of biochar on the extractability of heavy metals (Cd, Cu, Pb, and Zn) and enzyme activity in soil - Xing Yang; Jingjing Liu; Kim McGrouther; Huagang Huang; Kouping Lu; Xi Guo; Lizhi He; Xiaoming Lin; Lei Che; Zhengqian Ye; Hailong Wang (Environmental Science and Pollution Research, 2016)

Prediction of the sorption capacities and affinities of organic chemicals by XAD-7 - Kun Yang; Long Qi; Wei Wei; Wenhao Wu; Daohui Lin (Environmental Science and Pollution Research, 2016)

Complete Genome of a Novel Pseudoalteromonas Phage PHq0 - Duo-bing Wang; Yan Li; Meng-qi Sun; Jin-peng Huang; Hong-bing Shao; Qi-lin Xin; Min Wang (Current Microbiology, 2016)

A study of biases in simulation of the Indian Ocean basin mode and its capacitor effect in CMIP3/CMIP5 models - Weichen Tao; Gang Huang; Kaiming Hu; Hainan Gong; Guanhuan Wen; Lin Liu (Climate Dynamics, 2016)

Northern East Asian low and its impact on the interannual variation of East Asian summer rainfall - Zhongda Lin; Bin Wang (Climate Dynamics, 2016)

Groundwater Molybdenum from Emerging Industries in Taiwan - Kuo-Sheng Tsai; Yu-Min Chang; Jimmy C. M. Kao; Kae-Long Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Effects of Hypoxia on the Physiology of Zebrafish (Danio rerio): Initial Responses, Acclimation and Recovery - Jianfeng Feng; Ying Guo; Yongfei Gao; Lin Zhu (Bulletin of Environmental Contamination and Toxicology, 2016)

Cortical thickness and surface area in neonates at high risk for schizophrenia - Gang Li; Li Wang; Feng Shi; Amanda E. Lyall; Mihye Ahn; Ziwen Peng; Hongtu Zhu; Weili Lin; John H. Gilmore; Dinggang Shen (Brain Structure and Function, 2016)

Niching sustainability in an Indigenous community: protected areas, autonomous initiatives, and negotiating power in natural resource management - Pei-Shan Sonia Lin; Yen-Lan Liu (Sustainability Science, 2016)

Time-domain hyperbolic Radon transform for separation of P-P and P-SV wavefields - Xiaoxue Jiang; Fan Zheng; Haiqing Jia; Jun Lin; Hongyuan Yang (Studia Geophysica et Geodaetica, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Geomorphologic analysis and physico-dynamic characteristics of Zhatai-Gully debris flows in SW China - Xi-lin Liu; Chuan Tang; Hua-yong Ni; Yuan Zhao (Journal of Mountain Science, 2016)

Gymnocypris przewalskii decreases cytosolic carbonic anhydrase expression to compensate for respiratory alkalosis and osmoregulation in the saline-alkaline lake Qinghai - Zongli Yao; Wenfei Guo; Qifang Lai; Jianquan Shi; Kai Zhou; Hongfang Qi; Tingting Lin; Ziniu Li; Hui Wang (Journal of Comparative Physiology B, 2016)

Wide-area ionospheric delay model for GNSS users in middle- and low-magnetic-latitude regions - An-Lin Tao; Shau-Shiun Jan (GPS Solutions, 2016)

Prenatal molecular cytogenetic analysis of a mild dysmorphic fetus with a huge unbalance karyotype involving partial 9p deletion and partial 18q duplication - Yueh-Chun Li; Yi-Ju Pan; Fuu-Jen Tsai; Chyi-Chyang Lin (Genes & Genomics, 2016)

Short Peptides and Telomere Length Regulator Hormone Irisin - V. Kh. Khavinson; B. I. Kuznik; S. I. Tarnovskaya; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2016)

Impact of IL-8-251A/T gene polymorphism on severity of disease caused by enterovirus 71 infection - Daoyan Xu; Jian Li; Xiangjuan Huang; Aiwei Lin; Zhongtao Gai; Zongbo Chen (Archives of Virology, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Roles of microRNA-1 in hypoxia-induced apoptotic insults to neuronal cells - Chia-Yu Chang; Tai-Ngar Lui; Jia-Wei Lin; Yi-Ling Lin; Chung-Hsi Hsing; Jhi-Joung Wang; Ruei-Ming Chen (Archives of Toxicology, 2016)

Autoinducer-2 signaling is involved in regulation of stress-related genes of Deinococcus radiodurans - Lin Lin; Tao Li; Shang Dai; Jiangliu Yu; Xiuqin Chen; Liangyan Wang; Yunguang Wang; Yuejin Hua; Bing Tian (Archives of Microbiology, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Revisiting the second EOF mode of interannual variation in summer rainfall over East China - Zhongda Lin; Qin Su; Riyu Lu (Advances in Atmospheric Sciences, 2016)

Bioinformatics analysis and expression of a novel protein ROP48 in Toxoplasma gondii - Jian Zhou; Lin Wang; Aihua Zhou; Gang Lu; Qihang Li; Zhilin Wang; Meiyan Zhu; Huaiyu Zhou; Hua Cong; Shenyi He (Acta Parasitologica, 2016)
is an obligate intracellular apicomplexan parasite, and can infect warmblooded animals and humans all over the world. In the past years, ROP family genes encoding particular proteins of

New magnetostratigraphic and pedostratigraphic investigations of loess deposits in north‐east China and their implications for regional environmental change during the Mid‐Pleistocene climatic transition - Lin Zeng; Huayu Lu; Shuangwen Yi; Yongxiang Li; Anqi Lv; Wenchao Zhang; Zhiwei Xu; Haifeng Wu; Han Feng; Mengchun Cui (Journal of Quaternary Science, 2016)
Little is known about the long‐term climatic evolution of north‐eastern (NE) China, because well‐preserved terrestrial paleoenvironmental archives are scarce in this vast region. The extensive loess deposits in the Chifeng region are the thickest and most complete loess–paleosol sequence in NE China, and have significant potential for reconstructing the paleoclimate of the region. Here, we present new high‐resolution magnetostratigraphic results from two loess–paleosol sections in the Chifeng region: the Sanbahuo (SBH) and Toudaojingzi (TDJZ) sections. The results demonstrate that both sections record the Brunhes normal polarity chron and the upper portion of the Matuyama reversed polarity chron. Based on these new results, the base of the TDJZ loess sequence is dated at ca. 1.22 Ma, representing the oldest known loess deposits in NE China. The initiation of loess accumulation in NE China was roughly synchronous with the large expansion of the Eurasian loess belt during the late Early Pleistocene (1.2–0.7 Ma), probably reflecting a widespread intensification of aridity in northern mid‐latitudes. We suggest that global cooling during the Mid‐Pleistocene climatic transition led to increased aridity and more favorable conditions for promoting the availability of silt for entrainment, transport and deposition.